Polyamide-cellulose resin composition
By using polyamide, polyphenylene ether or crystalline resin in the resin composition and adding cellulose nanofibers, the problems of insufficient rigidity of the material and high thermal expansion coefficient in the prior art are solved, and resin compositions with high rigidity, low thermal expansion coefficient and low water absorption are achieved, which are suitable for the lightweight and high strength requirements of automotive exterior components.
Patent Information
- Application Number
- CN202080072847.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-13
- Filing Date
- 2020-10-23
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2040-10-23
AI Technical Summary
In the prior art, the room temperature and high temperature rigidity of polypropylene-based materials are insufficient, making it difficult to be suitable for vertical parts of automobiles; while although the polyamide/polyphenylene ether-based alloy materials have high rigidity, their high thermal expansion coefficient causes large dimensional changes when the temperature changes, affecting contact with adjacent parts; in addition, when mixing inorganic fillers to suppress thermal expansion coefficient, it will damage the lightweight effect and impact strength, resulting in poor physical stability.
A resin composition is adopted, which comprises a polyamide forming a continuous phase, a polyphenylene ether or a crystalline resin forming a dispersed phase, and cellulose nanofibers are added to improve the rigidity and thermal stability of the material while reducing the coefficient of thermal expansion and water absorption.
It achieves comprehensive performance of low specific gravity, high rigidity, low thermal expansion coefficient and low water absorption, and is suitable for the lightweight and high strength requirements of automotive exterior components.
Smart Images

Figure CN114555710B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition comprising polyamide and cellulose. Background Art
[0002] Thermoplastic resins are widely used in various fields such as automobile components, electrical and electronic components, office equipment housings, and precision parts due to their light weight and excellent processing characteristics. In the automotive industry in particular, in order to improve fuel efficiency compared to the past, the replacement of metal components with resin components has been promoted. In recent years, in regions centered on China and Europe, the transition to electric vehicles has begun rapidly, and the development of electric vehicles has begun actively. Therefore, in order to extend the cruising range of electric vehicles, the lightweighting of vehicles has become an urgent issue. The replacement of metal components with resin components is effective for lightweighting automobiles, especially the resinization of large-volume exterior components contributes greatly to lightweighting, so automobile manufacturers have invested more energy in this regard.
[0003] As resin exterior parts, polypropylene-based materials are widely used, mainly in bumpers, etc. In addition, in fenders as vertical parts, the use of polyamide / polyphenylene ether-based alloy materials as described in Patent Document 1 is studied from the perspective of rigidity, heat resistance, etc. In addition, in order to further improve dimensional accuracy, for example, Patent Documents 2 and 3 have studied the mixing of inorganic fillers.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2002 / 094936
[0007] Patent Document 2: International Publication No. 2006 / 077818
[0008] Patent Document 3: Japanese Patent Application Publication No. 2006-199748 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, polypropylene-based materials are not suitable for plate-shaped members (door panels, fenders, etc.) in vertical parts because of their insufficient room temperature and high temperature rigidity. In addition, although polyamide / polyphenylene ether-based alloy materials have the rigidity to be used for fenders, the alloy materials have a high thermal expansion coefficient (approximately about 90 ppm / K).
[0011] Automobiles are designed to be driven in a variety of driving environments. For example, in extremely cold regions and deserts, the surface temperature difference of components can be around 100°C. In the case of the thermal expansion coefficient of this alloy material, if a component with a length of 70 cm is used for calculation, the dimensional change is about 6 mm. In this case, in order to avoid contact with adjacent components due to thermal expansion, a gap of several mm needs to be prepared in advance. This is a big issue for passenger cars that attach great importance to design.
[0012] In order to suppress the thermal expansion coefficient, the technology of mixing inorganic fillers has been considered. However, in the materials obtained by this technology, the addition of high-density inorganic fillers will damage the lightweight effect of using resin components, reduce impact strength, cause warping or anisotropy in the product, and further have new problems such as poor stability of physical properties. Therefore, it has not yet been widely adopted.
[0013] On the other hand, since the horizontal parts of automobiles (such as the hood and roof) are large parts, further improvements in thermal expansion and anisotropy are required, and in fact, no progress has been made in replacing metal parts with resin parts.
[0014] In recent years, as fillers, reinforced resins made of cellulose such as cellulose nanofibers (CNF) have been studied. Cellulose-reinforced polyamides, especially cellulose nanofiber-reinforced polyamides, have the advantages of low specific gravity, high rigidity (especially high rigidity at high temperatures), and low thermal expansion coefficients, and it is required to further improve these properties. In addition, cellulose nanofiber-reinforced polyamides have low specific gravity, high rigidity, and low thermal expansion coefficients, but on the other hand, they have the problem of high water absorption. When the water absorption in cellulose-reinforced resins is high, it may become a cause of reduced physical properties, deformation of molded bodies accompanied by dimensional changes, etc. due to water absorption. That is, the current status is that a material that simultaneously achieves low specific gravity, high rigidity, low thermal expansion coefficient, and low water absorption has not yet been obtained. In addition, in order to replace metal components with resin components, a resin composition with low specific gravity and at the same time highly taking into account the opposite characteristics of high toughness and low thermal expansion is also required, but the current status is that such a resin composition has not yet been obtained.
[0015] The purpose of one embodiment of the present invention is to solve the above-mentioned problems, and to provide a resin composition that particularly highly takes into account low specific gravity, high rigidity and low linear expansion coefficient. In addition, the purpose of another embodiment of the present invention is to provide a resin composition that simultaneously achieves low specific gravity, high rigidity, low thermal expansion coefficient and low water absorption. In addition, the purpose of another embodiment of the present invention is to provide a resin composition with low specific gravity or with low specific gravity and low physical anisotropy and simultaneously highly takes into account the opposite characteristics of high toughness and low thermal expansion.
[0016] Means for solving problems
[0017] The present disclosure includes the following aspects.
[0018] 《First Implementation Mode》
[0019] [1] A resin composition comprising:
[0020] The first polymer forming the continuous phase,
[0021] a second polymer forming a dispersed phase, and
[0022] cellulose,
[0023] in,
[0024] The first polymer is polyamide,
[0025] The second polymer is at least one polymer selected from the group consisting of a crystalline resin having a melting point of 60° C. or higher and an amorphous resin having a glass transition point of 60° C. or higher.
[0026] [2] A resin composition comprising:
[0027] Polyamide,
[0028] Polyphenylene ether, and
[0029] Cellulose nanofibers,
[0030] The polyamide forms a continuous phase, and the polyphenylene ether forms a dispersed phase.
[0031] [3] The resin composition according to the above embodiment 2, wherein the amount of the polyphenylene ether is 30 to 150 parts by mass based on 100 parts by mass of the polyamide.
[0032] [4] The resin composition according to the above aspect 2 or 3, wherein at least a part of the polymer present in the dispersed phase has an acidic functional group.
[0033] [5] The resin composition according to any one of aspects 2 to 4, wherein the polyphenylene ether is present in the continuous phase of the polyamide as dispersed particles having a number average particle size of 3 μm or less.
[0034] [6] The resin composition according to any one of the above aspects 2 to 5, wherein
[0035] The polyphenylene ether is present in the continuous phase of the polyamide in the form of dispersed particles.
[0036] The dispersed particles have a volume ratio such that the volume ratio of particles having a particle size of 1 μm or more is 30 volume % or less.
[0037] [7] The resin composition according to any one of aspects 2 to 6 above, further comprising an elastomer.
[0038] [8] The resin composition according to the above embodiment 7, wherein the polyphenylene ether forms a continuous phase and the elastomer forms a dispersed phase inside the dispersed phase of the polyphenylene ether.
[0039] [9] A resin composition as described in the above embodiment 7 or 8, wherein the above elastomer is one or more selected from the group consisting of ethylene-α-olefin copolymers, block copolymers of aromatic vinyl compounds and conjugated diene compounds, and hydrogenated block copolymers of aromatic vinyl compounds and conjugated diene compounds.
[0040]
[10] The resin composition according to any one of aspects 7 to 9 above, wherein the elastomer is an acid anhydride-modified elastomer.
[0041]
[11] The resin composition according to any one of aspects 7 to 10, wherein the elastomer is a mixture of an elastomer having an acidic functional group and an elastomer not having an acidic functional group.
[0042]
[12] The resin composition according to any one of aspects 2 to 11, wherein more than 50% by mass of the cellulose nanofibers are present in the polyamide phase.
[0043]
[13] A resin composition as described in any one of the above embodiments 2 to 12, wherein the orientation degree of cellulose nanofibers determined by a small-angle X-ray scattering method in the central part of a multi-purpose test piece formed by molding the resin composition according to ISO 294-1 is 0.45 or less.
[0044]
[14] The resin composition according to any one of aspects 2 to 13 above, wherein the amount of the cellulose nanofibers is 0.1 to 30% by mass relative to 100% by mass of the resin composition.
[0045]
[15] The resin composition according to any one of aspects 2 to 14 above, wherein the cellulose nanofibers are hydrophobized cellulose nanofibers.
[0046]
[16] The resin composition according to the above aspect 15, wherein the hydrophobized cellulose nanofibers are acetylated cellulose nanofibers.
[0047]
[17] A resin composition as described in any one of the above methods 2 to 16, wherein the weight average molecular weight (Mw) of the above cellulose nanofibers is greater than 100,000, and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is less than 6.
[0048]
[18] The resin composition according to any one of aspects 2 to 17 above, wherein the cellulose nanofibers have an average alkali-soluble polysaccharide content of 12% by mass or less and a crystallinity of 60% or more.
[0049]
[19] A resin composition as described in any one of the above aspects 1 to 18, wherein the polyamide is one or more selected from the group consisting of polyamide 6, polyamide 10, polyamide 11, polyamide 12, polyamide 66, polyamide 610, polyamide 612, polyamide 6 / 6I, polyamide 66 / 6I, polyamide 6I, and mixtures thereof.
[0050]
[20] A resin composition as described in any one of the above aspects 1 to 19, wherein the viscosity value (V N ) is less than 200.
[0051]
[21] The resin composition according to any one of aspects 1 to 20, further comprising a saponified ethylene-vinyl ester copolymer.
[0052]
[22] The resin composition according to any one of aspects 1 to 21 above, further comprising an antioxidant.
[0053]
[23] The resin composition according to any one of aspects 1 to 22 above, further comprising a colorant.
[0054]
[24] The resin composition according to any one of aspects 1 to 23 above, wherein the thermal expansion coefficient at 20°C to 100°C is 50 ppm / K or less.
[0055]
[25] A molded article comprising the resin composition according to any one of aspects 1 to 24.
[0056]
[26] An automobile exterior part comprising the resin composition according to any one of aspects 1 to 24 above.
[0057] Second Implementation Method
[0058] [1] A resin composition comprising:
[0059] Polyamide;
[0060] One or more elastomers selected from the group consisting of aromatic vinyl compound-conjugated diene compound block copolymers and derivatives thereof; and
[0061] Cellulose, among which
[0062] The polyamide and the elastomer are phase separated.
[0063] More than 50% by mass of the above-mentioned cellulose is present in the polyamide phase.
[0064] [2] The resin composition according to the above aspect 1, wherein the polyamide forms a continuous phase and the elastomer forms a dispersed phase.
[0065] [3] The resin composition according to the above embodiment 1 or 2, wherein the polyamide is one or more selected from the group consisting of polyamide 6, polyamide 10, polyamide 11, polyamide 12, polyamide 66, polyamide 610, polyamide 612, polyamide 6 / 6I, polyamide 66 / 6I, polyamide 6I, and mixtures thereof.
[0066] [4] The resin composition according to any one of the above aspects 1 to 3, wherein the viscosity value (V N ) is less than 200.
[0067] [5] The resin composition according to any one of aspects 1 to 4 above, wherein the amount of the elastomer is 1 to 50 parts by mass based on 100 parts by mass of the polyamide.
[0068] [6] The resin composition according to any one of the above aspects 1 to 5, wherein the derivative comprises an acid-modified product of an aromatic vinyl compound-conjugated diene compound block copolymer.
[0069] [7] The resin composition according to the above embodiment 6, wherein the elastomer is a mixture of a polymer having an acidic functional group and a polymer having no acidic functional group.
[0070] [8] The resin composition according to any one of the above aspects 1 to 7, wherein
[0071] The elastomer exists in the form of dispersed particles in the polyamide continuous phase.
[0072] The dispersed particles have a number average particle size of 3 μm or less.
[0073] [9] The resin composition according to any one of the above aspects 1 to 8, wherein
[0074] The elastomer exists in the form of dispersed particles in the polyamide continuous phase.
[0075] The dispersed particles have a volume ratio such that the volume ratio of particles having a particle size of 1 μm or more is 30 volume % or less.
[0076]
[10] The resin composition according to any one of aspects 1 to 9 above, wherein the amount of cellulose is 0.1 to 30% by mass relative to 100% by mass of the resin composition.
[0077]
[11] A resin composition as described in any one of the above embodiments 1 to 10, wherein the cellulose is a cellulose nanofiber having a diameter of 50 to 1000 nm and a length (L) / diameter (D) ratio of 30 or more, a cellulose nanocrystal having a diameter of 100 nm or less and a length (L) / diameter (D) ratio of less than 30, or a cellulose microfiber having a diameter greater than 1 μm to 50 μm, or a mixture of two or more thereof.
[0078]
[12] The resin composition according to the above aspect 11, wherein the amount of the cellulose microfibers is 0.1 to 20% by mass relative to 100% by mass of the resin composition.
[0079]
[13] The resin composition according to any one of aspects 1 to 12 above, wherein the cellulose is hydrophobized cellulose.
[0080]
[14] The resin composition according to any one of aspects 1 to 13 above, wherein the hydrophobized cellulose is acetylated cellulose.
[0081]
[15] The resin composition according to any one of aspects 1 to 14, further comprising a conductive carbon filler.
[0082]
[16] The resin composition according to any one of aspects 1 to 15 above, further comprising an antioxidant.
[0083]
[17] The resin composition according to any one of aspects 1 to 16 above, further comprising a colorant.
[0084]
[18] The resin composition according to any one of aspects 1 to 17 above, wherein the thermal expansion coefficient at 20°C to 100°C is 60 ppm / K or less.
[0085]
[19] A molded article comprising the resin composition according to any one of aspects 1 to 18 above.
[0086]
[20] An automobile exterior part comprising the resin composition according to any one of aspects 1 to 18 above.
[0087] 《Third Implementation Mode》
[0088] [1] A resin composition comprising:
[0089] Polyamide,
[0090] Ethylene-vinyl ester copolymer saponification product, and
[0091] Cellulose.
[0092] [2] The resin composition according to the above embodiment 1, wherein the amount of the saponified ethylene-vinyl ester copolymer is 1 to 100 parts by mass based on 100 parts by mass of the polyamide.
[0093] [3] The resin composition according to the above aspect 1 or 2, wherein the amount of the saponified ethylene-vinyl ester copolymer is 50 to 5000 parts by mass based on 100 parts by mass of the cellulose.
[0094] [4] The resin composition according to any one of aspects 1 to 3 above, wherein the amount of the cellulose is 0.1 to 30% by mass relative to 100% by mass of the resin composition.
[0095] [5] The resin composition according to any one of aspects 1 to 4 above, wherein the polyamide forms a continuous phase.
[0096] [6] The resin composition according to any one of the above aspects 1 to 5, wherein the polyamide is one or more selected from the group consisting of polyamide 6, polyamide 10, polyamide 11, polyamide 12, polyamide 66, polyamide 610, polyamide 612, polyamide 6 / 6I, polyamide 66 / 6I, polyamide 6I, and mixtures thereof.
[0097] [7] The resin composition according to any one of the above aspects 1 to 6, wherein the viscosity value (V N ) is less than 200.
[0098] [8] The resin composition according to any one of aspects 1 to 7 above, further comprising an elastomer.
[0099] [9] The resin composition as described in the above embodiment 8, wherein the above elastomer is one or more selected from the group consisting of ethylene-α-olefin copolymers, block copolymers of aromatic vinyl compounds and conjugated diene compounds, and hydrogenated block copolymers of aromatic vinyl compounds and conjugated diene compounds.
[0100]
[10] The resin composition according to the above aspect 8 or 9, wherein the amount of the elastomer is 1 to 50 parts by mass based on 100 parts by mass of the polyamide.
[0101]
[11] The resin composition according to any one of aspects 8 to 10, wherein the elastomer is an acid anhydride-modified elastomer.
[0102]
[12] The resin composition according to any one of aspects 8 to 11, wherein the elastomer is a mixture of a polymer having an acidic functional group and a polymer having no acidic functional group.
[0103]
[13] The resin composition according to any one of aspects 1 to 12, wherein the proportion of the vinyl alcohol unit is 60 mol% or more relative to 100 mol% of all monomer units constituting the saponified ethylene-vinyl ester copolymer.
[0104]
[14] A resin composition as described in any one of the above embodiments 1 to 13, wherein the cellulose is a cellulose nanofiber having a diameter of 50 to 1000 nm and a length (L) / diameter (D) ratio of 30 or more, a cellulose nanocrystal having a diameter of 100 nm or less and a length (L) / diameter (D) ratio of less than 30, or a cellulose microfiber having a diameter greater than 1 μm to 50 μm, or a mixture of two or more thereof.
[0105]
[15] The resin composition according to aspect 14 above, wherein the amount of the cellulose microfibers is 0.1 to 20% by mass relative to 100% by mass of the resin composition.
[0106]
[16] The resin composition according to any one of aspects 1 to 15 above, wherein the cellulose is a hydrophobized cellulose.
[0107]
[17] The resin composition according to the above embodiment 16, wherein the hydrophobized cellulose is acetylated cellulose.
[0108]
[18] The resin composition according to any one of aspects 1 to 17 above, further comprising polyphenylene ether.
[0109]
[19] The resin composition according to any one of aspects 1 to 18 above, further comprising an antioxidant.
[0110]
[20] The resin composition according to any one of aspects 1 to 19 above, further comprising a colorant.
[0111]
[21] The resin composition according to any one of aspects 1 to 20 above, wherein the linear thermal expansion coefficient at 20°C to 100°C is 70 ppm / K or less.
[0112]
[22] The resin composition according to any one of aspects 1 to 21 above, wherein the tensile breaking strain is 10% or more.
[0113]
[23] A molded article comprising the resin composition according to any one of aspects 1 to 22.
[0114]
[24] An automobile exterior part comprising the resin composition according to any one of aspects 1 to 22 above.
[0115] Effects of the Invention
[0116] According to one embodiment of the present invention, a resin composition that particularly highly combines low specific gravity, high rigidity and low linear expansion coefficient can be provided. In addition, according to another embodiment of the present invention, a resin composition that simultaneously achieves low specific gravity, high rigidity, low thermal expansion coefficient and low water absorption can be provided. In addition, according to yet another embodiment of the present invention, a resin composition that has low specific gravity or low specific gravity and low physical property anisotropy and simultaneously highly combines contradictory properties such as high toughness and low thermal expansion can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0117] Figure 1 is a microscope image showing an example of cellulose nanofibers.
[0118] Figure 2 is a microscope image showing an example of cellulose nanocrystals.
[0119] Figure 3 is a microscope image showing an example of cellulose microfibrils.
[0120] Figure 4 This is an explanatory diagram of the calculation method of the IR index 1730 and the IR index 1030.
[0121] Figure 5 This is a diagram for explaining the method of calculating the average degree of substitution of hydroxyl groups in cellulose.
[0122] Figure 6 It is a schematic diagram showing the shape of the fender produced for fender evaluation in Examples and Comparative Examples.
[0123] Figure 7 The diagram shows the positions where test pieces are taken out for fender evaluation in Examples and Comparative Examples. DETAILED DESCRIPTION
[0124] The following is an explanation of the embodiment of the present invention (hereinafter referred to as "the present embodiment"), but the present invention is not limited to these embodiments. In addition, unless otherwise specified, the characteristic values of the present disclosure are values measured by the method described in the [Examples] of the present disclosure or by a method that is understood by those skilled in the art to be equivalent thereto.
[0125] 《Resin composition》
[0126] This embodiment includes the following first to third embodiments.
[0127] The first embodiment comprises a first polymer forming a continuous phase, a second polymer forming a dispersed phase (thus, a polymer different from the first polymer), and cellulose. In one embodiment, the first polymer is a polyamide, and the second polymer is at least one polymer selected from the group consisting of a crystalline resin having a melting point of 60°C or higher and an amorphous resin having a glass transition point of 60°C or higher. In such a resin composition, low specific gravity, high rigidity, and low thermal expansion coefficient can be achieved at a particularly high level.
[0128] In the present disclosure, the crystalline resin refers to a resin having an endothermic peak due to crystal melting when the temperature is increased from 23° C. at a temperature increase rate of 10° C. / min using a differential scanning calorimeter (DSC).
[0129] In the present disclosure, the amorphous resin refers to a resin that does not have an endothermic peak due to crystal melting when the temperature is increased from 23° C. at a temperature increase rate of 10° C. / min using a differential scanning calorimeter (DSC).
[0130] In the present disclosure, the term "elastomer" refers to a substance (specifically, a natural or synthetic polymer substance) that is elastic at room temperature (23°C). In addition, the term "elastic" refers to a substance that has a storage modulus of 1 MPa to 100 MPa at 23°C and 10 Hz measured by a dynamic viscoelasticity measurement.
[0131] In a mode of the first embodiment, the resin composition includes polyamide, polyphenylene ether and cellulose nanofiber. In the resin composition, phase separation occurs between polyamide and polyphenylene ether, and polyamide forms a continuous phase and polyphenylene ether forms a dispersed phase. Utilizing such a phase structure, the high water absorption of polyphenylene ether can be utilized to reduce the effect of water absorption without damaging the various characteristics (especially high heat resistance, low linear expansion coefficient, etc.) originally possessed by polyamide to make up for the high water absorption as the shortcoming of cellulose nanofiber reinforced polyamide, and then the high rigidity (especially high rigidity in high temperature region) and low specific gravity possessed by polyphenylene ether can also be well shown. Therefore, the above-mentioned resin composition can have low specific gravity, high rigidity, low thermal expansion coefficient and low water absorption.
[0132] In one embodiment, at least a portion of the polymer (e.g., polyphenylene ether) present in the dispersed phase has an acidic functional group. The dispersed phase, such as the acidic modified group of polyphenylene ether, reacts with the amino terminal of polyamide, thereby appropriately improving the compatibility of the continuous phase and the dispersed phase, reducing the dispersed size of the dispersed phase, and being able to suppress the interfacial peeling of the continuous phase and the dispersed phase. From the perspective of better showing the above-mentioned advantages brought by the coexistence of the continuous phase and the dispersed phase, this situation is favorable. In addition, compared with the affinity for, for example, polyphenylene ether, cellulose (e.g., cellulose nanofibers) has a higher affinity for polyamide, so the cellulose is mainly present in the polyamide phase. This is believed to be due to the hydrogen bond between cellulose and polyamide. Cellulose (especially cellulose nanofibers) contributes to the low linear expansion coefficient and high rigidity (especially high rigidity in high temperature regions) of the resin composition. In this way, according to the resin composition of the first embodiment, a resin composition that achieves high rigidity, low thermal expansion coefficient, low specific gravity and low water absorption can be provided while using cellulose (especially cellulose nanofibers).
[0133] The second embodiment provides a resin composition comprising polyamide, one or more elastomers (hereinafter also referred to as the elastomer of the second embodiment) selected from the group consisting of aromatic vinyl compound-conjugated diene compound block copolymer and derivatives thereof, and cellulose. In one mode, polyamide and elastomer are phase separated. In one mode, cellulose exceeding 50% by mass is present in the polyamide phase. In a representative mode, the resin composition has a 2-phase structure of a polyamide phase and an elastomer phase. The resin composition of the second embodiment is not excluded from having more than 3 phases, but the present disclosure mainly describes the resin composition of the 2-phase structure of the polyamide phase and the elastomer phase as the representative mode of the second embodiment. The resin composition of the second embodiment can have high toughness and low linear expansion. In one mode, the resin composition can have a high fluidity that can also cope with the manufacture of a large-scale molded body, and then a molded body substantially not including partial strength defects can be provided.
[0134] The phase morphology of the resin composition of the second embodiment can have the following morphologies: a morphology in which polyamide forms a continuous phase and an elastomer forms a dispersed phase; a morphology in which polyamide forms a dispersed phase and an elastomer forms a continuous phase; and a morphology in which both polyamide and an elastomer form a continuous phase (i.e., a co-continuous phase structure). From the perspective of being able to exhibit good heat resistance as a composition, achieving high rigidity, and low linear expansion, a morphology in which polyamide forms a continuous phase and an elastomer forms a dispersed phase is preferred.
[0135] Usually, cellulose has hydrophilicity, and therefore has high affinity with polyamide, and may also have affinity for at least a portion of the polymer that has been acid-modified (i.e. at least a portion has an acidic functional group). It is also known that the cellulose of micronization may be captured by the elastomeric component with high viscosity. On the other hand, the hydrophilicity of the cellulose of the known hydrophobic treatment described later is reduced, and thus its presence position in the resin combination may change due to the mixing conditions.
[0136] About the ratio of the cellulose (cellulose nanofiber in a specific way) in the resin composition of the first embodiment, and the ratio of the cellulose (cellulose nanofiber in a specific way) in the polyamide phase, and the ratio of the cellulose in the resin composition of the second embodiment, the lower limit of the ratio is preferably more than 50 mass %, more preferably 60 mass %, further preferably 70 mass %, and then preferably 75 mass %, and then more preferably 80 mass %, most preferably 100 mass % (i.e. substantially all cellulose is present in the polyamide phase). In the case where the above-mentioned ratio is within the above-mentioned range, in the first embodiment, low thermal expansion and high rigidity can be taken into account more highly, or in the second embodiment, various opposite characteristics such as low thermal expansion, low anisotropy and high toughness can be taken into account. From the aspect of the ease of manufacture of the resin composition, the upper limit of the above-mentioned ratio can be, for example, 99 mass % or 98 mass %.
[0137] For each cellulose of the cellulose in the resin composition of the first embodiment (cellulose nanofiber in a specific manner) and the cellulose in the resin composition of the second embodiment, as an example of a method for confirming that more than 50% by mass is present in the polyamide phase, for example, the resin composition can be photographed using a transmission electron microscope to confirm the area of cellulose present in the polyamide phase and the area of cellulose present in other phases (for example, the polyphenylene ether of the first embodiment or the elastomer phase of the second embodiment), thereby confirming. The above method is useful, for example, when the ratio of the presence of cellulose in the polyamide phase and the other phase is significantly different and does not require quantitative determination. On the other hand, when quantitative determination is required, the resin composition is sliced with a thickness of about 0.1 to 2 μm to obtain a film-like sample. The sample is immersed in a solvent (for example, chloroform, toluene, etc.) that can dissolve other phase components (for example, polyphenylene ether components or elastomer components) but does not dissolve polyamide, so that other phases are dissolved, and after the eluate is concentrated, ultracentrifugal separation is performed to separate the cellulose present in other phases, and then the washing using the solvent is repeatedly performed at least 3 times, and it is dried to measure the amount of cellulose present in other phases.
[0138] The third embodiment provides a resin composition comprising polyamide, ethylene-vinyl ester copolymer saponification, and cellulose. In the resin composition of the third embodiment, cellulose is stably micro-dispersed in the polyamide phase, so that, for example, a low linear thermal expansion coefficient can be provided even when formed into a large-scale molded body. In addition, the resin composition can have a high tensile fracture strain (i.e., high toughness) due to the contribution of the ethylene-vinyl ester copolymer saponification.
[0139] The resin composition of the present embodiment can be suitably used for various molded products, particularly various large parts (for example, automobile exterior parts, etc.), because it has the above-mentioned excellent properties.
[0140] Next, each component that can be used in this embodiment will be described in detail.
[0141] <First polymer (polyamide)>
[0142] As the polyamide used in the first to third embodiments, polycondensates of dibasic acids and diamines, cyclic lactam ring-opening polymers, polycondensates of aminocarboxylic acids, and copolymers and blends thereof can be cited. More specifically, aliphatic polyamides such as polyamide 6, polyamide 10, polyamide 11, polyamide 12, polyamide 46, polyamide 66, polyamide 610, and polyamide 612, aromatic polyamide resins such as poly(m-xylene adipamide) (polyamide MXD6), polyhexamethylene terephthalamide (polyamide 6T), and polyhexamethylene isophthalamide (polyamide 6I), and copolymers and blends such as polyamide 6 / 6I, polyamide 66 / 6I, polyamide 6 / 6T, polyamide 66 / 6T, polyamide 6 / 66 / 6T, polyamide 6 / 66 / 6I, polyamide 9T, and polyamide 10T can be used. Among these, polyamide 6, polyamide 10, polyamide 11, polyamide 12, polyamide 66, polyamide 610, polyamide 612, polyamide 6 / 6I, polyamide 66 / 6I, polyamide 6I, and mixtures thereof are particularly preferably used. Polyamide 6, polyamide 66, polyamide 610, polyamide 612, polyamide 6I, and mixtures thereof are most preferred.
[0143] In the first to third embodiments, the terminal carboxyl group concentration of the polyamide is not particularly limited, but the lower limit is preferably 5 μmol / g, 10 μmol / g, 20 μmol / g, 25 μmol / g, or 30 μmol / g. In addition, the upper limit of the terminal carboxyl group concentration is preferably 150 μmol / g, 100 μmol / g, or 80 μmol / g.
[0144] In the first to third embodiments, the terminal amino group concentration of the polyamide is not particularly limited, but the lower limit is preferably 20 μmol / g or 30 μmol / g, and the upper limit is preferably 150 μmol / g, 100 μmol / g, or 80 μmol / g.
[0145] In the polyamides of the first to third embodiments, the ratio of carboxyl terminal groups to all terminal groups ([COOH] / [all terminal groups]) is preferably 0.20 to 0.95. The lower limit of the carboxyl terminal group ratio is more preferably 0.3, further preferably 0.35, still more preferably 0.40, and most preferably 0.45. In addition, the upper limit of the carboxyl terminal group ratio is more preferably 0.90, still more preferably 0.85, and most preferably 0.80. From the perspective of the dispersibility of cellulose in the resin composition, the above-mentioned carboxyl terminal group ratio is preferably 0.20 or more, and from the perspective of the color tone of the obtained resin composition, the above-mentioned carboxyl terminal group ratio is preferably 0.95 or less.
[0146] As a method for adjusting the terminal group concentration of polyamide, a known method can be used. For example, a method of adding a terminal adjusting agent such as a diamine compound, a monoamine compound, a dicarboxylic acid compound, a monocarboxylic acid compound, an acid anhydride, a monoisocyanate, a monoacyl halide, a monoester, a monoalcohol, etc., which reacts with the terminal group, to the polymerization solution in such a manner that a specific terminal group concentration is achieved during the polymerization of polyamide.
[0147] Examples of the terminal adjusting agent that reacts with the terminal amino group include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, tetradecanoic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, methylbenzoic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid; and mixtures of two or more thereof. Among these, from the perspectives of reactivity, stability of the blocked terminal, price, and the like, preferably one or more terminal adjusting agents selected from the group consisting of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, tetradecanoic acid, palmitic acid, stearic acid, and benzoic acid are used, and acetic acid is most preferred.
[0148] Examples of the terminal adjusting agent that reacts with the terminal carboxyl group include aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; aromatic monoamines such as aniline, toluidine, diphenylamine, and naphthylamine, and any mixture thereof. Among these, one or more terminal adjusting agents selected from the group consisting of butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline are preferred in terms of reactivity, boiling point, stability of the blocked terminal, price, and the like.
[0149] From the viewpoint of accuracy and simplicity, the concentrations of these amino terminal groups and carboxyl terminal groups are preferably determined by 1 H-NMR is obtained based on the integral value of the characteristic signal corresponding to each terminal group. As a method for obtaining the concentration of these terminal groups, specifically, the method described in Japanese Patent Publication No. 7-228775 is recommended. When using this method, deuterated trifluoroacetic acid is useful as a measurement solvent. In addition, regarding 1 The number of H-NMR integrations requires at least 300 scans when measuring with a device having sufficient resolution. Alternatively, the concentration of the terminal groups can be measured by a titration-based measurement method described in Japanese Patent Application Publication No. 2003-055549. However, in order to minimize the influence of additives, lubricants, etc., it is more preferable to use 1 Quantification by H-NMR.
[0150] The degree of polymerization of the polyamide is not particularly limited. From the perspective of general injection molding processability, the viscosity value (V) of the polyamide measured in 96 mass % sulfuric acid according to ISO 307 is preferably N ) is preferably 200 or less. The upper limit is more preferably 180, more preferably 150, still more preferably 140, and most preferably 130. By making the viscosity value within the above range, the fluidity during molding of the molded body can be appropriately maintained and the molding strain can be reduced, thereby suppressing the anisotropy of the actual molded product to a low level. The lower limit of the above viscosity value is not particularly limited, but from the perspective of obtaining good impact resistance, it is preferably 50, more preferably 60, still more preferably 65, and most preferably 70.
[0151] The polyamide in the present embodiment may be a mixture of two or more different polyamides. In the case of a mixture of two or more polyamides, various property values of the polyamide may be an average value of the two or more polyamides.
[0152] The polymerization method of polyamide is not particularly limited, and may be any of melt polymerization, interfacial polymerization, solution polymerization, bulk polymerization, solid phase polymerization, and a combination thereof. Among these, melt polymerization is more preferably used from the viewpoint of polymerization controllability.
[0153] In addition, for the purpose of improving the heat resistance stability of polyamide resin, known metal stabilizers such as those described in Japanese Patent Laid-Open No. 1-163262 can be used. Among metal stabilizers, CuI, CuCl2, cupric acetate, cerium stearate, etc. can be cited as particularly preferred examples. In addition, alkali metal halides represented by potassium iodide, potassium bromide, etc. can also be suitably used. These components can also be added in combination. The preferred blending amount of the above-mentioned metal stabilizer and / or alkali metal halide is 0.001 to 5 parts by mass in total relative to 100 parts by mass of polyamide. From the aspect of heat aging resistance, it is preferably above the above lower limit, and from the aspect of maintaining high toughness, it is preferably below the above upper limit.
[0154] In addition to the above components, known additives that can be added to polyamide may be added in an amount of, for example, less than 10 parts by mass based on 100 parts by mass of polyamide.
[0155] In the first to third embodiments, from the perspective of obtaining the advantages of high heat resistance and low linear expansion coefficient based on the polyamide phase, the proportion of polyamide relative to 100% by mass of the resin composition is preferably 30% by mass or more, or 35% by mass or more, or 40% by mass or more, and from the perspective of obtaining the advantages brought about by other components in the resin composition, the proportion is preferably 90% by mass or less, or 80% by mass or less, or 70% by mass or less, or 60% by mass or less.
[0156] <Second polymer>
[0157] In one embodiment, the resin composition contains a second polymer in addition to the polyamide as the first polymer. The second polymer is a polymer different from the first polymer. In one embodiment, the second polymer is at least one polymer selected from the group consisting of a crystalline resin having a melting point of 60° C. or higher and an amorphous resin having a glass transition point of 60° C. or higher.
[0158] As crystalline resins, crystalline polyolefin resins such as polyethylene and polypropylene, crystalline polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polylactic acid, polybutylene succinate, crystalline polyacetal resins such as polyoxymethylene, ethylene-vinyl ester copolymer saponified products, etc. can be cited. Among these, ethylene-vinyl ester copolymer saponified products are preferred from the aspect of achieving high toughness. The crystalline resin can be, for example, the ethylene-vinyl ester copolymer saponified product of the third embodiment.
[0159] The melting point of the crystalline resin is 60° C. or more, preferably 100° C. or more, or 150° C. or more, or 180° C. or more, and preferably 350° C. or less, or 300° C. or less, or 280° C. or less in one embodiment. In the present disclosure, the melting point refers to the peak top temperature of an endothermic peak that appears when the temperature is increased from 23° C. at a temperature increase rate of 10° C. / min using a differential scanning calorimeter (DSC). When two or more endothermic peaks appear, it refers to the peak top temperature of the peak on the lowest temperature side.
[0160] As amorphous resin, amorphous polyolefin resins such as polymethylene pentene and cyclic polyolefin, amorphous polyvinyl resins such as polystyrene and polyvinyl chloride, polycarbonate resins, polyacrylic acid resins, polyarylate resins, polysulfone resins, polyphenylene ether resins, polyphenylene sulfide resins, polyether sulfone resins, polyketone resins, polyphenylene ether ketone resins, polyimide resins, etc. can be cited. Among these, polyphenylene ether resins are preferred from the aspect of achieving low specific gravity and high rigidity. The amorphous resin can be, for example, the polyphenylene ether of the first embodiment.
[0161] The glass transition point of the amorphous resin is 60°C or more, preferably 100°C or more, or 150°C or more, or 180°C or more, preferably 350°C or less, or 300°C or less, or 280°C or less in one embodiment. In the present disclosure, the glass transition point refers to the temperature at the top of the peak with the largest loss modulus when the storage modulus is significantly reduced when the temperature is increased from -100°C at a rate of 2°C / min using a dynamic viscoelasticity measuring device and the temperature is measured at an applied frequency of 10 Hz. When there are two or more peaks of the loss modulus, it refers to the peak top temperature of the peak on the lowest temperature side.
[0162] In one embodiment, from the perspective of obtaining the advantages brought by resins other than polyamide, the amount of the second polymer is preferably 1 part by mass or more, or 5 parts by mass or more, or 10 parts by mass or more relative to 100 parts by mass of polyamide as the first polymer, and from the perspective of obtaining the original advantages of polyamide, in one embodiment, it is 100 parts by mass or less, preferably 80 parts by mass or less, or 60 parts by mass or less, or 40 parts by mass or less.
[0163] <Polyphenylene ether of first embodiment>
[0164] In one mode of the first embodiment, the resin composition includes polyphenylene ether. In the second and third embodiments, the resin composition may further include polyphenylene ether. The polyphenylene ether has a structure represented by the following general formula (1):
[0165] [Chemistry 1]
[0166]
[0167] (In formula (1), R 1 , R 2 , R 3 , and R 4 Each is independently a monovalent group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 7 carbon atoms, a phenyl group, a halogenated alkyl group, an aminoalkyl group, a hydrocarbon group, or a halogenated hydrocarbon group in which a halogen atom and an oxygen atom are separated by at least two carbon atoms, and n is an integer greater than 20.
[0168] In the above formula (1), R 1 , R 2 , R 3 and R 4 Examples of the halogen atom represented by include a fluorine atom, a chlorine atom, a bromine atom and the like, and a chlorine atom and a bromine atom are preferred.
[0169] In the above formula (1), R 1 , R 2 , R 3 and R 4 The "alkyl" represented here means a linear or branched alkyl group having preferably 1 to 6 carbon atoms, more preferably 1 to 3 carbon atoms, and examples thereof include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, etc. Methyl and ethyl are preferred, and methyl is more preferred.
[0170] In the above formula (1), R 1 , R 2 , R 3 and R 4 The alkyl group represented may be substituted with one or more substituents at the substitutable position. Examples of such substituents include halogen atoms (e.g., fluorine atoms, chlorine atoms, bromine atoms), alkyl groups having 1 to 6 carbon atoms (e.g., methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl), aryl groups (e.g., phenyl, naphthyl), alkenyl groups (e.g., vinyl, 1-propenyl, 2-propenyl), alkynyl groups (e.g., ethynyl, 1-propynyl, 2-propynyl), aralkyl groups (e.g., benzyl, phenethyl), and alkoxy groups (e.g., methoxy, ethoxy).
[0171] In the above formula (1), n may be 20 or more, 100 or more, or 200 or more, and may be 2000 or less, 1000 or less, or 400 or less.
[0172] The polyphenylene ether is not particularly limited, and known polyphenylene ethers can be used. For example, poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), etc. can be mentioned, and polyphenylene ether copolymers of 2,6-dimethylphenol and other phenols (for example, 2,3,6-trimethylphenol or 2-methyl-6-butylphenol) can also be used. Among the above, poly(2,6-dimethyl-1,4-phenylene ether) and copolymers of 2,6-dimethylphenol and 2,3,6-trimethylphenol are preferred, and poly(2,6-dimethyl-1,4-phenylene ether) is more preferred.
[0173] These polyphenylene ethers may be used alone or in combination of two or more.
[0174] From the perspective of obtaining a high-rigidity resin composition, the intrinsic viscosity [η] of the polyphenylene ether is preferably 0.1 dl / g or more, or 0.2 dl / g or more, or 0.3 dl / g or more, and from the perspective of imparting good fluidity to the resin composition, the intrinsic viscosity [η] of the polyphenylene ether is preferably 1.0 dl / g or less, or 0.7 dl / g or less, or 0.6 dl / g or less, or 0.5 dl / g or less. The above intrinsic viscosity is a value measured in chloroform at 25°C.
[0175] In one embodiment, the polyphenylene ether is present in the dispersed phase, and at least a portion of the polyphenylene ether may be acid-modified. The acid-modification may be achieved by reacting a modifier (eg, α,β-unsaturated carboxylic acid and its derivatives) with the polyphenylene ether.
[0176] Examples of α,β-unsaturated carboxylic acids include monoacids such as (meth)acrylic acid, crotonic acid, isocrotonic acid, furoic acid, pentenoic acid, vinylacetic acid, and angelic acid; diacids such as maleic acid, chloromaleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, and bridged cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid (nadic acid); and triacids such as citric acid and aconitic acid.
[0177] As the derivative of α,β-unsaturated carboxylic acid, examples include acid halides, amides, imides, anhydrides, esters, etc. of the above-mentioned α,β-unsaturated carboxylic acids. For example, maleic chloride, acrylamide, maleimide, N-phenylmaleimide, N-methylmaleimide, N-ethylmaleimide, maleic anhydride, itaconic anhydride, glutaconic anhydride, citraconic anhydride, nadic anhydride, aconitic anhydride, methyl (meth)acrylate, monomethyl maleate, dimethyl maleate, diethyl itaconate, dibutyl citrate, glycidyl (meth)acrylate, diglycidyl maleate, etc. As examples of preferred modifiers, maleic acid, citric acid, itaconic acid, itaconic anhydride, maleic anhydride, and more preferably citric acid and maleic anhydride.
[0178] From the perspective of dispersing the polyphenylene ether in the polyamide phase with a relatively small dispersion size and obtaining the advantages brought by the combination of polyamide and polyphenylene ether, the acid modification degree of the polyphenylene ether is preferably 0.01% or more, or 0.1% or more, or 0.2% or more, or 0.25% or more. From the perspective of obtaining the advantages of high rigidity and low water absorption brought by the use of polyphenylene ether, the acid modification degree of the polyphenylene ether is preferably 10% or less, or 5% or less, or 2% or less, or 1% or less, or 0.7% or less, or 0.6% or less. The polyphenylene ether disclosed in the present invention can be a mixture of two or more polymers with different acid modification degrees. In this case, the acid modification degree of the entire polyphenylene ether in the resin composition is preferably within the above range. The above acid modification degree is the addition rate calculated by infrared spectroscopy. When the acidic functional group comes from maleic anhydride, a mixture of polyphenylene ether and maleic anhydride is used, and for the 1790cm -1 A calibration curve was prepared in advance, and then the peak of maleic anhydride-modified polyphenylene ether at 1790 cm -1 The addition rate was calculated from the peak intensity.
[0179] As the acid modification method of polyphenylene ether, there can be exemplified a method of reacting a modifier with polyphenylene ether in a flowing state (e.g., by melting, or dispersing or dissolving in a solvent), a method of reacting a modifier with a powdered polyphenylene ether at a temperature below the glass transition point of the polyphenylene ether in the presence of a modifier, etc. As an example of a method of reacting a modifier with polyphenylene ether in a flowing state, there can be exemplified a method of melt-kneading polyphenylene ether and a modifier at 250° C. to 350° C. for 5 seconds to 30 minutes using a roll mill, a Banbury mixer, an extruder, etc., a method of dissolving polyphenylene ether in an organic solvent (e.g., toluene, xylene, decalin, tetralin, etc.), and then adding a modifier and heating. In addition, as an example of a method for reacting a modifier with a powdered polyphenylene ether, there can be cited a method in which a specific amount of polyphenylene ether and a modifier are added to a stirring device capable of high-speed stirring, and the temperature of the contents is maintained at 160°C to 200°C for at least 30 seconds by shear heat generation under high-speed stirring and / or heat transfer from a jacket.
[0180] The reaction can be carried out in the presence of a free radical initiator. As free radical initiators, organic peroxides (benzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, tert-butyl cumyl peroxide, cumene hydroperoxide, 2,5-dimethyl-2,5-di(tert-butyl peroxide)hexane, 2,5-dimethyl-2,5-di(tert-butyl peroxide)hexyne-3, etc.) and azo compounds (azobisisobutylnitrile, dimethylazoisobutyrate, etc.) can be cited. The amount of the free radical initiator used can be, for example, 0.01 to 10 parts by mass relative to 100 parts by mass of the polyphenylene ether.
[0181] In one embodiment, polyphenylene ether can be a mixture of polyphenylene ether with acidic functional groups and polyphenylene ether without acidic functional groups. About the mixing ratio of polyphenylene ether with acidic functional groups and polyphenylene ether without acidic functional groups, when the total of the two is 100% by mass, from the aspect of the advantages of high rigidity and low water absorption of resin composition obtained well and the aspect of improving the affinity with cellulose nanofiber, polyphenylene ether with acidic functional groups is preferably 10% by mass or more, more preferably 20% by mass or more, and more preferably 30% by mass or more, most preferably 40% by mass or more. The upper limit is not particularly limited, and substantially all polyphenylene ethers are polyphenylene ethers with acidic functional groups, but from the aspect that the fluidity during melting does not cause problems, it is preferably 80% by mass or less.
[0182] The phase containing polyphenylene ether can form a granular dispersed phase (dispersed particles) in the resin composition. In this case, the dispersed particle size is preferably 3 μm or less, more preferably 2 μm or less, and most preferably 1 μm or less in terms of number average particle size. The lower limit is not particularly limited, for example, 0.01 μm. From the perspective of high toughness and physical property stability, it is preferably within the above range.
[0183] The phase containing polyphenylene ether preferably has a high uniformity of dispersed particle size. From this aspect, the volume ratio of dispersed particles with a particle size of more than 1 μm to the dispersed particles of polyphenylene ether as a whole is preferably less than 30% by volume. The upper limit is more preferably 25% by volume, further preferably 20% by volume, and even more preferably 15% by volume, and most preferably 10% by volume. In the volume-based dispersed particle size distribution, if there are coarse particles (even if they are very few), the volume ratio of dispersed particles with a particle size of more than 1 μm rapidly increases. When the above-mentioned volume ratio is within the above-mentioned range, the uniformity of the dispersed particle size is high, which is preferred. From the aspect of the ease of manufacture of the resin composition, the above-mentioned volume ratio can, for example, be more than 2% by volume or more than 5% by volume.
[0184] As methods for improving the uniformity of the dispersed particle size of the phase containing polyphenylene ether, the following methods can be cited: a method of preparing a resin composition by extrusion kneading the compounding components of the resin composition, and increasing the screw speed during extrusion kneading to impart high shear strain to the compounding components, thereby finely dispersing the polyphenylene ether; a method of providing a screw component such as a seal ring with uniformly small gaps to impart extensional flow strain to the compounding components; a method of passing a molten polymer through a special narrow slit to impart extensional flow strain using the slit portion; and the like. Any of these methods can be used, but when using the method of imparting high shear, the polymer temperature increases significantly during processing, so it is more preferable to use the method of extending the flow strain.
[0185] As a method for observing the dispersed morphology, the following methods can be cited: a method of cutting a resin composition in the form of a molded body, pellets, etc. into ultrathin slices, staining the polyamide phase with phosphotungstic acid, etc., and observing with a transmission electron microscope; a method of uniformly surface-treating the surface of a resin composition in the form of a molded body, pellets, etc., immersing the surface in a solvent that selectively dissolves only polyphenylene ether, extracting the polyphenylene ether, and observing with a scanning electron microscope; etc. The obtained image is binarized using an image analyzer, and the diameter of the dispersed particles (at least 500 randomly selected) of the dispersed phase is calculated in the form of an equivalent circle diameter, and the respective particle sizes are counted, thereby calculating the number average particle size of the dispersed particles and the volume ratio of particles with a specific particle size (for example, the above-mentioned particle size of 1 μm or more).
[0186] In the first embodiment, from the perspective of obtaining the advantages of high rigidity, low specific gravity and low water absorption based on the polyphenylene ether phase, the ratio of the polyphenylene ether to 100% by mass of the resin composition is preferably 10% by mass or more, or 20% by mass or more, or 30% by mass or more, and from the perspective of obtaining the advantages based on other components in the resin composition, the ratio is preferably 60% by mass or less, or 50% by mass or less, or 40% by mass or less.
[0187] In addition, from the perspective of obtaining the above-mentioned advantages brought about by the polyphenylene ether phase, the amount of polyphenylene ether relative to 100 parts by mass of polyamide is preferably 30 parts by mass or more, or 40 parts by mass or more, or 50 parts by mass or more, and from the perspective of easily making the polyphenylene ether phase exist in the form of a dispersed phase in the polyamide phase, the amount is preferably 150 parts by mass or less, or 120 parts by mass or less, or 100 parts by mass or less.
[0188] <Elastic Body of First Embodiment>
[0189] In the first embodiment, the resin composition may have an elastomeric phase in addition to the first and second polymers; in one embodiment, the resin composition may have an elastomeric phase in addition to the polyamide phase and the polyphenylene ether phase. The elastomer constituting the elastomeric phase is a substance that is elastic at room temperature (23° C.) (specifically, a natural or synthetic polymer substance). In the case where the elastomeric phase is further present, the toughness and elongation (particularly the elongation in a low temperature environment) of the resin composition are good, which is preferred.
[0190] In one embodiment of the first embodiment, the resin composition has a polyamide phase (continuous phase) and a polyphenylene ether phase (dispersed phase). When an elastomer is further used, the elastomer originally has a higher affinity for polyphenylene ether than for polyamide, so the elastomer phase can be distributed in a manner that the elastomer phase is present in the polyphenylene ether phase (i.e., the polyphenylene ether phase is the continuous phase and the elastomer phase is the dispersed phase). That is, in a resin composition further comprising an elastomer, the polyphenylene ether phase is dispersed in the polyamide phase with a smaller size, and the elastomer phase is further dispersed in the polyphenylene ether phase. In order to obtain such a dispersed form, for example, a method using polyamide, a polyphenylene ether having an acidic functional group, and an elastomer without an acidic functional group can be cited.
[0191] In addition, the elastomer phase can be dispersed in the polyamide phase and the first polymer phase or the polyphenylene ether phase can be further distributed in the elastomer phase. In order to obtain such a dispersed form, for example, a method of using a polyamide, a polyphenylene ether without an acidic functional group, and an elastomer with an acidic functional group can be cited.
[0192] In addition, the phase of the second polymer or the polyphenylene ether phase and the elastomer phase can also be separately distributed in the polyamide phase. In order to obtain such a dispersed form, for example, the mode of using polyamide, the second polymer with acidic functional groups or the polyphenylene ether with acidic functional groups and the elastomer with acidic functional groups can be enumerated.
[0193] It should be noted that, in the case where an elastomer phase is further present, the preferred example of the dispersed size of the polyphenylene ether phase may also be the same as above. In addition, the elastomer phase may be present in the polyphenylene ether phase in the form of dispersed particles, or may be present in the polyamide phase in the form of dispersed particles. The preferred dispersed particle size in this case is preferably 3 μm or less, more preferably 2 μm or less, and most preferably 1 μm or less in terms of number average particle size. The lower limit is not particularly limited, for example, 0.01 μm. From the perspective of exerting good toughness and elongation, it is preferably within the above range.
[0194] In the elastomer, it is preferred that the uniformity of the dispersed particle size is high. From this aspect, the volume ratio of the dispersed particles with a particle size of 3 μm or more to the dispersed particles of the elastomer is preferably less than 30% by volume. The upper limit is more preferably 25% by volume, further preferably 20% by volume, and even more preferably 15% by volume, and most preferably 10% by volume. From the aspect of the ease of manufacture of the resin composition, the above-mentioned volume ratio can be, for example, more than 2% by volume or more than 5% by volume. As a method for improving the uniformity of the dispersed particle size of the elastomer, a resin composition can be manufactured by extruding and kneading the compounding components of the resin composition, and a method for microdispersing the elastomer by increasing the screw speed during extrusion and kneading to impart high shear strain to the compounding components can be cited.
[0195] As the specific example of elastomer, natural rubber, conjugated diene compound polymer, aromatic compound-conjugated diene copolymer, hydride of aromatic compound-conjugated diene copolymer, polyolefin, polyester elastomer, polyurethane elastomer, polyamide elastomer, elastomer with core-shell structure etc. can be enumerated.In one mode, elastomer is a polymer different from polyamide (i.e. not a polyamide elastomer).Among these, from the aspect of the ease of modification reaction of the acidic functional group described later, preferably aromatic compound-conjugated diene copolymer and its hydride, polyolefin and elastomer with core-shell structure.As above-mentioned aromatic compound-conjugated diene copolymer and its hydride, more preferably aromatic compound-conjugated diene block copolymer and its hydride, as above-mentioned polyolefin, more preferably copolymer of ethylene and alpha-olefin.
[0196] In one embodiment, the elastomer is one or more selected from the group consisting of ethylene-α-olefin copolymers, block copolymers of aromatic vinyl compounds and conjugated diene compounds, and hydrogenated products of block copolymers of aromatic vinyl compounds and conjugated diene compounds.
[0197] In the present disclosure, the aromatic compound-conjugated diene block copolymer is a block copolymer composed of a polymer block (A) mainly composed of an aromatic vinyl compound and a polymer block (B) mainly composed of a conjugated diene compound. From the perspective of exhibiting impact strength, the block copolymer preferably has a bonding form of any one of AB type, ABA type, and ABAB type, and more preferably ABA type or ABAB type.
[0198] In addition, the mass ratio of the aromatic vinyl compound unit to the conjugated diene compound unit in the block copolymer is preferably 10 / 90 to 70 / 30. More preferably 15 / 85 to 55 / 45, most preferably 20 / 80 to 45 / 55. Furthermore, they can also be two or more copolymers with different mass ratios of aromatic vinyl compounds and conjugated diene compounds blended. As specific examples of aromatic vinyl compounds, styrene, α-methylstyrene, vinyltoluene, etc. can be cited, and one or more compounds selected from them can be used, wherein styrene is particularly preferred.
[0199] Specific examples of conjugated diene compounds include butadiene, isoprene, piperylene, 1,3-pentadiene, etc., and one or more compounds selected from these can be used, among which butadiene, isoprene and a combination thereof are preferred, and butadiene is particularly preferred. When butadiene is used as the conjugated diene compound of the block copolymer, the microstructure of the polybutadiene block portion is preferably 5 to 80% in terms of 1,2-vinyl content or the total amount of 1,2-vinyl content and 3,4-vinyl content on a molar basis from the perspective of suppressing crystallization of the soft segment. 5 to 80%, more preferably 10 to 50%, and most preferably 15 to 40%.
[0200] The so-called aromatic compound-conjugated diene block copolymer is a block copolymer composed of a polymer block mainly composed of an aromatic vinyl compound and a polymer block mainly composed of a conjugated diene compound, and refers to a block copolymer that has not been substantially subjected to a hydrogenation treatment. The hydrogenated product of the block copolymer of an aromatic vinyl compound and a conjugated diene compound refers to a substance in which the aliphatic double bonds of the polymer block mainly composed of a diene compound are controlled within a range of greater than 0% to 100% by hydrogenating the block copolymer of the aromatic vinyl compound and the conjugated diene compound. From the perspective of suppressing thermal degradation during processing, the hydrogenation rate of the hydrogenated product of the block copolymer is preferably 50% or more, more preferably 80% or more, and most preferably 98% or more. From the perspective of low-temperature toughness, it is preferably 50% or less, more preferably 20% or less, and most preferably 0% (i.e., a block copolymer of an aromatic vinyl compound and a conjugated diene compound).
[0201] In addition, as the molecular weight of the block copolymer of the aromatic vinyl compound and the conjugated diene compound and its hydrogenated product, the number average molecular weight (Mn) is preferably 10,000 to 500,000, and most preferably 40,000 to 250,000 from the perspective of both impact strength and fluidity. In the present disclosure, unless otherwise specified, the number average molecular weight refers to the value measured by a gel permeation chromatography apparatus using chloroform as a solvent at a measurement temperature of 40° C. and converted to a polystyrene standard sample.
[0202] These block copolymers of aromatic vinyl compounds and conjugated diene compounds may be used by mixing two or more substances having different bonding forms, substances having different molecular weights, substances having different kinds of aromatic vinyl compounds, substances having different kinds of conjugated diene compounds, substances having different 1,2-vinyl contents or the total amount of 1,2-vinyl contents and 3,4-vinyl contents, substances having different contents of aromatic vinyl compound components, substances having different hydrogenation rates, etc. In a mixture of substances having different hydrogenation rates, the preferred hydrogenation rate of the mixture is as described above.
[0203] In addition, as the polyolefin, an ethylene-α-olefin copolymer can be preferably used from the viewpoint of exhibiting impact resistance. Examples of the monomer copolymerizable with the ethylene unit include propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, aliphatic substituted vinyl monomers such as isobutylene, aromatic vinyl monomers such as styrene and substituted styrene, ester vinyl monomers such as vinyl acetate, acrylic acid ester, methacrylic acid ester, glycidyl acrylate, glycidyl methacrylate, hydroxyethyl methacrylate, acrylamide, allylamine, vinyl para-aminobenzene, nitrogen-containing vinyl monomers such as acrylonitrile, and dienes such as butadiene, cyclopentadiene, 1,4-hexadiene, and isoprene.
[0204] Preferably, it is a copolymer of ethylene and one or more α-olefins having 3 to 20 carbon atoms, more preferably a copolymer of ethylene and one or more α-olefins having 3 to 16 carbon atoms, and most preferably a copolymer of ethylene and one or more α-olefins having 3 to 12 carbon atoms. In addition, as for the molecular weight of the ethylene-α-olefin copolymer, from the aspect of exhibiting impact resistance, the number average molecular weight (Mn) measured by a gel permeation chromatography measuring apparatus using 1,2,4-trichlorobenzene as a solvent at 140°C using a polystyrene standard sample is preferably 10,000 or more, more preferably 10,000 to 100,000, and further preferably 20,000 to 60,000. In addition, from the aspect of achieving both fluidity and impact resistance, the molecular weight distribution (weight average molecular weight / number average molecular weight: Mw / Mn) is preferably 3 or less, and further preferably 1.8 to 2.7.
[0205] In addition, from the viewpoint of handling properties during processing, the content of ethylene units in the ethylene-α-olefin copolymer is preferably 30 to 95% by mass based on the total amount of the ethylene-α-olefin copolymer.
[0206] These preferred ethylene-α-olefin copolymers can be produced by the production methods described in, for example, Japanese Patent Publication No. 4-12283, Japanese Patent Application Laid-Open No. 60-35006, Japanese Patent Application Laid-Open No. 60-35007, Japanese Patent Application Laid-Open No. 60-35008, Japanese Patent Application Laid-Open No. 5-155930, Japanese Patent Application Laid-Open No. 3-163088, U.S. Patent No. 5,272,236, and the like.
[0207] In the present disclosure, as the elastomer with core-shell structure, there can be enumerated the core-shell type elastomer with the shell as the graft layer of granular rubber and the glassy formed outside the core. About the rubber component as the core, butadiene rubber, acrylic rubber, silicone-acrylic composite rubber etc. can be used suitably. In addition, as the shell, it is suitable for the glassy macromolecules such as styrene resin, acrylonitrile-styrene copolymer, acrylic resin. Among these, from the aspect of compatibility with polyamide, the elastomer with core-shell structure having the core of butadiene rubber and the shell of acrylic resin can be used suitably.
[0208] In one embodiment, at least a portion of the elastomer has an acidic functional group. In the present disclosure, the so-called elastomer having an acidic functional group means that the acidic functional group is added to the molecular skeleton of the elastomer by chemical bonds. In addition, in the present disclosure, the so-called acidic functional group refers to a functional group that can react with a basic functional group, etc., and specific examples thereof include a hydroxyl group, a carboxyl group, a carboxylate group, a sulfonic group, an anhydride group, etc.
[0209] From the aspect of compatibility with the second polymer having an acidic functional group or the polyphenylene ether having an acidic functional group, the amount of the acidic functional group added to the elastomer is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and further preferably 0.2% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less, based on 100% by mass of the elastomer. It should be noted that the number of acidic functional groups is a value obtained by measuring a calibration curve sample pre-mixed with an acidic substance using an infrared absorption spectrometer and measuring the sample based on a calibration curve prepared using the characteristic absorption band of the acid.
[0210] Examples of elastomers having an acidic functional group include an elastomer having a core-shell structure having a layer formed using acrylic acid or the like as a copolymer component as a shell; an elastomer that is a modified product obtained by grafting α,β-unsaturated dicarboxylic acid or a derivative thereof onto an ethylene-α-olefin copolymer, a polyolefin, an aromatic compound-conjugated diene copolymer, or an aromatic compound-conjugated diene copolymer hydrogenated product containing acrylic acid or the like as a monomer in the presence or absence of a peroxide; and the like.
[0211] In a preferred embodiment, the elastomer is an anhydride-modified elastomer.
[0212] Among these, more preferred are modified products obtained by grafting α,β-unsaturated dicarboxylic acids or derivatives thereof onto polyolefins, aromatic compound-conjugated diene copolymers or aromatic compound-conjugated diene copolymer hydrogenates in the presence or absence of peroxides, and particularly preferred are modified products obtained by grafting α,β-unsaturated dicarboxylic acids and derivatives thereof onto ethylene-α-olefin copolymers or aromatic compound-conjugated diene block copolymer hydrogenates in the presence or absence of peroxides.
[0213] Specific examples of the α,β-unsaturated dicarboxylic acid and its derivatives include maleic acid, fumaric acid, maleic anhydride and fumaric anhydride. Among these, maleic anhydride is particularly preferred.
[0214] In one embodiment, the elastomer can be a mixture of an elastomer with an acidic functional group and an elastomer without an acidic functional group. Regarding the mixing ratio of an elastomer with an acidic functional group and an elastomer without an acidic functional group, when the total of the two is 100% by mass, from the aspect of maintaining the high toughness and physical stability of the resin composition well, the elastomer with an acidic functional group is preferably more than 10% by mass, more preferably more than 20% by mass, and more preferably more than 30% by mass, and most preferably more than 40% by mass. The upper limit is not particularly limited, and substantially all elastomers are elastomers with acidic functional groups, but from the aspect that fluidity does not cause problems, it is preferably less than 80% by mass.
[0215] In the first embodiment, when an elastomer phase is further present, the ratio of the elastomer to 100% by mass of the resin composition is preferably 3% by mass or more, or 5% by mass or more, or 8% by mass or more from the perspective of improving the toughness and elongation of the resin composition, and is preferably 40% by mass or less, or 30% by mass or less, or 10% by mass or less from the perspective of improving the rigidity of the resin composition while reducing the thermal expansion coefficient.
[0216] When the above-mentioned elastomer phase is further present, the amount of the elastomer is preferably 1 part by mass or more, or 2 parts by mass or more, or 3 parts by mass or more, or 4 parts by mass or more, or 5 parts by mass or more relative to 100 parts by mass of the total of the polyamide and the second polymer or the polyphenylene ether, from the aspect of well improving the toughness and elongation of the resin composition, and the amount of the elastomer is preferably 50 parts by mass or less, or 40 parts by mass or less, or 35 parts by mass or less, or 30 parts by mass or less, or 25 parts by mass or less, from the aspect of improving the rigidity of the resin composition and reducing the thermal expansion coefficient.
[0217] In the case where the above-mentioned elastomer phase is further present, the amount of the elastomer is preferably 10 parts by mass or more, or 15 parts by mass or more, or 20 parts by mass or more relative to 100 parts by mass of the second polymer or polyphenylene ether from the perspective of improving the toughness and elongation of the resin composition. From the perspective that the elastomer phase is easily present as a dispersed phase in the second polymer phase or the polyphenylene ether phase, the amount of the elastomer is preferably 100 parts by mass or less, or 80 parts by mass or less, or 70 parts by mass or less, or 50 parts by mass or less, or 40 parts by mass or less.
[0218] <Elastic Body of Second Embodiment>
[0219] In the second embodiment, the resin composition contains an elastomer (i.e., a substance that is an elastic material at room temperature (23° C.) (specifically, a natural or synthetic polymer substance)) that is an aromatic compound-conjugated diene compound block copolymer (i.e., a block copolymer composed of a polymer block (A) mainly composed of an aromatic vinyl compound and a polymer block (B) mainly composed of a conjugated diene compound) and / or its derivatives. From the perspective of exhibiting impact strength, it is preferred that the bonding form of each block is a block copolymer of any one of AB type, ABA type, and ABAB type, and more preferably ABA type or ABAB type. In addition, the derivative of the aromatic compound-conjugated diene compound block copolymer refers to a polymer that has a structural difference by modification, hydrogenation, etc. while maintaining the main structure of the block copolymer, and in one embodiment is a modified product (e.g., an acid-modified product, etc.) and / or a hydrogenated product of the aromatic compound-conjugated diene compound block copolymer.
[0220] The structure of the block copolymer, and the structures of the aromatic vinyl compound unit and the conjugated diene compound unit in the block copolymer and preferred examples of their mass ratio may be the same as those described above for the block copolymer in the first embodiment.
[0221] In the resin composition of the second embodiment, it is also unexpectedly found that the elastomer as an aromatic vinyl compound-conjugated diene compound block copolymer and / or its derivative can give high toughness to the resin composition and give low thermal expansion coefficient at the same time. Although it is not desired to be bound by theory, it can be considered that in the aromatic vinyl compound-conjugated diene compound block copolymer and its derivative, molecules can be cross-linked by double bonds in the molecule, so the molecular mobility is reduced. In the resin composition comprising a combination of polyamide and elastomer, the elastomer forms a micro-region to help improve toughness, and on the other hand, it is more prone to thermal expansion than polyamide, so it becomes a reason for the increase of the thermal expansion of the resin composition. However, according to the elastomer of the second embodiment, the thermal expansion of the resin composition can be suppressed to be relatively low due to the crosslinking of the elastomer molecules as described above. In this way, the resin composition comprising an elastomer of the second embodiment can also unexpectedly highly take into account the opposite characteristics such as high toughness and low thermal expansion.
[0222] In addition, when the elastomer contains an acid-modified substance, the formation of crosslinks between the molecules described above also helps to inhibit the reaction between cellulose and the acidic functional group. In this case, the advantage of not easily causing an increase in the thermal expansion coefficient of the resin composition due to the elastomer adhering to the cellulose (i.e., not easily causing the cellulose to be mainly present in the polyamide phase to reduce the effect of reducing the thermal expansion coefficient) can also be obtained.
[0223] The number average molecular weight (Mn) of each of the aromatic vinyl compound-conjugated diene compound block copolymer and its derivative is preferably 10,000 to 500,000, more preferably 40,000 to 250,000, from the viewpoint of achieving both impact strength and fluidity.
[0224] In one embodiment, the derivative of the aromatic vinyl compound-conjugated diene compound block copolymer includes an acid-modified product of the block copolymer. In one embodiment, the acidic functional group of the present disclosure is added to the molecular skeleton of the block copolymer via a chemical bond.
[0225] As the acid-modified product, there can be mentioned a modified product obtained by grafting an α,β-unsaturated dicarboxylic acid or a derivative thereof on an aromatic vinyl compound-conjugated diene compound block copolymer or a hydrogenated product thereof in the presence or absence of a peroxide. In a preferred embodiment, the acid-modified product is an anhydride-modified product. As specific examples of α,β-unsaturated dicarboxylic acids and their derivatives, there can be mentioned maleic acid, fumaric acid, maleic anhydride and fumaric anhydride, among which maleic anhydride is particularly preferred.
[0226] Elastomer can be the mixture of the polymer with acidic functional group and the polymer without acidic functional group, or can be made up of the polymer with acidic functional group.When the total of the polymer (acid-modified substance) with acidic functional group and the polymer (non-acid-modified substance) without acidic functional group is 100 mass %, from the aspect of the toughness improvement effect brought by the elastomer of the second embodiment obtained well, the ratio of acid-modified substance is preferably more than 10 mass %, more preferably more than 20 mass %, and then more preferably more than 30 mass %, most preferably more than 40 mass %.The upper limit of the ratio of acid-modified substance is not particularly limited, and the elastomer of the second embodiment can be substantially only made up of acid-modified substance, but from the aspect that the flowability of resin combination does not produce problems, it is preferably below 80 mass %.
[0227] From the perspective of compatibility with polyamide, the amount of acidic functional groups in the acid-modified product is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and further preferably 0.2% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less. It should be noted that the number of acidic functional groups is a value obtained by measuring a calibration curve sample pre-mixed with an acidic substance using an infrared absorption spectrometer and measuring the sample based on a calibration curve prepared using the characteristic absorption band of the acid.
[0228] In one embodiment, the amount of the acidic functional groups in the acid-modified product is preferably within the above-exemplified range based on 100% by mass of the total amount of the elastomer of the second embodiment.
[0229] In the resin composition, the amount of the elastomer relative to 100 parts by mass of polyamide is preferably in the range of 1 to 50 parts by mass. The upper limit is more preferably 40 parts by mass, more preferably 35 parts by mass, further more preferably 30 parts by mass, and most preferably 25 parts by mass. In order to maintain the rigidity and heat resistance of the resin composition well, it is preferably below the above upper limit. In addition, the lower limit is more preferably 2 parts by mass, further preferably 3 parts by mass, further more preferably 4 parts by mass, and most preferably 5 parts by mass. In order to improve the toughness and physical property stability of the resin composition, it is preferably above the above lower limit.
[0230] From the viewpoint of high toughness and physical property stability, the dispersed particle size of the elastomer phase when it forms a particulate dispersed phase (dispersed particles) in the resin composition is preferably in the same range as that of the elastomer phase in the first embodiment.
[0231] The uniformity of the dispersed particle size of the elastomer is preferably high. From this aspect, the volume ratio of the dispersed particles with a particle size of 1 μm or more to the dispersed particles of the elastomer as a whole is preferably 30% by volume or less. The upper limit is more preferably 25% by volume, further preferably 20% by volume, and even more preferably 15% by volume, and most preferably 10% by volume. In the volume-based dispersed particle size distribution, if there are coarse particles (even if they are very few), the volume ratio of the dispersed particles with a particle size of 1 μm or more rapidly increases. When the above-mentioned volume ratio is within the above-mentioned range, the uniformity of the dispersed particle size is high, which is preferred. From the aspect of the ease of manufacture of the resin composition, the above-mentioned volume ratio can be, for example, more than 2% by volume or more than 5% by volume.
[0232] As a method for improving the uniformity of the dispersed particle size of the elastomer, there is mentioned a method of preparing the resin composition by extrusion kneading the ingredients of the resin composition, and increasing the screw speed during extrusion kneading to apply high shear strain to the ingredients, thereby finely dispersing the elastomer.
[0233] As a method for observing the dispersed morphology, the following methods can be cited: a method of cutting a resin composition in the form of a molded body, pellets, etc. into ultrathin slices, staining the polyamide phase with phosphotungstic acid, etc., and observing with a transmission electron microscope; a method of uniformly surface-treating the surface of the resin composition in the form of a molded body, pellets, etc., immersing the surface in a solvent that selectively dissolves only the elastomer, extracting the elastomer, and observing with a scanning electron microscope; etc. The obtained image is binarized using an image analyzer, and the diameter of the dispersed particles (at least 500 randomly selected) of the dispersed phase is calculated in the form of an equivalent circle diameter, and the respective particle sizes are counted, thereby calculating the number average particle size of the dispersed particles and the volume ratio of particles with a specific particle size (for example, the above-mentioned particle size of 1 μm or more).
[0234] In the second embodiment, the resin composition may further contain an elastomer component other than the aromatic vinyl compound-conjugated diene compound block copolymer and / or its derivative within a range that does not impair the advantages of the present invention.
[0235] <Third Embodiment of Ethylene-Vinyl Ester Copolymer Saponification Product>
[0236] In the third embodiment, the resin composition includes ethylene-vinyl ester copolymer saponification. In addition, in the first and second embodiments, the resin composition may further include ethylene-vinyl ester copolymer saponification. Ethylene-vinyl ester copolymer saponification can give high fracture strain (i.e. excellent toughness) to the resin composition including polyamide and cellulose due to its excellent strength and dimensional stability and the contribution of hydroxyl and excellent affinity with polyamide and cellulose. In addition, ethylene-vinyl ester copolymer saponification is not detrimental to the advantages brought by cellulose (i.e., the advantages of excellent reduction effect of linear thermal expansion coefficient and physical anisotropy of resin composition while being low specific gravity), and it is also advantageous from this aspect. Therefore, the resin composition of the third embodiment can have the specific advantages of highly taking into account the opposite characteristics such as high toughness and low thermal expansion.
[0237] The ethylene-vinyl ester copolymer saponified product is a compound obtained by adding an alkaline salt to a copolymer obtained by copolymerizing ethylene and vinyl ester and saponifying the copolymer, and comprises ethylene units and vinyl alcohol units. The ethylene-vinyl ester copolymer saponified product may contain a vinyl ester unit as an unsaponified portion, but in a typical embodiment, does not substantially contain a vinyl ester unit.
[0238] From the perspective of obtaining a good effect of improving the fracture strain of the resin composition, the proportion of the vinyl alcohol unit (specifically, the structural unit produced by saponification of the vinyl ester unit) in 100 mol% of all the monomer units constituting the saponified ethylene-vinyl ester copolymer is preferably 60 mol% or more, or 65 mol% or more, or 70 mol% or more, or 74 mol% or more, or 76 mol% or more, and from the perspective of containing an appropriate amount of ethylene units in the saponified ethylene-vinyl ester copolymer, it is preferably 95 mol% or less, or 90 mol% or less, or 80 mol% or less.
[0239] In 100 mol% of all monomer units constituting the saponified ethylene-vinyl ester copolymer, the proportion of ethylene units is preferably 5 mol% or more, or 10 mol% or more, or 20 mol% or more from the viewpoint of processability and water absorption during production of the resin composition, and is preferably 40 mol% or less, or 35 mol% or less, or 30 mol% or less, or 26 mol% or less, or 24 mol% or less from the viewpoint of obtaining a good effect of improving the breaking strain of the resin composition.
[0240] From the perspective of obtaining the advantages brought by the saponified ethylene-vinyl ester copolymer, the proportion of the vinyl ester unit (specifically, the unit that is not saponified during the saponification after copolymerization of ethylene and vinyl ester) in 100 mol% of all monomer units in the saponified ethylene-vinyl ester copolymer is preferably 20 mol% or less, or 10 mol% or less, or 5 mol% or less, or 1 mol% or less. This proportion is ideally 0 mol%, but from the perspective of ease of production of the saponified ethylene-vinyl ester copolymer, it can be, for example, 0.01 mol% or more, or 0.1 mol% or more, or 0.5 mol% or more.
[0241] From the aspect of making the fracture strain of the resin composition good, the saponification degree of the ethylene-vinyl ester copolymer saponified product is preferably 90 mol% or more, or 95 mol% or more, or 99 mol% or more. From the aspect of the ease of manufacturing the ethylene-vinyl ester copolymer saponified product, the saponification degree can be, for example, 99.99 mol% or less, or 99.9 mol% or less, or 99.5 mol% or less. The saponification degree is obtained as a value obtained by dividing the number of vinyl alcohol units in the ethylene-vinyl ester copolymer saponified product by the total number of vinyl alcohol units and vinyl ester units.
[0242] The amount of each structural unit in the saponified ethylene-vinyl ester copolymer can be confirmed by a nuclear magnetic resonance (NMR) method.
[0243] The ethylene-vinyl ester copolymer saponification product may contain additional structural units in addition to the ethylene unit, the vinyl alcohol unit and the vinyl ester unit, within the range not impairing the effect of the present invention. As the additional structural units, olefins such as propylene, 1-butene, and isobutylene can be cited; α-olefins containing hydroxyl groups such as 2-propylene-1-ol, 3-butene-1-ol, 4-pentene-1-ol, 5-hexene-1-ol, 3,4-dihydroxy-1-butene, and 5-hexene-1,2-diol; acylated products or esterified products thereof; and the like. As the esterified products, 3,4-diacyloxy-1-butene, particularly 3,4-diacetoxy-1-butene can be cited. Other examples include hydroxyalkyl vinyls such as 2-methylenepropane-1,3-diol and 3-methylenepentane-1,5-diol; hydroxyalkyl vinylene diacetates such as 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, and 1,3-dibutyryloxy-2-methylenepropane; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, phthalic acid (anhydride), maleic acid (anhydride), and itaconic acid (anhydride) or their salts, and monoalkyl esters or dialkyl esters having 1 to 18 carbon atoms; acrylamides such as acrylamide, N-alkyl acrylamide having 1 to 18 carbon atoms, N,N-dimethyl acrylamide, 2-acrylamidopropanesulfonic acid or its salts, acrylamidopropyl dimethylamine or its acid salt or its quaternary salt; methacrylamide, N-alkyl acrylamide having 1 to 18 carbon atoms, methacrylamides such as methyl methacrylamide, N,N-dimethyl methacrylamide, 2-methacrylamide propane sulfonic acid or its salts; methacrylamide propyl dimethylamine, its acid salt or its quaternary salt; N-vinyl amides such as N-vinyl pyrrolidone, N-vinyl formamide, N-vinylacetamide; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl ethers such as alkyl vinyl ethers having 1 to 18 carbon atoms, hydroxyalkyl vinyl ethers, alkoxyalkyl vinyl ethers; halogenated vinyls such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride, vinyl bromide; vinyl silanes such as trimethoxyvinylsilane; allyl acetate, allyl chloride, trimethyl-(3-acrylamide-3-dimethylpropyl)-ammonium chloride, acrylamide-2-methylpropane sulfonic acid, vinyl ethylene carbonate, glycerol monoallyl ether, etc. The molar ratio of the additional structural unit in 100 mol% of all monomer units constituting the saponified ethylene-vinyl ester copolymer is preferably 20 mol% or less, or 15 mol% or less, or 10 mol% or less. The molar ratio may be, for example, 1 mol% or more, 3 mol% or more, or 5 mol% or more.
[0244] The method for producing the saponified ethylene-vinyl ester copolymer is not limited. The ethylene monomer and the vinyl ester monomer may be radically polymerized by a known polymerization method (eg, solution polymerization) and then saponified by a known saponification method.
[0245] Examples of the vinyl ester monomer include aliphatic vinyl esters and aromatic vinyl esters. Specific preferred examples of the vinyl ester include vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl versatate, vinyl benzoate, and the like.
[0246] For saponification, for example, at least one alkaline salt selected from the group consisting of sodium hydroxide and potassium hydroxide can be used.
[0247] The ethylene-vinyl ester copolymer saponification product may be a commercially available product. Examples of commercially available products include Soarnol V2504 (ethylene ratio 25 mol%), Soarnol DT2904 (ethylene ratio 29 mol%), Soarnol DC3212 (ethylene ratio 32 mol%) (all available from Mitsubishi Chemical Holdings Co., Ltd.), Eval M100B (ethylene ratio 24 mol%), Eval L104B (ethylene ratio 27 mol%), and Eval C109B (ethylene ratio = 35 mol%) (all available from KURARAY Co., Ltd.).
[0248] In the resin composition, the amount of the saponified ethylene-vinyl ester copolymer relative to 100 parts by mass of the polyamide is preferably 1 part by mass or more, or 5 parts by mass or more, or 10 parts by mass or more, or 20 parts by mass or more, or 30 parts by mass or more, from the perspective of obtaining a good effect of improving the breaking strain, and is preferably 100 parts by mass or less, or 80 parts by mass or less, or 60 parts by mass or less, or 50 parts by mass or less, or 40 parts by mass or less, from the perspective of toughness.
[0249] The phase morphology of the resin composition can have the following morphologies: a morphology in which polyamide forms a continuous phase and an ethylene-vinyl ester copolymer saponify forms a dispersed phase; a morphology in which polyamide forms a dispersed phase and an ethylene-vinyl ester copolymer saponify forms a continuous phase; and a morphology in which both polyamide and an ethylene-vinyl ester copolymer saponify form a continuous phase (i.e., a co-continuous phase structure). From the perspective of exhibiting good heat resistance and achieving high toughness as a composition, a morphology in which polyamide forms a continuous phase and an ethylene-vinyl ester copolymer saponify forms a dispersed phase is preferred.
[0250] In the resin composition, the amount of the ethylene-vinyl ester copolymer saponified product is preferably 50 parts by mass or more, or 100 parts by mass or more, or 200 parts by mass or more, or 300 parts by mass or more relative to 100 parts by mass of cellulose from the perspective of obtaining a good effect of improving the breaking strain, and is preferably 5000 parts by mass or less, or 1000 parts by mass or less, or 700 parts by mass or less, or 500 parts by mass or less from the perspective of molding processability and cost.
[0251] <Elastic Body of the Third Embodiment>
[0252] In the third embodiment, the resin composition may further include an elastomer. When the resin composition includes an elastomer, the phase morphology of the resin composition may have: a morphology in which a polyamide forms a continuous phase and an elastomer forms a dispersed phase; a morphology in which a polyamide forms a dispersed phase and an elastomer forms a continuous phase; and a morphology in which both a polyamide and an elastomer form a continuous phase (i.e., a co-continuous phase structure), preferably a morphology in which a polyamide forms a continuous phase and an elastomer forms a dispersed phase from the perspective of showing good heat resistance as a composition, achieving high rigidity, and low linear expansion.
[0253] In cellulose, from the aspect of realizing the opposite characteristics of low thermal expansion, low anisotropy, and high toughness simultaneously and highly, the lower limit of the proportion of cellulose present in the phase other than the elastomer phase is preferably more than 50% by mass, or more than 60% by mass, or more than 70% by mass, or more than 75% by mass, or more than 80% by mass, or 100% by mass (i.e., substantially all of the cellulose is present in the polyamide phase). From the aspect of the ease of manufacture of the resin composition, the above proportion can be, for example, less than 99% by mass, or less than 98% by mass.
[0254] As an example of a method for confirming that more than 50% by mass of cellulose is present in a phase other than the elastomer phase, for example, when the proportion of cellulose in the phase other than the elastomer phase and the elastomer phase is significantly different, the resin composition can be photographed using a transmission electron microscope without quantification, and the amount of cellulose present in the phase other than the elastomer phase and the amount of cellulose present in the elastomer phase can be confirmed, thereby easily confirming. When quantification is required, the resin composition is sliced with a thickness of about 0.1 to 2 μm to obtain a film-like sample. The sample is immersed in a solvent (such as chloroform, toluene, etc.) that can dissolve the elastomer component but not the components other than the elastomer phase, so that the elastomer phase is dissolved, and after concentrating the eluate, ultracentrifugal separation is performed to separate the cellulose present in the elastomer phase, and then the washing with the solvent is repeated at least 3 times, and it is dried, and the amount of cellulose present in the elastomer phase is measured.
[0255] In addition, as a method for observing the phase morphology of the resin composition, the following methods can be cited: a method of cutting a resin composition in the form of a molded body, pellets, etc. into ultrathin slices, staining the polyamide phase with phosphotungstic acid, etc., and observing with a transmission electron microscope; a method of uniformly surface-treating the surface of the resin composition in the form of a molded body, pellets, etc., immersing it in a solvent that selectively dissolves only the elastomer, extracting the elastomer, and observing with a scanning electron microscope; etc. The obtained image is binarized using an image analyzer, and the diameters of at least 500 randomly selected particles are calculated in the form of equivalent circle diameters, and the particle sizes of each particle are counted, thereby determining the size of the dispersed phase (e.g., dispersed particles described later).
[0256] Elastomer contributes to further improvement of toughness of resin composition. Preferred examples of molecular structure, various characteristics (molecular weight, etc.) and usage (mixing amount, etc.) of elastomer can be the same as those exemplified by elastomers of the first and second embodiments, preferably aromatic compound-conjugated diene copolymers and hydrides thereof, polyolefins and elastomers with core-shell structure exemplified in the first embodiment. As aromatic compound-conjugated diene copolymers and hydrides thereof, aromatic compound-conjugated diene block copolymers and hydrides thereof exemplified in the first embodiment are more preferred, and as polyolefins, copolymers of ethylene and α-olefins are more preferred.
[0257] The elastomer preferably has an acidic functional group in at least a portion thereof. The specific example of the elastomer with an acidic functional group may be the same as the illustration in the first and second embodiments. From the aspect of compatibility with polyamide, the addition amount of the acidic functional group in the elastomer may be the same as the illustration in the first and second embodiments.
[0258] For example, in the resin composition, the amount of the elastomer relative to 100 parts by mass of the polyamide is preferably 1 part by mass or more, or 2 parts by mass or more, or 3 parts by mass or more, or 4 parts by mass or more, or 5 parts by mass or more, from the perspective of improving the toughness and physical property stability of the resin composition, and is preferably 50 parts by mass or less, or 40 parts by mass or less, or 35 parts by mass or less, or 30 parts by mass or less, or 25 parts by mass or less, from the perspective of improving the rigidity and heat resistance of the resin composition.
[0259] The elastomer can form a granular dispersed phase (dispersed particles) in the resin composition. From the perspective of obtaining the effect of improving the toughness and physical stability of the resin composition brought by the elastomer and the ease of manufacturing the resin composition, the dispersed particle size in this case can be the same as the elastomer of the first and second embodiments.
[0260] From the perspective of obtaining a good effect of improving the properties of the resin composition, the uniformity of the dispersed particle size of the elastomer is preferred. The preferred volume ratio of dispersed particles with a particle size of 1 μm or more in the total dispersed particles of the elastomer and the method for adjusting the same can be used for the elastomer of the second embodiment.
[0261] In aromatic vinyl compound-conjugated diene compound block copolymer and its hydride, due to the effect of double bonds in the molecule, crosslinking may occur between molecules, so it is believed that molecular mobility can be reduced. In the resin composition comprising a combination of polyamide and elastomer, the elastomer forms a micro-region to help improve toughness, on the other hand, it is more prone to thermal expansion than polyamide, and therefore becomes a reason for the increase in the thermal expansibility of the resin composition. However, aromatic vinyl compound-conjugated diene compound block copolymer and its hydride can suppress the thermal expansibility of the resin composition to be relatively low due to the crosslinking of the elastomer molecules. Such an elastomer is advantageous in terms of taking into account both high toughness and low linear thermal expansion.
[0262] In addition, when the elastomer contains an acid-modified substance, the formation of crosslinks between the molecules described above also helps to inhibit the reaction between cellulose and the acidic functional group. In this case, it is also possible to obtain the advantage that the linear thermal expansion coefficient of the resin composition is not easily increased due to the elastomer adhering to the cellulose (that is, it is not easy to reduce the effect of reducing the thermal expansion coefficient because the cellulose is not mainly present in the polyamide phase).
[0263] <Cellulose>
[0264] [Cellulose of the first embodiment]
[0265] In the first embodiment, the resin composition includes cellulose. Cellulose includes fibrous cellulose in one embodiment, and is fibrous cellulose in one embodiment. Cellulose includes cellulose nanofibers in one embodiment, and is cellulose nanofibers in one embodiment. As raw materials of cellulose, natural cellulose and regenerated cellulose can be cited. As natural cellulose, wood pulp obtained from wood species (broadleaved trees or coniferous trees), non-wood pulp obtained from non-wood species (bamboo, hemp fiber, bagasse, kenaf, cotton linters, etc.), and their refined pulps (refined cotton linters, etc.) can be used. As non-wood pulp, pulp derived from cotton including cotton linters pulp, pulp derived from hemp, pulp derived from bagasse, pulp derived from kenaf, pulp derived from bamboo, pulp derived from straw, etc. can be used. Cotton-derived pulp, hemp-derived pulp, bagasse-derived pulp, kenaf-derived pulp, bamboo-derived pulp, and straw-derived pulp include cellulose made from refined pulp obtained from raw materials such as cotton linter, cotton linter, hemp-based abaca (e.g., abaca from Ecuador or the Philippines), sisal, bagasse, kenaf, bamboo, and straw, through a refining step such as delignification by steaming treatment, a bleaching step, and the like.
[0266] For example, cellulose nanofibers can be obtained as follows: the pulp is treated with hot water at 100°C or above, the hemicellulose portion is hydrolyzed to make it brittle, and then the cellulose nanofibers are defibrated by a high-pressure homogenizer, a high-pressure microfluidizer, a ball mill, a disc mill, or the like. The diameter of the cellulose nanofibers is 2 to 1000 nm in one embodiment, preferably 4 nm or more, or 5 nm or more, or 10 nm or more, or 15 nm or more, or 20 nm or more, or 50 nm or more, or 100 nm or more, preferably 500 nm or less, or 450 nm or less, or 400 nm or less, or 350 nm or less, or 300 nm or less, or 250 nm or less, or 200 nm or less.
[0267] In the first embodiment, the length, diameter and L / D ratio of each cellulose are obtained by diluting an aqueous dispersion of cellulose to 0.01 to 0.1% by mass using a water-soluble solvent (e.g., water, ethanol, tert-butyl alcohol, etc.), dispersing the cellulose using a high shear homogenizer (e.g., manufactured by IKA, trade name "ULTRA-TURRAXT18") at a rotation speed of 25,000 rpm × 5 minutes, pouring the mixture onto mica, air-drying the mixture, and measuring the mixture using a high-resolution scanning microscope (SEM) or an atomic force microscope (AFM). Specifically, in an observation field adjusted in magnification so that at least 100 fibrous substances can be observed, the length (L) and diameter (D) of 100 randomly selected fibrous substances are measured, and the ratio (L / D) is calculated. The number average of the length (L), the number average of the diameter (D), and the number average of the ratio (L / D) are calculated for cellulose.
[0268] It should be noted that, regarding the length, diameter and L / D ratio of the cellulose in the resin composition described later, the solid resin composition can be used as a measurement sample, and the measurement is carried out by the above-mentioned measurement method, thereby confirming. Alternatively, the length, diameter and L / D ratio of the cellulose in the resin composition can be confirmed as follows: the resin component in the resin composition is dissolved in an organic or inorganic solvent that can dissolve the resin component of the resin composition, and the cellulose is separated. After being fully washed with the above-mentioned solvent, it is replaced with a water-soluble solvent (such as water, ethanol, tert-butyl alcohol, etc.), and a 0.01-0.1 mass % dispersion is prepared, and a high shear homogenizer (such as IKA manufacturing, trade name "ULTRA-TURRAXT18") is used to disperse it again. The redispersion liquid is poured on mica, air-dried as a measurement sample, and measured using the above-mentioned measurement method, thereby confirming. At this time, for the measured cellulose, more than 100 randomly selected roots are used for measurement.
[0269] The crystallinity of cellulose is preferably 55% or more. When the crystallinity is within this range, the mechanical properties (strength, dimensional stability) of cellulose itself are high, so when cellulose is dispersed in a resin, the strength and dimensional stability of the resin composition tend to increase. A more preferred lower limit of the crystallinity is 60%, further preferably 70%, and most preferably 80%. There is no particular upper limit for the crystallinity of cellulose, and the upper limit is preferably high, but from the perspective of productivity, the preferred upper limit is 99%.
[0270] There are acid insoluble components such as alkali-soluble polysaccharides such as hemicellulose and lignin between each other and between microfibril bundles of the cellulose of plant origin.Hemicellulose is a polysaccharide composed of sugars such as mannan and xylan, which is hydrogen-bonded with cellulose and plays the effect of connecting microfibrils.In addition, known lignin is a compound with aromatic rings, which is covalently bonded with hemicellulose in the cell wall of plants.If the impurity residual amounts such as lignin in cellulose are many, then discoloration may occur due to the heat during processing, therefore from the aspect of the discoloration of the resin combination during the suppression of extrusion processing and molding processing, the crystallinity of the preferred cellulose is in the above-mentioned range.
[0271] The crystallinity referred to herein is determined by the following formula using the Segal method from a diffraction pattern (2θ / deg. 10 to 30) obtained when the cellulose is cellulose I type crystal (derived from natural cellulose) when the sample is measured by wide-angle X-ray diffraction.
[0272] Crystallinity (%) = ([Diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] - [Diffraction intensity due to the amorphous state at 2θ / deg. = 18]) / [Diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] × 100
[0273] In addition, regarding the crystallinity, when the cellulose is a cellulose II type crystal (derived from regenerated cellulose), it can be calculated using the following formula based on the absolute peak intensity h0 at 2θ=12.6° of the (110) plane peak belonging to the cellulose II type crystal in wide-angle X-ray diffraction and the peak intensity h1 from the baseline at the plane interval.
[0274] Crystallinity (%) = h1 / h0×100
[0275] As the crystal form of cellulose, there are known types I, II, III, and IV, among which types I and II are particularly common, and types III and IV can be obtained on a laboratory scale, but are not commonly used on an industrial scale. As the cellulose disclosed in the present invention, cellulose containing type I cellulose crystals or type II cellulose crystals is preferred, and cellulose containing type I cellulose crystals and having a crystallinity of 55% or more is more preferred, because the cellulose has relatively high structural mobility and a resin composition having a lower linear expansion coefficient and excellent strength and elongation during tensile and bending deformation can be obtained by dispersing the cellulose in a resin.
[0276] In addition, the degree of polymerization of cellulose is preferably 100 or more, more preferably 150 or more, more preferably 200 or more, more preferably 300 or more, more preferably 400 or more, and is preferably 3500 or less, more preferably 3300 or less, more preferably 3200 or less, more preferably 3100 or less, more preferably 3000 or less.
[0277] The degree of polymerization of cellulose is preferably within the above range from the viewpoint of processability and the development of mechanical properties. From the viewpoint of processability, the degree of polymerization is preferably not too high, and from the viewpoint of the development of mechanical properties, the degree of polymerization is preferably not too low.
[0278] The degree of polymerization of cellulose refers to the average degree of polymerization measured by the reduced viscosity method using an ethylenediamine copper solution described in the confirmation test (3) of "Explanation of the Fifteenth Revised Japanese Pharmacopoeia (published by Hirokawa Shoten)".
[0279] In one embodiment, the weight average molecular weight (Mw) of cellulose is 100,000 or more, more preferably 200,000 or more. The ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) is 6 or less, preferably 5.4 or less. The larger the weight average molecular weight, the fewer the number of terminal groups of the cellulose molecule. In addition, the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight represents the width of the molecular weight distribution, so the smaller the Mw / Mn, the fewer the number of terminals of the cellulose molecule. Since the terminal of the cellulose molecule is the starting point of thermal decomposition, in the case where not only the weight average molecular weight of the cellulose molecule is increased, but also the width of the molecular weight distribution is narrowed while the weight average molecular weight is increased, a highly heat-resistant cellulose and a resin composition comprising cellulose and a resin can be obtained. From the aspect of the ease of obtaining the cellulose raw material, the weight average molecular weight (Mw) of the cellulose can be, for example, 600,000 or less, or 500,000 or less. From the aspect of the ease of manufacturing cellulose, the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) can be, for example, 1.5 or more, or 2 or more. Mw can be controlled within the above range by a method of selecting a cellulose raw material having a Mw corresponding to the purpose, a method of appropriately performing physical and / or chemical treatment on the cellulose raw material in an appropriate range, etc. In addition, Mw / Mn can also be controlled within the above range by a method of selecting a cellulose raw material having a Mw / Mn corresponding to the purpose, a method of appropriately performing physical and / or chemical treatment on the cellulose raw material in an appropriate range, etc. In both the control of Mw and the control of Mw / Mn, as the above-mentioned physical treatment, dry or wet grinding such as high-pressure microfluidizer, ball mill, disc mill, etc., physical treatment by applying mechanical forces such as impact, shearing, scraping, and friction using a crusher, homogeneous mixer, high-pressure homogenizer, ultrasonic device, etc., and as the above-mentioned chemical treatment, steaming, bleaching, acid treatment, regenerated cellulose, etc. can be exemplified.
[0280] The weight average molecular weight and number average molecular weight of cellulose mentioned here are values determined by dissolving cellulose in N,N-dimethylacetamide to which lithium chloride is added, and then subjecting the result to gel permeation chromatography using N,N-dimethylacetamide as a solvent.
[0281] As a method for controlling the degree of polymerization (i.e., average degree of polymerization) or molecular weight of cellulose, hydrolysis treatment and the like can be cited. Through the hydrolysis treatment, the amorphous cellulose inside the cellulose is depolymerized, and the average degree of polymerization is reduced. And at the same time, through the hydrolysis treatment, in addition to the above-mentioned amorphous cellulose, impurities such as hemicellulose and lignin are also removed, so that the fiber becomes porous inside. Therefore, in the process of applying mechanical shear force to cellulose in the kneading process described later, cellulose is easily subjected to mechanical treatment, and cellulose is easily refined.
[0282] There is no particular limitation on the method of hydrolysis, and examples include acid hydrolysis, alkaline hydrolysis, hot water decomposition, steam explosion, microwave decomposition, and the like. These methods may be used alone or in combination of two or more. In the method of acid hydrolysis, for example, α-cellulose obtained from fibrous plants in the form of pulp is used as a cellulose raw material, and a protonic acid, carboxylic acid, Lewis acid, heteropoly acid, etc. are added in an appropriate amount in a state in which the cellulose is dispersed in an aqueous medium, and the mixture is heated while stirring, thereby making it easy to control the average degree of polymerization. The reaction conditions such as temperature, pressure, and time at this time vary according to the type of cellulose, cellulose concentration, type of acid, acid concentration, etc., and can be appropriately adjusted in a manner to achieve the target average degree of polymerization. For example, the condition of treating cellulose for more than 10 minutes at a temperature of more than 100°C under pressure using an aqueous solution of an inorganic acid of less than 2% by mass can be cited. Under this condition, catalyst components such as acid penetrate into the interior of the cellulose, promote hydrolysis, reduce the amount of catalyst components used, and make subsequent refining easier. In addition, the dispersion liquid of the cellulose raw material during hydrolysis may contain a small amount of an organic solvent in addition to water within a range that does not impair the effects of the present invention.
[0283] The alkali-soluble polysaccharides that cellulose may contain include β-cellulose and γ-cellulose in addition to hemicellulose. For those skilled in the art, alkali-soluble polysaccharides can be understood as components obtained in the form of alkali-soluble parts in the whole cellulose obtained by solvent extraction and chlorine treatment of plants (such as wood) (i.e., components after removing α-cellulose from the whole cellulose). Alkali-soluble polysaccharides are polysaccharides containing hydroxyl groups, which have poor heat resistance and may cause undesirable conditions such as decomposition when heated, yellowing during heat aging, and reduction in the strength of cellulose fibers. Therefore, it is preferred that the content of alkali-soluble polysaccharides in cellulose is low.
[0284] In one embodiment, from the aspect of obtaining good dispersibility of cellulose, the average content of alkali-soluble polysaccharides in cellulose is preferably 20% by mass or less, or 18% by mass or less, or 15% by mass or less, or 12% by mass or less, or 11% by mass or less, or 8% by mass or less relative to 100% by mass of cellulose. From the aspect of the ease of manufacturing cellulose, the above content can be 1% by mass or more, or 2% by mass or more, or 3% by mass or more, or 6% by mass or more. In one embodiment, the average content of alkali-soluble polysaccharides in cellulose raw materials can be 13% by mass or less, or 12% by mass or less, or 11% by mass or less, or 8% by mass or less, and most preferably 0% by mass, from the aspect of the ease of obtaining cellulose raw materials, for example, it can be 3% by mass or more, or 6% by mass or more.
[0285] The average content of alkali-soluble polysaccharides can be obtained by the method described in the non-patent literature (Handbook of Wood Science Experiments, edited by the Japan Wood Society, pages 92-97, 2000), by subtracting the α-cellulose content from the total cellulose content (Wise method). In addition, this method can be understood as a method for determining the amount of hemicellulose in this field. The alkali-soluble polysaccharide content is calculated three times for one sample, and the number mean of the calculated alkali-soluble polysaccharide content is used as the average content of alkali-soluble polysaccharides.
[0286] In one embodiment, from the perspective of avoiding a decrease in the heat resistance of cellulose and the discoloration associated therewith, the average content of the acid-insoluble components in the cellulose is preferably 10% by mass or less, or 5% by mass or less, or 3% by mass or less relative to 100% by mass of the cellulose. From the perspective of ease of production of the cellulose, the above content may be 0.1% by mass or more, or 0.2% by mass or more, or 0.3% by mass or more.
[0287] About the acid insoluble component average content, the Klason method of recording in the non-patent literature (wood science experiment manual, Japan Wood Society compilation, 92~97 pages, 2000) is used to carry out quantitative analysis with the form of acid insoluble component. In addition, this method can be understood as the assay method of lignin amount in this field. After stirring the sample in sulfuric acid solution to dissolve cellulose and hemicellulose etc., glass fiber filter paper is utilized to filter, and the resulting residue is equivalent to the acid insoluble component. The acid insoluble component content is calculated by the acid insoluble component mass, and the average of the acid insoluble component content calculated for 3 samples is used as the acid insoluble component average content.
[0288] Cellulose may be chemically treated (e.g., oxidized or chemically modified using a modifying agent). For example, cellulose fibers may be oxidized using 2,2,6,6-tetramethylpiperidin-1-oxyl radicals as shown in Cellulose (1998) 5, 153-164, followed by washing and mechanical defibration, and the resulting finely divided cellulose fibers may be used.
[0289] In the first embodiment, from the perspective of obtaining the advantages of low linear expansion coefficient and high rigidity brought by cellulose, the proportion of cellulose relative to 100% by mass of the resin composition (especially the proportion of cellulose nanofibers) is preferably 0.1% by mass or more, or 0.5% by mass or more, or 1% by mass or more, or 3% by mass or more, and from the perspective of obtaining the advantages brought by other components in the resin composition, it is preferably 30% by mass or less, or 25% by mass or less, or 20% by mass or less, or 15% by mass or less.
[0290] In the first embodiment, from the perspective of obtaining the advantages of low linear expansion coefficient and high rigidity brought by cellulose, the ratio of cellulose to 100 parts by mass of polyamide (especially the ratio of cellulose nanofibers) is preferably 1 part by mass or more, or 5 parts by mass or more, or 10 parts by mass or more, or 15 parts by mass or more, and from the perspective of well dispersing cellulose in the polyamide phase, the ratio is preferably 50 parts by mass or less, or 40 parts by mass or less, or 30 parts by mass or less, or 20 parts by mass or less.
[0291] <Cellulose of the Second and Third Embodiments>
[0292] The resin composition of the second and third embodiments includes cellulose. Cellulose may include fibrous cellulose. Cellulose may include cellulose nanofibers (CNF) having a diameter of 50 to 1000 nm and a length (L) / diameter (D) ratio of 30 or more, cellulose nanocrystals (CNC) having a diameter of less than 100 nm and a length (L) / diameter (D) of less than 30, or cellulose microfibers (CMF) having a diameter greater than 1 μm to 50 μm, or a mixture thereof, preferably CNF, CNC or CMF, or a mixture thereof. As these celluloses, the natural cellulose and regenerated cellulose exemplified above may be cited.
[0293] Cellulose nanofibers (CNF) can be obtained by the steps described in the first embodiment. In one embodiment, the diameter of CNF is 50 to 1000 nm. The diameter of CNF is preferably 50 nm or more, more preferably 100 nm or more, more preferably 400 nm or less, and more preferably 200 nm or less. In addition, in one embodiment, the L / D of CNF is 30 or more, preferably 50 or more, more preferably 80 or more, and more preferably 100 or more, preferably 5000 or less, more preferably 4000 or less, and more preferably 3000 or less.
[0294] Figure 1 : is a microscope image showing an example of cellulose nanofibers. It can be seen that each cellulose has a fibrous structure with a diameter of 50 to 1000 nm and an L / D of 30 or more.
[0295] Cellulose nanocrystals (CNC) are crystalline cellulose remaining after the above-mentioned pulp is cut as raw material and the amorphous part of cellulose is dissolved in an acid such as hydrochloric acid or sulfuric acid. In one embodiment, the diameter of CNC is less than 100nm, preferably less than 80nm, more preferably less than 70nm, preferably more than 3nm, more preferably more than 5nm, and more preferably more than 10nm. In addition, in one embodiment, the length / diameter ratio (L / D ratio) of CNC is less than 30, preferably less than 20, more preferably less than 15, and more preferably less than 10. In one embodiment, the L / D ratio is greater than 1, preferably greater than 2, more preferably greater than 4, and more preferably greater than 5.
[0296] Figure 2 is a microscope image showing an example of cellulose nanocrystals (also called cellulose nanowhiskers or needle-like particulate cellulose), Figure 2 (B) is Figure 2 Partially enlarged view of (A). It can be seen that each cellulose forms a needle-like crystal particle structure with a diameter of less than 100 nm and an L / D of less than 30.
[0297] In addition, cellulose microfibers (hereinafter sometimes referred to as CMF) refer to fibrous cellulose of larger size obtained by reducing the defibration process in the manufacturing process of CNF. In one embodiment, the diameter of CMF is greater than 1 μm to 50 μm. The diameter of CMF is preferably 2 μm or more, more preferably 5 μm or more, and more preferably 10 μm or more, preferably 45 μm or less, more preferably 40 μm or less, and more preferably 35 μm or less. The L / D of CMF is preferably 30 or more, more preferably 50 or more, and more preferably 70 or more, preferably 2000 or less, more preferably 1000 or less, and more preferably 500 or less. CMF is obtained by about half of the energy of the energy normally used to manufacture CNF.
[0298] Figure 3 This is a micrograph of cellulose microfibrils. It can be seen that each cellulose has a diameter of more than 1 μm to 50 μm and an L / D of 30 or more.
[0299] The amount of cellulose relative to the total mass of 100 mass of the resin composition is preferably 0.1 to 30 mass%. The more preferred upper limit of the amount of cellulose is 25 mass%, 20 mass%, or 15 mass%. The more preferred lower limit of the amount of cellulose is 0.5 mass%, 1 mass%, or 3 mass%. From the perspective of suppressing the thermal expansion coefficient and obtaining good physical property stability, it is preferably within the above range.
[0300] As preferred forms of cellulose in the second and third embodiments, from the aspect of ensuring physical property stability, CNF alone, CMF alone, CNF and CNC combined, CNF and CMF combined, CMF and CNC combined, CMF, CNF, and CNC combined can be cited. As more preferred forms, CMF alone, CNF and CNC combined, CNF and CMF combined, CMF and CNC combined, CMF and CNC combined, and CMF, CNF, and CNC combined can be cited.
[0301] When CNF and CMF are used together, when the total amount of cellulose is 100% by mass, the preferred ratio of CMF is 50 to 99% by mass. The upper limit of the above ratio is more preferably 97% by mass, further preferably 95% by mass, further preferably 93% by mass, and most preferably 90% by mass. The lower limit of the above ratio is more preferably 55% by mass, further more preferably 60% by mass, and most preferably 70% by mass.
[0302] In addition, when CNF and CNC are used in combination, and when CMF and CNC are used in combination, when the total amount of cellulose is 100% by mass, the preferred ratio of CNC is 50 to 99% by mass. The upper limit of the above ratio is more preferably 97% by mass, further preferably 95% by mass, further preferably 93% by mass, and most preferably 90% by mass. The lower limit of the above ratio is more preferably 55% by mass, further more preferably 60% by mass, and most preferably 70% by mass.
[0303] In addition, when CMF, CNF and CNC are used together, when the total amount of cellulose is 100% by mass, the preferred ratio of CNC is 50 to 99% by mass. The upper limit of the above ratio is more preferably 97% by mass, more preferably 95% by mass, further preferably 93% by mass, and most preferably 90% by mass. The lower limit of the above ratio is more preferably 55% by mass, further more preferably 60% by mass, and most preferably 65% by mass. In addition, when the total amount of cellulose other than CNC is 100% by mass, the preferred ratio of CMF is 50 to 99% by mass. The upper limit of the above ratio is more preferably 97% by mass, further preferably 95% by mass, further preferably 93% by mass, and most preferably 90% by mass. The lower limit of the above ratio is more preferably 55% by mass, further more preferably 60% by mass, and most preferably 70% by mass.
[0304] The amount of CNF relative to 100% by mass of the resin composition is preferably 0.1 to 20% by mass. By making the amount of CNF within the above range, properties such as thermal expansion can be improved. The lower limit of the above amount is more preferably 1% by mass, more preferably 2% by mass, further preferably 3% by mass, and most preferably 5% by mass. In addition, the upper limit is more preferably 18% by mass, further preferably 16% by mass, further preferably 14% by mass, and most preferably 12% by mass.
[0305] In addition, the amount of CMF relative to 100% by mass of the resin composition is preferably 0.1 to 20% by mass. By making the amount of CMF within the above range, the properties such as elongation at break and vibration fatigue characteristics can be improved. The lower limit of the above amount is more preferably 1% by mass, further preferably 2% by mass, further more preferably 3% by mass, and most preferably 5% by mass. In addition, the upper limit is more preferably 18% by mass, further preferably 16% by mass, further preferably 14% by mass, and most preferably 12% by mass.
[0306] In the second and third embodiments, regarding the length, diameter and L / D ratio of each of CNC and CNF, the aqueous dispersion of each of CNC and CNF is dispersed using a high shear homogenizer (e.g., manufactured by Nippon Seiki Co., Ltd., trade name "EXCEL AutoHomogenizer ED-7") at a speed of 15,000 rpm × 5 minutes, and the obtained aqueous dispersion is diluted with pure water to 0.1-0.5% by mass, poured on mica, air-dried, and prepared as a measurement sample, and measured using a high-resolution scanning microscope (SEM) or an atomic force microscope (AFM). Specifically, in an observation field adjusted by magnification in a manner that at least 100 celluloses can be observed, the length (L) and diameter (D) of 100 randomly selected celluloses are measured, and the ratio (L / D) is calculated. Cellulose with a ratio (L / D) of less than 30 is classified as CNC, and cellulose with a ratio (L / D) of 30 or more is classified as CNF. The number average of length (L), the number average of diameter (D) and the number average of ratio (L / D) were calculated for CNC and CNF, respectively, as the length, diameter and L / D ratio of CNC and CNF, respectively. In addition, the length and diameter of the cellulose mentioned above are the number averages of the 100 cellulose strands.
[0307] CMF has different size grades from CNC and CNF, and electron microscopes are not suitable for measuring the length, diameter, and L / D ratio of CMF, so the size of CMF is observed by other methods. A low-concentration aqueous dispersion prepared in a manner of about 0.1% by mass of CMF is given sufficient vibration using an ultrasonic cleaner, or a dispersion machine (such as Despamill manufactured by Asada Iron Works Co., Ltd.) is used to perform a 20-minute dispersion treatment, and after untangling the CMF, the aqueous dispersion is directly observed using an optical microscope. The measurement-calculation method at this time is the same as that in CNF and CNC.
[0308] Alternatively, regarding the length, diameter and L / D ratio of each of CMF, CNC and CNF in the resin composition, the polymer component in the composition can be dissolved in an organic or inorganic solvent that can dissolve the polymer component of the composition, and the cellulose can be separated. After being fully washed with the above solvent, an aqueous dispersion in which the solvent is replaced with pure water is prepared, and the dispersion is diluted with pure water to a cellulose concentration of 0.1 to 0.5% by mass, and then measured by the above method.
[0309] The average diameter of CNC obtained by volume average particle size measurement is preferably 10 nm or more, more preferably 15 nm or more, further preferably 20 nm or more, more preferably 40 nm or more, further preferably 50 nm or more, preferably 1000 nm or less, more preferably 700 nm or less, further preferably 500 nm or less, further preferably 300 nm or less.
[0310] The average diameter of CNF as measured by volume average particle size is preferably 20 nm or more, more preferably 40 nm or more, and even more preferably 50 nm or more, and is preferably 1000 nm or less, more preferably 700 nm or less, and even more preferably 500 nm or less.
[0311] The volume average particle size is a value obtained by using a laser diffraction / scattering particle size distribution meter as the spherical equivalent diameter (volume average particle size) of the particles when the cumulative volume reaches 50%. Specifically, the sample is made to have a solid content of 40% by mass, and is kneaded at 126 rpm for 30 minutes at room temperature and normal pressure in a planetary mixer (e.g., 5DM-03-R manufactured by Shinagawa Industry Co., Ltd., with a hook-type stirring blade), and then made into a pure water suspension with a concentration of 0.5% by mass, and is dispersed using a high shear homogenizer (e.g., manufactured by Nippon Seiki Co., Ltd., trade name "EXCEL Auto Homogenizer ED-7") at a rotation speed of 15,000 rpm × 5 minutes. A centrifuge (e.g., manufactured by Kubota Shoji Co., Ltd., trade name "6800 Centrifuge", rotor type RA-400) is used at a centrifugal force of 39200 m 2 / s treatment conditions for 10 minutes, the supernatant was collected, and the supernatant was further centrifuged at 116000 m 2 / s for 45 minutes, and the supernatant after centrifugation is collected. Using the supernatant, the cumulative 50% particle size (i.e., the spherical conversion diameter of the particles when the cumulative volume reaches 50% relative to the volume of the entire particles) in the volume frequency particle size distribution obtained by using a laser diffraction / scattering particle size distribution meter (e.g., manufactured by Horiba, Ltd., trade name "LA-910" or trade name "LA-950", ultrasonic treatment for 1 minute, refractive index 1.20) is used as the volume average particle size.
[0312] In the second and third embodiments, the crystallinity, crystal form, degree of polymerization, weight average molecular weight (Mw), ratio of weight average molecular weight to number average molecular weight (Mn) (Mw / Mn), average content of alkali-soluble polysaccharides, average content of acid-insoluble components of cellulose, and their measurement and adjustment methods may be the same as those exemplified in the first embodiment.
[0313] <Hydrophobicization of Cellulose>
[0314] The cellulose in the first to third embodiments may be cellulose that has been hydrophobized using a hydrophobizing agent (also referred to as chemically modified cellulose in the present disclosure). By hydrophobizing, the hydrogen bonds between the celluloses become weaker, which helps to disperse microscopically, and as the heat resistance of cellulose is improved, the deterioration due to mixing with the resin can be suppressed, and the cellulose has the effect of not being easily the starting point of physical defects. As a hydrophobizing agent (also referred to as a modifying agent in the present disclosure), a compound that reacts with the hydroxyl group of cellulose can be used, and esterifying agents, etherifying agents, and silylating agents can be cited. Esterifying agents are particularly preferred. In a preferred embodiment, hydrophobization is acylation using an esterifying agent. As esterifying agents, preferred are acyl halides, acid anhydrides, and carboxylic acid vinyl esters. In a particularly preferred embodiment, hydrophobization is acetylation.
[0315] The acid halide may be at least one selected from the group consisting of compounds represented by the following formula (1).
[0316] R 1 -C(=O)-X (1)
[0317] (Where R 1 represents an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 24 carbon atoms, or an aryl group having 6 to 24 carbon atoms, and X is Cl, Br or I.
[0318] As specific examples of acyl halides, acetyl chloride, acetyl bromide, acetyl iodide, propionyl chloride, propionyl bromide, propionyl iodide, butyryl chloride, butyryl bromide, butyryl iodide, benzoyl chloride, benzoyl bromide, benzoyl iodide, etc. can be cited, but they are not limited to these. Among them, from the aspects of reactivity and handling, acyl chloride can be appropriately used. It should be noted that in the reaction of acyl halides, in order to play a role as a catalyst and neutralize the acidic substance as a by-product, one or more basic compounds can be added. As basic compounds, specifically, tertiary amine compounds such as triethylamine and trimethylamine; and nitrogen-containing aromatic compounds such as pyridine and dimethylaminopyridine can be cited, but they are not limited to this.
[0319] As the acid anhydride, any appropriate acid anhydride can be used. For example:
[0320] Saturated aliphatic monocarboxylic anhydrides of acetic acid, propionic acid, (iso)butyric acid, valeric acid, etc.; unsaturated aliphatic monocarboxylic anhydrides of (meth)acrylic acid, oleic acid, etc.;
[0321] Alicyclic monocarboxylic anhydrides of cyclohexanecarboxylic acid, tetrahydrobenzoic acid, etc.;
[0322] Aromatic monocarboxylic anhydrides of benzoic acid, 4-methylbenzoic acid, etc.;
[0323] Examples of the dicarboxylic acid anhydride include saturated aliphatic dicarboxylic anhydrides such as succinic anhydride and adipic acid, unsaturated aliphatic dicarboxylic anhydrides such as maleic anhydride and itaconic anhydride, alicyclic dicarboxylic anhydrides such as 1-cyclohexene-1,2-dicarboxylic anhydride, hexahydrophthalic anhydride and methyltetrahydrophthalic anhydride, and aromatic dicarboxylic anhydrides such as phthalic anhydride and naphthalene dicarboxylic anhydride;
[0324] Examples of the trivalent or higher polycarboxylic acid anhydrides include polycarboxylic acids (anhydrides) such as trimellitic anhydride and pyromellitic dianhydride.
[0325] It should be noted that, in the reaction of the acid anhydride, one or more of an acidic compound such as sulfuric acid, hydrochloric acid, phosphoric acid, or a Lewis acid (for example, a Lewis acid compound represented by MYn, where M represents a semimetal element such as B, As, Ge; or a base metal element such as Al, Bi, In; or a transition metal element such as Ti, Zn, Cu; or a lanthanide element, where n is an integer equivalent to the atomic valence of M, representing 2 or 3, and Y represents a halogen atom, OAc, OCOCF3, ClO4, SbF6, PF6 or OSO2CF3(OTf)), or a basic compound such as triethylamine or pyridine can be added as a catalyst.
[0326] As the carboxylic acid vinyl ester, the following formula (1) is preferred:
[0327] R-COO-CH=CH2…Formula (1)
[0328] A carboxylic acid vinyl ester represented by {wherein R is any one of an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 16 carbon atoms, or an aryl group having 6 to 24 carbon atoms}. The carboxylic acid vinyl ester is more preferably at least one selected from the group consisting of vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl cyclohexanecarboxylate, vinyl octanoate, vinyl decanoate, vinyl laurate, vinyl myristic acid, vinyl palmitate, vinyl stearate, vinyl pivalate, vinyl octanoate, divinyl adipate, vinyl methacrylate, vinyl crotonate, vinyl pivalate, vinyl octanoate, vinyl benzoate, and vinyl cinnamate. When the esterification reaction is carried out using vinyl carboxylate, one or more selected from the group consisting of alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkaline earth metal carbonates, alkali metal hydrogen carbonates, primary to tertiary amines, quaternary ammonium salts, imidazole and its derivatives, pyridine and its derivatives, and alkoxides can be added as a catalyst.
[0329] Examples of the alkali metal hydroxide and alkaline earth metal hydroxide include sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, barium hydroxide, etc. Examples of the alkali metal carbonate, alkaline earth metal carbonate, and alkali metal hydrogen carbonate include lithium carbonate, sodium carbonate, potassium carbonate, cesium carbonate, magnesium carbonate, calcium carbonate, barium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, and cesium hydrogen carbonate, etc.
[0330] The primary to tertiary amines refer to primary amines, secondary amines and tertiary amines, and specific examples thereof include ethylenediamine, diethylamine, proline, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethyl-1,3-propylenediamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, tris(3-dimethylaminopropyl)amine, N,N-dimethylcyclohexylamine, triethylamine and the like.
[0331] Examples of imidazole and derivatives thereof include 1-methylimidazole, 3-aminopropylimidazole, and carbonyldiimidazole.
[0332] Examples of pyridine and derivatives thereof include N,N-dimethyl-4-aminopyridine and picoline.
[0333] Examples of the alkoxide include sodium methoxide, sodium ethoxide, potassium tert-butoxide, and the like.
[0334] Examples of the carboxylic acid include at least one selected from the group consisting of compounds represented by the following formula (1).
[0335] R-COOH…(1)
[0336] (In the formula, R represents an alkyl group having 1 to 16 carbon atoms, an alkenyl group having 2 to 16 carbon atoms, a cycloalkyl group having 3 to 16 carbon atoms, or an aryl group having 6 to 16 carbon atoms.)
[0337] Specific examples of carboxylic acids include at least one selected from the group consisting of acetic acid, propionic acid, butyric acid, caproic acid, cyclohexanecarboxylic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, pivalic acid, methacrylic acid, crotonic acid, pivalic acid, caprylic acid, benzoic acid, and cinnamic acid.
[0338] Among these carboxylic acids, at least one selected from the group consisting of acetic acid, propionic acid, and butyric acid is preferred from the viewpoint of reaction efficiency, and acetic acid is particularly preferred.
[0339] It should be noted that, in the reaction of carboxylic acid, one or more of an acidic compound such as sulfuric acid, hydrochloric acid, phosphoric acid, or a Lewis acid (for example, a Lewis acid compound represented by MYn, where M represents a semimetal element such as B, As, Ge; or a base metal element such as Al, Bi, In; or a transition metal element such as Ti, Zn, Cu; or a lanthanide element, where n is an integer equivalent to the atomic valence of M, representing 2 or 3, and Y represents a halogen atom, OAc, OCOCF3, ClO4, SbF6, PF6 or OSO2CF3(OTf)), or a basic compound such as triethylamine or pyridine can be added as a catalyst.
[0340] Among these esterification reaction agents, at least one selected from the group consisting of acetic anhydride, propionic anhydride, butyric anhydride, vinyl acetate, vinyl propionate, vinyl butyrate and acetic acid is particularly preferred from the viewpoint of reaction efficiency, and acetic anhydride and vinyl acetate are particularly preferred.
[0341] In the case of obtaining hydrophobized cellulose nanofibers, there is no particular limitation on the method of miniaturizing the natural cellulose raw material and reducing the fiber diameter, and it is preferred to make the processing conditions of the defibrination (the method of imparting the shear field, the size of the shear field, etc.) more efficient. In particular, by impregnating the defibrination solution containing an aprotic solvent into the cellulose raw material with a cellulose purity of more than 85% by mass, the swelling of cellulose can be caused in a short time, and the miniaturization of cellulose can be carried out only by imparting slight stirring and shearing energy. In addition, by adding a cellulose modifier immediately after defibrination, hydrophobized cellulose nanofibers can be obtained. From the aspects of generation efficiency and refining efficiency (i.e., the high cellulose purification of the hydrophobized cellulose nanofibers) and the physical properties of the resin composition, this method is preferred.
[0342] Examples of the aprotic solvent include alkyl sulfoxides, alkyl amides, pyrrolidones, etc. These solvents may be used alone or in combination of two or more.
[0343] Examples of the alkyl sulfoxides include dimethyl sulfoxide (DMSO), di-C1-4 alkyl sulfoxides such as methyl ethyl sulfoxide and diethyl sulfoxide.
[0344] Examples of the alkylamides include N,N-dimethylformamide (DMF), N,N-diethylformamide and other N,N-di-C1-4 alkylformamides; N,N-dimethylacetamide (DMAc), N,N-diethylacetamide and other N,N-di-C1-4 alkylacetamides; and the like.
[0345] Examples of the pyrrolidones include pyrrolidones such as 2-pyrrolidone and 3-pyrrolidone; and N-C1-4 alkylpyrrolidone such as N-methyl-2-pyrrolidone (NMP).
[0346] These aprotic solvents can be used alone or in combination of two or more. Among these aprotic solvents (the numbers in brackets are the number of donors), if DMSO (29.8), DMF (26.6), DMAc (27.8), NMP (27.3), etc., especially DMSO, is used, hydrophobized cellulose nanofibers with high thermal decomposition starting temperature can be more effectively produced. Its mechanism of action may not be clear, but it is presumed to be caused by uniform microswelling of the fiber raw material in the aprotic solvent.
[0347] When the cellulose raw material swells in an aprotic solvent, the aprotic solvent quickly penetrates into the fibrils constituting the raw material and swells, thereby making the microfibrils mutually microfibrillated. It is speculated that by chemically modifying after forming this state, the microfibers are uniformly hydrophobized as a whole, and high heat resistance can be obtained as a result. In addition, the microfibrillated chemically modified microfibers can maintain high crystallinity, and high mechanical properties and excellent dimensional stability (especially the linear thermal expansion coefficient is significantly reduced) can be obtained when compounded with a resin.
[0348] In the case of obtaining hydrophobized cellulose nanofibers, the cellulose nanofibers that have been micronized (defibrated) and hydrophobized can be obtained by using a device that applies collision shear, such as a planetary ball mill and a bead mill, a device that applies a rotating shear field that can induce fibrillation of cellulose, such as a disc grinder and a grinder, or a device that can efficiently perform mixing, stirring and dispersing functions, such as various kneaders and planetary mixers.
[0349] The hydrophobicity (modification degree) of cellulose is expressed in the form of the average degree of substitution of hydroxyl groups (the average number of substituted hydroxyl groups of each glucose as the basic structural unit of cellulose, also referred to as DS). In one embodiment, the DS of chemically modified cellulose is preferably 0.01 or more and 2.0 or less. When DS is 0.01 or more, a resin composition containing chemically modified cellulose with a high thermal decomposition starting temperature can be obtained. On the other hand, when DS is 2.0 or less, an unmodified cellulose skeleton remains in the chemically modified cellulose, and a resin composition containing chemically modified cellulose with high tensile strength and dimensional stability derived from cellulose and high thermal decomposition starting temperature derived from chemical modification can be obtained. DS is more preferably 0.05 or more, further preferably 0.1 or more, particularly preferably 0.2 or more, most preferably 0.3 or more, more preferably 1.8 or less, further preferably 1.5 or less, particularly preferably 1.2 or less, and most preferably 1.0 or less.
[0350] In the reflective infrared absorption spectrum of hydrophobized cellulose, the peak position of the absorption band changes depending on the type of hydrophobized modifying group. Based on the change in the peak position, it is possible to determine which absorption band the peak is based on, and to identify the modifying group. In addition, the modification rate can be calculated based on the peak intensity ratio of the peak derived from the modifying group to the peak derived from the cellulose skeleton.
[0351] In the case where the modifying group is an acyl group, the degree of acyl substitution (DS) can be calculated based on the peak intensity ratio of the peak derived from the acyl group to the peak derived from the cellulose skeleton from the reflective infrared absorption spectrum of the esterified cellulose. The peak of the absorption band based on C=O of the acyl group appears at 1730 cm -1 The peak of the absorption band of CO based on the cellulose backbone chain appears at 1030 cm -1 (Refer to Figure 4 and 5 ). A correlation diagram of (DS obtained by solid NMR measurement of esterified cellulose described later) and (modification rate (IR index 1030) defined by the ratio of the peak intensity of the absorption band based on C=O of the acyl group to the peak intensity of the absorption band based on CO of the cellulose backbone chain) can be prepared, and the DS of the esterified cellulose can be obtained by using a calibration curve (substitution degree DS=4.13×IR index (1030)) calculated from the correlation diagram.
[0352] It should be noted that when it is difficult to perform appropriate measurement using the above-mentioned reflection infrared absorption spectrum, solid NMR is used. Regarding the method for calculating the DS of esterified cellulose based on solid NMR, the DS of esterified cellulose after freeze-crushing can be calculated by 13C solid NMR measurement, DS is calculated from the following formula based on the area intensity (Inf) of the signal attributed to one carbon atom derived from the modifying group relative to the total area intensity (Inp) of the signals attributed to carbons C1-C6 derived from the pyranose ring of cellulose appearing in the range of 50 ppm to 110 ppm.
[0353] DS=(Inf)×6 / (Inp)
[0354] For example, when the modifying group is an acetyl group, a signal of 23 ppm attributed to -CH 3 can be used.
[0355] Used 13 The conditions for C solid NMR measurement are as follows, for example.
[0356] Device: Bruker Biospin Avance500WB
[0357] Frequency: 125.77MHz
[0358] Determination method: DD / MAS method
[0359] Waiting time: 75sec
[0360] NMR sample tube: 4mmΦ
[0361] Integration times: 640 times (about 14 hours)
[0362] MAS: 14,500Hz
[0363] Chemical shift standard: glycine (external standard: 176.03 ppm)
[0364] <Antioxidants>
[0365] In the first to third embodiments, the resin composition may further include an antioxidant. From the perspective of suppressing the thermal degradation of each component (e.g., polyphenylene ether, elastomer, and / or ethylene-vinyl ester copolymer saponified product) when the resin composition is melt-kneaded at a high temperature above the melting point of polyamide, an antioxidant is advantageous. The antioxidant may be one or more selected from the group consisting of hindered phenol antioxidants, hindered amine antioxidants, phosphorus antioxidants, sulfur antioxidants, benzotriazole antioxidants, benzophenone antioxidants, triazine antioxidants, salicylate antioxidants, and p-phenylenediamine antioxidants. For example, in the third embodiment, hindered phenol antioxidants and phosphorus antioxidants are particularly preferred.
[0366] Examples of the hindered phenol antioxidant include 2,4-bis[(laurylthio)methyl]-o-cresol, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzil), 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzil), 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,6-di-tert-butyl-4-nonylphenol, 2,2'-isobutylene-bis-(4,6-dimethyl-phenol), 4,4'-butylene-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, and tetrakis(3,5-di-tert-butyl-4-hydroxyphenyl)propionate. -bis-(2-tert-butyl-5-methylphenol), 2,2'-thio-bis-(6-tert-butyl-4-methylphenol), 2,5-di-tert-amylhydroquinone, 2,2'thiodiethylbis-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate, 1,1,3-tris-(2'-methyl-4'-hydroxy-5'-tert-butylphenyl)-butane, 2,2'-methylene-bis-(6-(1-methyl-cyclohexyl)-p-cresol), 2,4-dimethyl-6-(1-methyl-cyclohexyl)-phenol, N,N-hexamethylenebis(3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid amide), etc. Other oligomer and polymer compounds having a hindered phenol structure may also be used.
[0367] Specific examples include ADKSTAB AO-20, AO-30, AO-40, AO50, AO60, AO80, and AO320 manufactured by ADEKA Corporation; KEMINOX 101, 179, 76, and 9425 manufactured by Chemipro Corporation; IRGANOX 1010, 1035, 1076, 1098, 1135, 1330, 1726, 1425WL, 1520L, 245, 259, 3114, 5057, and 565 manufactured by BASF Corporation; and Cyanox CY-1790 and CY-2777 manufactured by Sun Chemical Corporation.
[0368] Examples of hindered amine antioxidants include bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(N-methyl-2,2,6,6-tetramethyl-4-piperidyl) sebacate, N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,6-hexanediamine, 2-methyl-2-(2,2,6,6-tetramethyl-4-piperidyl)amino-N-(2,2,6,6-tetramethyl-4-piperidyl)propionamide, tetrakis(2,2,6,6-tetramethyl-4-piperidyl) (1,2,3,4-butanetetracarboxylate, poly[{6-(1,1,3,3-tetramethylbutyl)imino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexadecane methyl{(2,2,6,6-tetramethyl-4-piperidinyl)imino}], poly[(6-morpholino-1,3,5-triazine-2,4-diyl){(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}], polycondensate of dimethyl succinate and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine, N,N'-4,7-tetra[4,6-bis{N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidinyl)amino}-1,3,5-triazin-2-yl]-4,7-diazadecane-1,10-diamine, etc. Other oligomeric and polymeric compounds having a hindered amine structure may also be used.
[0369] Specific examples include ADKSTAB LA-52, LA-57, LA-63P, LA-68, LA-72, LA-77Y, LA-77G, LA-81, LA-82, LA-87, LA-402F, and LA-502XP manufactured by ADEKA Corporation; KAMISTAB 29, 62, 77, 29, and 94 manufactured by Chemipro Kasei Co., Ltd.; Tinuvin 249, TINUVIN 111FDL, 123, 144, 292, and 5100 manufactured by BASF Corporation; and Cyasorb UV-3346, UV-3529, and UV-3853 manufactured by Sun Chemical Co., Ltd.
[0370] Examples of the phosphorus-based antioxidant include tris(isodecyl) phosphite, tris(tridecyl) phosphite, phenyl isooctyl phosphite, phenyl isodecyl phosphite, phenyl di(tridecyl) phosphite, diphenyl isooctyl phosphite, diphenyl isodecyl phosphite, diphenyl tridecyl phosphite, triphenyl phosphite, tris(nonylphenyl) phosphite, 4,4'-isopropylidene diphenol alkyl phosphite, trisnonylphenyl phosphite, tris(dinonylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris(biphenyl) phosphite, distearyl pentaerythritol diphosphite, di(2,4-di-tert-butylphenyl) pentaerythritol diphosphite Acid ester, di(nonylphenyl) pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, tetra(tridecyl) 4,4'-butylene bis(3-methyl-6-tert-butylphenol) diphosphite, hexa(tridecyl) 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl) butane triphosphite, 3,5-di-tert-butyl-4-hydroxybenzyl phosphite diethyl ester, bis(4-tert-butylphenyl) sodium phosphite, 2,2-methylene-bis(4,6-di-tert-butylphenyl)-sodium phosphite, 1,3-bis(diphenoxyphosphinooxy)-benzene, ethyl bis(2,4-di-tert-butyl-6-methylphenyl) phosphite, etc. Other oligomer and polymer compounds having a phosphite structure may also be used.
[0371] Specific examples include ADKSTAB PEP-36, PEP-8, and HP-10; ADKSTAB 2112, 1178, 1500, C, 3013, and TPP manufactured by ADEKA Corporation; IRGAFOS 168 manufactured by BASF Corporation; and Hostanox P-EPQ manufactured by Clariant Chemicals Co., Ltd.
[0372] Examples of the sulfur-based antioxidant include 2,2-thio-diethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis[(octylthio)methyl]o-cresol, 2,4-bis[(laurylthio)methyl]o-cresol, 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate], and 2,2-thio-diethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. Other oligomeric and polymeric compounds having a thioether structure may also be used.
[0373] Specific examples include ADKSTABAO-412S and AO-503 manufactured by ADEKA Corporation and KEMINOX PLS manufactured by Chemipro Kasei Corporation.
[0374] As the benzotriazole antioxidant, oligomer-type and polymer-type compounds having a benzotriazole structure and the like can be used.
[0375] Specific examples include ADKSTAB LA-29, LA-31RG, LA-32, LA-36, and -412S manufactured by ADEKA Corporation; KEMISORB 71, 73, 74, 79, and 279 manufactured by Chemipro Kasei Co., Ltd.; and TINUVINPS, 99-2, 384-2, 900, 928, and 1130 manufactured by BASF Corporation.
[0376] Examples of benzophenone antioxidants include 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 2-hydroxy-4-octadecyloxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone. Other oligomeric and polymeric compounds having a benzophenone structure may also be used.
[0377] Specific examples include ADKSTAB 1413 manufactured by ADEKA Co., Ltd.; KEMISORB 10, 11, 11S, 12, and 111 manufactured by Chemipro Kasei Co., Ltd.; and UV-12 and UV-329 manufactured by Sun Chemical Co., Ltd.
[0378] Examples of the triazine antioxidant include 2,4-bis(allyl)-6-(2-hydroxyphenyl)1,3,5-triazine, etc. Other oligomeric and polymeric compounds having a triazine structure may also be used.
[0379] Specific examples include ADKSTAB LA-46 and F70 manufactured by ADEKA Corporation; KEMISORB102 manufactured by Chemipro Kasei Co., Ltd.; TINUVIN 400, 405, 460, 477, and 479 manufactured by BASF Corporation; and Cyasorb UV-1164 manufactured by Sun Chemical Co., Ltd.
[0380] Examples of salicylate antioxidants include phenyl salicylate, p-octylphenyl salicylate, p-tert-butylphenyl salicylate, etc. Other oligomeric and polymeric compounds having a salicylate structure may also be used.
[0381] These antioxidants may be used alone or in combination of two or more at any ratio as required.
[0382] In addition, from the aspect of suppressing thermal degradation of the resin composition, the content of the antioxidant is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, further preferably 0.05% by mass or more, and further preferably 0.1% by mass or more in 100% by mass of the resin composition. In addition, from the aspect of suppressing the decrease in the physical property balance of the resin composition, it is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 2% by mass or less.
[0383] <Carbon-based fillers for electrical conductivity>
[0384] In the first to third embodiments, the resin composition may further include a conductive carbon filler. Thus, a conductive resin composition can be obtained. As preferred conductive carbon fillers, carbon black, carbon fiber, graphite, graphene, carbon nanotubes, etc. can be cited. In addition, they sometimes also function as colorants. The shape of these conductive carbon fillers can be any of granular, flaky and fibrous fillers. As specific examples of preferred conductive carbon fillers, conductive carbon black, carbon nanotubes (CNT), carbon fiber, graphite, etc. can be suitably used, among which conductive carbon black and CNT are most preferred.
[0385] In the first and second embodiments, the dibutyl phthalate (DBP) absorption of the conductive carbon black is preferably 250 ml / 100 g or more, more preferably 300 ml / 100 g or more, and further preferably 350 ml / 100 g or more. In the present disclosure, the DBP absorption value is a value measured by the method specified in ASTM D2414. The upper limit of the DBP absorption value is not particularly limited, and from the perspective of ease of acquisition, it can be, for example, 400 ml / 100 g or less. In addition, as conductive carbon black, a BET surface area of 200 m 2 / g or more, and more preferably 400m 2 The upper limit of the BET surface area is not particularly limited, but from the perspective of ease of acquisition, it can be, for example, 2000 m 2 / g or less. DBP absorption value is 250ml / 100g or more and / or BET surface area is 200m 2 / g or more conductive carbon black and conventional coloring carbon black (usually the above DBP absorption value is less than 250ml / 100g, BET surface area is less than 200m 2 / g), it can show good conductivity by adding a small amount.
[0386] In the third embodiment, the dibutyl phthalate (DBP) absorption of the conductive carbon black is preferably 20 ml / 100 g or more, more preferably 30 ml / 100 g or more, and further preferably 50 ml / 100 g or more. The upper limit of the DBP absorption value is not particularly limited, and from the perspective of ease of acquisition, for example, it can be 400 ml / 100 g or less. In addition, as conductive carbon black, a BET surface area of 20 m 2 / g or more, and more preferably 40m 2 The upper limit of the BET surface area is not particularly limited, but from the perspective of ease of acquisition, it can be, for example, 2000 m 2 / g or less.
[0387] In the first to third embodiments, examples of the conductive carbon black that can be obtained as a commercial product include Ketjen Black EC-600JD and the like.
[0388] Carbon nanotubes (CNTs) are carbon fibers with a fiber diameter of 100 nm or less and a hollow structure. CNTs include single-walled carbon nanotubes whose tube walls are formed of a single layer of carbon and multi-walled nanotubes formed of multi-walled carbon.
[0389] The conductive carbon-based filler is treated with various known coupling agents and / or sizing agents to improve the adhesion with the resin and / or the handling properties.
[0390] When the entire resin composition is 100 mass%, the preferred amount of the conductive carbon filler is 0.1 to 10 mass%. The upper limit is more preferably 8 mass%, further more preferably 6 mass%, and most preferably 3 mass%. In addition, the lower limit is more preferably 0.3 mass%, further more preferably 0.5 mass%, and most preferably 0.8 mass%. In order to maintain a balance between stable conductivity and fluidity of the resin composition, it is preferably within the above range.
[0391] <Agglutination inhibitors>
[0392] In the first to third embodiments, the resin composition may further include an aggregation inhibitor. Cellulose aggregates during the drying process and has the characteristic of being difficult to redisperse. Therefore, in order to improve the redispersibility of cellulose after melt kneading with the resin, an aggregation inhibitor is preferably used. By improving the redispersibility, the mechanical properties and stability of the obtained resin composition can be improved. Preferably, the aggregation inhibitor is added to the cellulose aqueous dispersion, and then dried while applying shear to obtain a cellulose powder.
[0393] The preferred amount of the coagulation inhibitor is 2 to 100 parts by mass relative to 100 parts by mass of cellulose in the resin composition. The lower limit is more preferably 4 parts by mass, further more preferably 5 parts by mass, and most preferably 6 parts by mass. In addition, the upper limit is more preferably 80 parts by mass, further more preferably 60 parts by mass, and most preferably 40 parts by mass. In order to improve the dispersibility of cellulose in the resin and improve the stability of physical properties, it is preferred that the preferred amount be within the above range.
[0394] The aggregation inhibitor may be at least one selected from the group consisting of a surfactant, an organic compound having a boiling point of 100° C. or higher, and a resin having a chemical structure capable of highly dispersing cellulose.
[0395] As a surfactant, any surfactant having a chemical structure in which a site having a hydrophilic substituent and a site having a hydrophobic substituent are covalently bonded can be used, and surfactants used for various applications such as food applications and industrial applications can be used. For example, one or more of the following substances can be used in combination.
[0396] As the surfactant, any of anionic surfactants, nonionic surfactants, zwitterionic surfactants and cationic surfactants can be used. From the aspect of affinity with cellulose, anionic surfactants and nonionic surfactants are preferred, and nonionic surfactants are more preferred.
[0397] Among the above substances, surfactants having a polyoxyethylene chain, a carboxyl group or a hydroxyl group as a hydrophilic group are preferred from the aspect of affinity with cellulose, polyoxyethylene surfactants (polyoxyethylene derivatives) having a polyoxyethylene chain as a hydrophilic group are more preferred, and nonionic polyoxyethylene derivatives are further preferred. The polyoxyethylene chain length of the polyoxyethylene derivative is preferably 3 or more, more preferably 5 or more, more preferably 10 or more, and particularly preferably 15 or more. The longer the chain length, the higher the affinity with cellulose. From the aspect of balance with coating properties, the upper limit is preferably 60 or less, more preferably 50 or less, more preferably 40 or less, particularly preferably 30 or less, and most preferably 20 or less.
[0398] Among the above-mentioned surfactants, alkyl ether type, alkyl phenyl ether type, rosin ester type, bisphenol A type, β-naphthyl type, styrenated phenyl type, hydrogenated castor oil type can be particularly suitably used as the hydrophobic group due to their high affinity with the resin. As a preferred alkyl chain length (the number of carbon atoms excluding the phenyl group in the case of an alkylphenyl group), the carbon chain is preferably 5 or more, more preferably 10 or more, further preferably 12 or more, and particularly preferably 16 or more. When the resin is a polyolefin, the more carbon atoms there are, the higher the affinity with the resin, so there is no upper limit, and from the aspect of handling, the upper limit is preferably 30 or less, more preferably 25 or less.
[0399] Among these hydrophobic groups, groups having a cyclic structure or groups having a bulky multifunctional structure are preferred. As the group having a cyclic structure, alkylphenyl ether type, rosin ester type, bisphenol A type, β-naphthyl type and styrenated phenyl type are preferred, and as the group having a multifunctional structure, hydrogenated castor oil type is preferred. Among these, rosin ester type and hydrogenated castor oil type are particularly preferred.
[0400] In addition, as a dispersion medium of the non-surfactant system, an organic compound with a boiling point of 100°C or above is effective. Examples of such organic compounds include polyethylene glycol, polypropylene glycol, and organic compounds having a glycerol structure. In addition, although it depends on the type of resin, for example, when the resin is a polyolefin, a high-boiling point organic solvent such as liquid paraffin and decalin is effective. In addition, when the resin is a polar resin such as nylon and polyacetate, it is sometimes effective to use the same solvent as the aprotic solvent that can be used when producing cellulose (for example, dimethyl sulfoxide).
[0401] <Colorant>
[0402] In the first to third embodiments, the resin composition may further include a colorant. Among them, the organic colorant has the effect of improving the toughness of the resin composition, which is advantageous from this aspect. As organic colorants, examples include azine compounds (nigrosin, etc.), nigrosine, cyanine compounds (phthalocyanine, naphthalocyanine, etc.), porphyrin, perylene, quaternaryl triphenyl, metal complex, azo dyes, anthraquinone, squaric acid derivatives, diimmonium dyes, etc., and nigrosin is particularly preferred. Nigrosin is a component known to those skilled in the art as a black azine condensation mixture, for example, it is known that there are components recorded in the Colour Index as CISOLVENT BLACK 5, CISOLVENT BLACK 7, etc. As specific examples of nigrosin, triphenazine oxazine, phenazine azine, etc. can be illustrated. Examples of commercially available nigrosin include Nubian Black PA-9801, Nubian Black PA-9800, and Nubian Black PA-0800 (all available from Orient Chemical Industries, Ltd.). Nigrosin not only functions as a colorant, but also has an effect of delaying the crystallization of polyamide during the production of the resin composition, especially during cooling after melt kneading, thereby improving the toughness of the resin composition, suppressing the occurrence of defects, and reducing the fluctuation of the toughness of the resin composition.
[0403] From the viewpoint of obtaining the above-mentioned effect brought about by using nigrosin well, the content of nigrosin in 100% by mass of the resin composition is preferably 0.001% by mass or more, 0.01% by mass or more, or 0.03% by mass or more, and from the viewpoint of dimensional stability, the content is preferably 1% by mass or less, 0.5% by mass or less, or 0.3% by mass or less.
[0404] <Other ingredients>
[0405] The resin composition of the first to third embodiments may include, as other components, fine fiber filler components formed of highly heat-resistant organic polymers other than cellulose (e.g., fibrillated fibers or fine fibers of aramid fibers); a compatibilizer; a plasticizer; polysaccharides such as starches and alginic acid; natural proteins such as gelatin, animal glue, and casein; inorganic compounds such as zeolite, ceramics, talc, silicon oxide, metal oxides, and metal powders; fragrances; pigments; flow regulators; leveling agents; conductive agents; antistatic agents; ultraviolet absorbers; ultraviolet dispersants; deodorants and other additives. The proportion of the above-mentioned other components in the resin composition can be appropriately selected within the range that does not impair the desired effect of the present invention.
[0406] 《Manufacturing of resin composition》
[0407] There is no particular limitation on the method for preparing the resin composition of the first to third embodiments, and the following methods can be cited as specific examples. Using a single-screw or twin-screw extruder, a mixture of a first polymer (i.e., polyamide), a second polymer (e.g., polyphenylene ether), cellulose (e.g., cellulose nanofibers), and an optional elastomer (first embodiment); a mixture of polyamide, an elastomer, and cellulose (second embodiment); or a mixture of polyamide, an ethylene-vinyl ester copolymer saponified product, cellulose, and an optional elastomer (third embodiment) is melt-kneaded, extruded into a strand, cooled and solidified in a water bath, and a method of obtaining a resin composition as a pellet-like molded body; using a single-screw or twin-screw extruder, similarly melt-kneading, extruding into a rod or barrel, cooling, and obtaining a resin composition as an extruded molded body; using a single-screw or twin-screw extruder, melt-kneading, extruding using a T-die, and obtaining a sheet or film-like molded body, etc.
[0408] 《Shape of resin composition》
[0409] The resin composition of the first to third embodiments can be provided in various shapes. Specifically, resin pellets, sheets, fibers, plates, rods, etc. can be cited. For the ease of post-processing and the ease of transportation, the resin pellet shape is more preferred. As the preferred pellet shape at this time, round, oval, cylindrical, etc. can be cited. The shape of the pellets can be different depending on the cutting method during extrusion processing. Most of the pellets cut by the cutting method called water cutting are round, most of the pellets cut by the cutting method called hot cutting are round or oval, and most of the pellets cut by the cutting method called wire cutting are cylindrical. In the case of round pellets, in the case of round pellets, the preferred size is 1 mm or more and 3 mm or less in terms of pellet diameter. In addition, the preferred diameter in the case of cylindrical pellets is 1 mm or more and 3 mm or less, and the preferred length is 2 mm or more and 10 mm or less. From the perspective of operational stability during extrusion, the above diameter and length are preferably above the lower limit, and from the perspective of biteability in the molding machine during post-processing, it is preferably below the upper limit.
[0410] The resin composition of the first to third embodiments can be used as various resin molded bodies. There is no particular restriction on the manufacturing method of the resin molded body, and any manufacturing method can be applied, and injection molding, extrusion molding, blow molding, inflation molding, foaming molding, etc. can be used. Among these, injection molding is most preferred from the aspect of design and cost.
[0411] 《Characteristics of resin composition》
[0412] In the resin compositions of the first to third embodiments, the coefficient of variation CV of the tensile strength at break is preferably 10% or less from the perspective of eliminating the strength defects of the obtained molded body. The coefficient of variation mentioned here is expressed as a percentage obtained by dividing the standard deviation (σ) by the arithmetic mean (μ) and multiplying it by 100, and is a unitless number indicating relative fluctuations.
[0413] CV=(σ / μ)×100
[0414] Here, μ and σ are given by the following equations.
[0415] [Number 1]
[0416]
[0417]
[0418] Here, xi is a single data of tensile breaking strength among the n data x1, x2, x3, ..., xn.
[0419] In order to find defects more easily, the number of samples (n) when calculating the coefficient of variation CV of the tensile strength at break is preferably at least 10 or more, and more preferably 15 or more.
[0420] The upper limit of the coefficient of variation is more preferably 9%, further preferably 8%, further preferably 7%, further more preferably 6%, and most preferably 5%. The lower limit is preferably zero, but is preferably 0.1% from the viewpoint of ease of production.
[0421] Some strength defects of existing resin molded products are believed to be caused by uneven dispersion of fillers, the formation of voids, etc. As an indicator for evaluating the ease of formation of such strength defects, a method of performing a tensile test on a plurality of test pieces to confirm the presence or absence of fluctuations in breaking strength and the number of fluctuations can be cited.
[0422] For example, in the molded bodies of automobile bodies, door panels, bumpers and other structural parts, due to the presence of unevenly distributed fillers and voids, when a large stress is applied to the molded body instantly, or when a small stress is repeatedly applied such as vibration, stress concentration occurs, resulting in the molded body being broken. This reduces the reliability of the product.
[0423] Until now, it has been difficult to foresee structural defects that may occur in actual products during the test phase, and methods have been used to confirm defective parts in products using, for example, a microscope. However, observation using a microscope is extremely microscopic, and it is not possible to evaluate the entire test piece or the entire product as a whole.
[0424] The present inventors have discovered during various studies that there is a correlation between the coefficient of variation of tensile strength at break and the proportion of structural defects of a product.
[0425] To explain in more detail, for example, if the material has a uniform internal structure and no voids, then after a plurality of samples are subjected to a tensile fracture test, the stress at fracture is roughly the same value among the plurality of samples, and the coefficient of variation is very small. However, for materials with uneven parts, voids, etc. inside, the stress at fracture in a certain sample is significantly different from the stress of other samples. The degree of the number of samples showing stress different from the stress of other samples can be clarified by using the coefficient of variation as a criterion.
[0426] For example, in the case of a material without yield strength, a sample with internal defects breaks at a lower strength than other samples. In addition, in the case of a material with yield strength, most of them break in the process from yielding to necking, and the sample with internal defects tends to break at a higher strength than other samples. Although there are differences in behavior like this, the possibility of strength defects in actual products can be predicted by the coefficient of variation of tensile fracture strength.
[0427] It is believed that the dispersion state and dispersion position of the cellulose in the composition will have a significant impact on the coefficient of variation of the tensile strength at break. In addition, for example, in the case of the polyamide / elastic system alloy of the second embodiment, the elastomer phase and the interface layer between the elastomer and the polyamide are important parts for stabilizing the physical properties. For example, if the cellulose is locally present at the interface between the dispersed phase and the continuous phase or in the dispersed phase, the locally present part becomes a stress concentration point, and the physical property stability is reduced. That is, the cellulose is stably dispersed in the polyamide phase, which is beneficial to the stability of the physical properties.
[0428] In the first to third embodiments, various methods can be cited as methods for stably dispersing cellulose in the polyamide phase. For example, in the first embodiment, various methods can be cited, including a method for making the composition ratio of the total of polyamide and polyphenylene ether and optional elastomer appropriate; a method for optimizing the amount of acidic functional groups of polyphenylene ether and optional elastomer; a method for making the terminal group concentration of polyamide appropriate; a method for optimizing the addition order during cellulose kneading; a method for reducing the affinity of polyphenylene ether to cellulose or increasing the affinity to polyamide by adding an optimal surfactant, etc.; a method for pre-melting polyamide and cellulose to form a masterbatch; a method for optimizing the screw configuration during extruder processing; a method for optimizing the viscosity of the resin by temperature control during processing, and the like. In addition, for example, in the second embodiment, various methods can be cited, such as a method for making the composition ratio of polyamide and elastomer appropriate; a method for optimizing the amount of acidic functional groups in the elastomer; a method for making the terminal group concentration of polyamide appropriate; a method for optimizing the addition order of cellulose during kneading; a method for weakening the affinity of the elastomer with cellulose or increasing the affinity with polyamide by adding an optimal surfactant, etc.; a method for pre-melting polyamide and cellulose to form a masterbatch; a method for optimizing the screw configuration during extruder processing; a method for optimizing the resin viscosity by temperature control during processing, and the like.
[0429] In addition to the above, by improving the heat resistance of cellulose and preventing it from becoming a starting point of structural defects due to thermal degradation during kneading with resin, the stability of physical properties can be increased.
[0430] Any of these methods may be used to stably disperse cellulose in the polyamide phase. Setting the coefficient of variation CV of tensile strength at break to 10% or less can significantly contribute to eliminating strength defects of the resulting molded product, thereby significantly improving the reliability of the strength of the molded product.
[0431] The resin compositions of the first to third embodiments have a tendency to dramatically improve tensile yield strength compared to a single thermoplastic resin. When the tensile yield strength of a single thermoplastic resin is 1.0, the ratio of the tensile yield strength of the resin composition is preferably 1.1 times or more, more preferably 1.15 times or more, further preferably 1.2 times or more, and most preferably 1.3 times or more. The upper limit of the above ratio is not particularly limited, and from the perspective of ease of manufacture, it is preferably 5.0 times, and more preferably 4.0 times.
[0432] The resin composition of the first to third embodiments contains cellulose, and thus can exhibit low thermal expansion without increasing specific gravity. Specifically, the thermal expansion coefficient of the resin composition in the temperature range of 20°C to 100°C is preferably 70ppm / K or less, more preferably 60ppm / K or less, more preferably 50ppm / K or less, more preferably 45ppm / K or less, further more preferably 40ppm / K or less, and most preferably 35ppm / K or less. There is no particular restriction on the lower limit of the thermal expansion coefficient, and from the perspective of ease of manufacture, for example, it is preferably 5ppm / K, and more preferably 10ppm / K.
[0433] In the resin compositions of the first to third embodiments, cellulose can be stably finely dispersed in the polyamide phase, and can also have the characteristic of small fluctuation of the linear expansion coefficient in the large molded body. Specifically, it can show a characteristic of very low fluctuation of the linear expansion coefficient measured using test pieces collected from different parts of the large molded body.
[0434] When cellulose is not evenly dispersed in the resin composition and the difference in linear expansion coefficient between different parts is large, it is easy to cause a problem such as strain or warping in the molded body due to temperature changes. Moreover, this problem is caused by the difference in thermal expansion, which is a failure mode that occurs reversibly due to the rise and fall of temperature. Therefore, it may become a potentially dangerous failure mode that cannot be identified by inspection at room temperature.
[0435] The magnitude of the fluctuation in the linear expansion coefficient can be expressed by the coefficient of variation of the linear expansion coefficient of the measurement samples obtained from different parts. The calculation method of the coefficient of variation here is the same as that described in the above-mentioned coefficient of variation of tensile strength.
[0436] The coefficient of variation of the linear expansion coefficient in the resin composition of the first to third embodiments is preferably 15% or less. The upper limit of the coefficient of variation is more preferably 13%, further preferably 11%, further preferably 10%, further preferably 9%, and most preferably 8%. The lower limit is preferably zero, but from the perspective of ease of manufacture, it is preferably 0.1%.
[0437] In order to reduce the influence of data errors and the like, the number of samples (n) when calculating the coefficient of variation of the linear expansion coefficient is preferably at least 10 or more.
[0438] <Tensile fracture strain>
[0439] In the first embodiment, the tensile fracture strain of the resin composition is preferably 10% or more, or 20% or more, or 30% or more, or 40% or more, or 50% or more. Such a resin composition has excellent toughness and is preferred. It is preferred that the tensile fracture strain of the resin composition is high. From the perspective of the ease of manufacturing the resin composition, it can be, for example, 500% or less, or 200% or less, or 100% or less. The above-mentioned tensile fracture strain is a value obtained in the form of strain at fracture when a tensile test is performed on a long test piece of 70 mm in length, 10 mm in width, and 2 mm in thickness using a tensile testing machine at a temperature of 23°C, a relative humidity of 50%, a distance between chucks of 40 mm, and a tensile speed of 5 mm / min.
[0440] In the second and third embodiments, the tensile strain at break of the resin composition is preferably 10% or more, or 20% or more, or 30% or more, or 40% or more, or 50% or more. Such a resin composition is excellent in toughness and is preferred. It is preferred that the tensile strain at break of the resin composition is high, and from the perspective of the ease of manufacturing the resin composition, it can be, for example, 500% or less, or 200% or less, or 100% or less. The above-mentioned tensile strain at break is a value obtained by using a tensile testing machine to perform a tensile test on an ISO37 type 3 test piece at a temperature of 23°C and a relative humidity of 50% at a tensile speed of 5 mm / min in the form of the arithmetic average of 5 strain data at break.
[0441] The resin composition of the first to third embodiments may have the advantage of small anisotropy of physical properties. From the perspective of small anisotropy of physical properties, the orientation of cellulose (particularly the orientation of cellulose nanofibers) determined by small-angle X-ray scattering method in the central part of the multi-purpose test piece formed by the resin composition according to ISO294-1 is preferably less than 0.45, or less than 0.40, or less than 0.35, or less than 0.30, or less than 0.25, or less than 0.20. It is preferred that the above-mentioned orientation is small, but from the perspective of the ease of manufacture of the resin composition, it can be, for example, more than 0.01, or more than 0.05, or more than 0.10.
[0442] Example
[0443] The present invention will be described in more detail below with reference to the following examples, but the present invention is not limited to these examples.
[0444] -Example 1 (First Embodiment)-
[0445] Materials used
[0446] <Polyamide>
[0447] (1) Polyamide 6 (PA6)
[0448] The carboxyl terminal group ratio is: ([COOH] / [total terminal groups]) = 0.7
[0449] The viscosity value (VN) of the polyamide measured in 96 mass % sulfuric acid according to ISO307 = 95
[0450] (2) Polyamide 66 (PA66)
[0451] The carboxyl terminal group ratio is: ([COOH] / [total terminal groups]) = 0.6
[0452] The viscosity value (VN) of the polyamide measured in 96 mass % sulfuric acid according to ISO307 = 118
[0453] (3) Polyamide 610 (PA610)
[0454] The ratio of carboxyl terminal groups is: ([COOH] / [total terminal groups]) = 0.5
[0455] The viscosity value (VN) of the polyamide measured in 96 mass % sulfuric acid according to ISO307 = 115
[0456] (4) Polyamide 12 (PA12)
[0457] The carboxyl terminal group ratio is: ([COOH] / [total terminal groups]) = 0.6
[0458] The viscosity value (VN) of the polyamide measured in 96 mass % sulfuric acid according to ISO307 = 98
[0459] <Polyphenylene ether (amorphous resin)>
[0460] (1) Polyphenylene ether (hereinafter referred to as PPE)
[0461] Poly(2,6-dimethyl-1,4-phenylene oxide)
[0462] Intrinsic viscosity [η]: 0.40 dl / g, glass transition point: 210°C
[0463] (2) Maleic anhydride modified polyphenylene ether (hereinafter referred to as m-PPE)
[0464] 0.1 parts by mass of a radical initiator and 1.5 parts by mass of maleic anhydride were added to 100 parts by mass of PPE, and melt-kneaded using a twin-screw extruder at a cylinder temperature of 320° C. The addition rate of maleic anhydride in m-PPE was 0.5%, and the glass transition point was 210° C.
[0465] <Elastomer>
[0466] (1) Maleic anhydride modified styrene-ethylene butylene-styrene block copolymer (hereinafter referred to as m-SEBS)
[0467] 0.15 parts by mass of a free radical initiator and 1.4 parts by mass of maleic anhydride were added to a styrene-ethylene butylene-styrene block copolymer Tuftec H1052 (Asahi Kasei Corporation) having a bonded styrene content of 20% by mass, and melt-kneaded using a twin-screw extruder at a barrel temperature of 230° C. for preparation. It should be noted that the addition rate of maleic anhydride in m-SEBS is 0.9%, the MFR (230° C., 2.16 kgf) is 8 g / 10 minutes, and the glass transition point is -48° C.
[0468] (2) Maleic anhydride modified ethylene-octene copolymer (hereinafter referred to as m-EOR)
[0469] Fusabond MN-493D (Dow-Dupont)
[0470] MFR (190°C, 2.16 kgf) = 1.2 g / 10 min
[0471] Octene content = 28 mass%
[0472] Melting point = 55°C (DSC method: heating rate 10°C / min)
[0473] Glass transition point = -55°C
[0474] (3) Styrene-ethylene-butylene-styrene block copolymer (hereinafter referred to as SEBS)
[0475] Taipol 6151(TSRC Taiwan Rubber Corporation)
[0476] Styrene content = 33% by mass
[0477] Weight average molecular weight = 270,000
[0478] Glass transition point = -48°C
[0479] (4) Styrene-butadiene-styrene block copolymer (hereinafter referred to as SBS1)
[0480] Asaprene T-437 (Asahi Kasei Co., Ltd.)
[0481] Styrene content = 30% by mass
[0482] MFR (200°C, 5kgf) = 2g / 10min
[0483] Glass transition point = -75°C
[0484] (5) Styrene-butadiene-styrene block copolymer (hereinafter referred to as SBS2)
[0485] Tufprene A(Asahi Kasei Co., Ltd.)
[0486] Styrene content = 40 mass%
[0487] MFR (200°C, 5kgf) = 13g / 10min
[0488] Glass transition point = -75°C
[0489] (6) Styrene-butadiene-styrene block copolymer (hereinafter referred to as SBS3)
[0490] Tufprene T-438 (Asahi Kasei Co., Ltd.)
[0491] Styrene content = 35 mass%
[0492] MFR (200°C, 5kgf) = 25g / 10min
[0493] Glass transition point = -75°C
[0494] <Antioxidants>
[0495] IRGANOX 1010 (BASF Japan Co., Ltd.)
[0496] <Hydrophobic CNF>
[0497] (Fiberization process)
[0498] Cotton linter pulp was used as a raw material and stirred in dimethyl sulfoxide (DMSO) at 500 rpm at room temperature for 1 hour using a single screw mixer (DKV-1Φ125 mm dissolver manufactured by IMEX). Then, it was loaded into a bead mill (NVM-1.5 manufactured by IMEX) using a hose pump and circulated for 120 minutes using only DMSO to obtain a defibrated pulp.
[0499] (Fibration-acetylation process)
[0500] Thereafter, 11 parts by mass of vinyl acetate and 1.63 parts by mass of sodium hydrogen carbonate were added to 100 parts by mass of the defibrated slurry in the bead mill device, and the mixture was circulated for 60 minutes to obtain a hydrophobized CNF slurry.
[0501] During the circulation operation, the rotation speed of the bead mill was set to 2500 rpm and the peripheral speed was set to 12 m / s. The beads were made of zirconium oxide and had a diameter of 2.0 mm, and the filling rate was set to 70% (the slit gap of the bead mill was 0.6 mm at this time). In addition, during the circulation operation, in order to absorb the heat generated by friction, the slurry temperature was controlled at 40°C using a cooler.
[0502] 192 parts by mass of pure water was added to the obtained hydrophobized CNF slurry relative to 100 parts by mass of the defibration slurry, and after sufficient stirring, the slurry was placed in a dehydrator for concentration. The obtained wet cake was again dispersed, stirred, and concentrated using the same amount of pure water, and this washing operation was repeated a total of 5 times.
[0503] The properties of the obtained hydrophobized CNF (in the form of wet cake or porous sheet) were evaluated, and the results showed that the acyl substitution degree DS (acetylation degree) was 0.9, the crystallinity was 75%, the average fiber diameter was 65 nm, the L / D was greater than 30 (about 450), the Mw was 340,000, the Mw / Mn ratio was 5.4, and the average content of alkali-soluble polysaccharides was 3.4% by mass.
[0504] To the obtained aqueous dispersion of hydrophobized CNF (solid content: 10% by mass), 5 parts by mass of PEG20000 was added based on 100 parts by mass of hydrophobized CNF, and then vacuum dried at about 40°C using a revolution / rotation mixer (HIVIS MIX 2P-1 manufactured by Primix), thereby obtaining hydrophobized CNF powder.
[0505] Evaluation Method
[0506] <Evaluation of polymer>
[0507] [Melting point]
[0508] The polymer pellets were measured using a differential scanning calorimeter (DSC8500 manufactured by PERKINELMER) for the peak top temperature of the endothermic peak that appeared when the temperature was increased from 23°C at a temperature increase rate of 10°C / min. When two or more endothermic peaks appeared, the peak top temperature of the peak on the lowest temperature side was taken as the melting point.
[0509] [Glass transition point]
[0510] The polymer is molded according to ISO294-1. For the central part of the obtained plate-shaped multipurpose test piece, using a dynamic viscoelasticity measuring device (ARES G2 manufactured by TA Instruments), while heating from -100°C at a heating rate of 2°C / minute, measurement is carried out at an applied frequency of 10 Hz. When measuring under this condition, the storage modulus decreases significantly, and the temperature at the peak top of the peak with the largest loss modulus is measured. When two or more peaks of the loss modulus appear, the peak top temperature of the peak on the lowest temperature side is taken as the glass transition point.
[0511] <Evaluation of CNF>
[0512] [Fabrication of porous sheet]
[0513] First, the wet filter cake is added to tert-butanol, and further dispersed using a mixer or the like until there are no aggregates. Adjustment is made such that it is 0.5 g relative to the CNF solid content weight and the concentration is 0.5 mass%. 100 g of the obtained tert-butanol dispersion is filtered through filter paper, dried at 150°C, and then the filter paper is peeled off to obtain a sheet. A sheet with an air permeability resistance of 100 sec / 100 ml or less per 10 g / m 2 of the basis weight of the sheet is used as the porous sheet and used as a measurement sample.
[0514] For the basis weight W (g / m 2 ) of the sample left standing in an environment of 23°C and 50% RH for 1 day, measurement is carried out, and then the air permeability resistance R (sec / 100 ml) is measured using a Wangyan type air permeability resistance testing machine (manufactured by Asahi Seiko Co., Ltd., model EG01). At this time, the value relative to the basis weight per 10 g / m 2 is calculated according to the following formula.
[0515] Air permeability resistance (sec / 100 ml) relative to the basis weight per 10 g / m 2 = R / W × 10
[0516] [Degree of acyl substitution (DS)]
[0517] Using a Fourier transform infrared spectrophotometer (FT / IR-6200 manufactured by JASCO Corporation), infrared spectroscopic analysis based on the ATR-IR method is carried out for 5 parts of the porous sheet. The infrared spectroscopic analysis is carried out under the following conditions.
[0518] Integration times: 64 times,
[0519] Wavenumber resolution: 4 cm -1 、
[0520] Measurement wavenumber range: 4000 - 600 cm -1,
[0521] ATR crystal: diamond,
[0522] Angle of incidence: 45°
[0523] From the obtained IR spectrum, the IR index was calculated according to the following formula (1).
[0524] IR index = H1730 / H1030···(1)
[0525] Where H1730 and H1030 are 1730cm -1 、1030cm -1 The absorbance at (absorption band of CO stretching vibration of cellulose backbone chain) is respectively -1 With 1500cm -1 The line and will connect 800cm -1 With 1500cm -1 The line is taken as the baseline, and the baseline is set as the absorbance when the absorbance is 0.
[0526] Thereafter, the average degree of substitution at each measurement site was calculated from the IR index according to the following formula (2), and the average value was defined as DS.
[0527] DS = 4.13 × IR index (2)
[0528] [Crystallinity]
[0529] The porous sheet was measured by X-ray diffraction, and the crystallinity was calculated by the following formula.
[0530] Crystallinity (%) = [I (200) -I (amorphous) ] / I (200) ×100
[0531] I (200) : Diffraction peak intensity of cellulose type I crystal based on the 200 plane (2θ=22.5°)
[0532] I (amorphous) : The halo peak intensity of cellulose type I crystal based on amorphous cellulose is the peak intensity at an angle 4.5° lower than the diffraction angle of the 200-degree plane (2θ=18.0°).
[0533] (X-ray diffraction measurement conditions)
[0534] Device MiniFlex (manufactured by Rigaku Co., Ltd.)
[0535] Operation axis 2θ / θ
[0536] Radiation source CuKα
[0537] Determination method: continuous
[0538] Voltage 40kV
[0539] Current 15mA
[0540] Starting angle 2θ = 5°
[0541] End angle 2θ=30°
[0542] Sampling width 0.020°
[0543] Scanning speed 2.0° / min
[0544] Sample: Stick the porous sheet on the sample holder
[0545] [Average fiber diameter, L / D]
[0546] The wet cake was diluted with tert-butyl alcohol to 0.01% by mass, dispersed using a high shear homogenizer (manufactured by IKA, trade name "ULTRA-TURRAXT18") at a rotation speed of 25,000 rpm × 5 minutes, cast on mica, and measured using a high-resolution scanning microscope after air drying. In the measurement, the magnification was adjusted so that at least 100 cellulose fibers were observed, and the length (L), major diameter (D) and their ratio of 100 randomly selected cellulose fibers were obtained, and the arithmetic average of the 100 cellulose fibers was calculated.
[0547] [Weight average molecular weight (Mw), number average molecular weight (Mn) and Mw / Mn ratio]
[0548] Weigh 0.88g of the porous sheet, cut it into small pieces with scissors, stir it gently, add 20mL of pure water and let it stand for 1 day. Then separate the water and solid components by centrifugation. Then add 20mL of acetone, stir it gently and let it stand for 1 day. Then separate the acetone and solid components by centrifugation. Then add 20mL of N,N-dimethylacetamide, stir it gently and let it stand for 1 day. After separating N,N-dimethylacetamide and the solid components by centrifugation again, add 20mL of N,N-dimethylacetamide, stir it gently and let it stand for 1 day. Separate N,N-dimethylacetamide and the solid components by centrifugation, add 19.2g of N,N-dimethylacetamide solution prepared in a solution with 8% by mass of lithium chloride to the solid components, stir it with a stirrer, and visually confirm the dissolution. The solution containing cellulose was filtered with a 0.45μm filter, and the filtrate was used as a sample for gel permeation chromatography. The device and measurement conditions used are as follows.
[0549] Device: Tosoh HLC-8120
[0550] Column: TSKgel SuperAWM-H (6.0mmI.D.×15cm)×2
[0551] Detector: RI detector
[0552] Eluent: N,N-dimethylacetamide (lithium chloride 0.2%)
[0553] Flow rate: 0.6mL / min
[0554] Calibration curve: Pullulan conversion
[0555] [Average content of alkali-soluble polysaccharides]
[0556] The alkali-soluble polysaccharide content was determined by subtracting the α-cellulose content from the total cellulose content (Wise method) using the method described in the non-patent literature (Handbook of Wood Science Experiments, edited by the Japan Wood Society, pages 92-97, 2000) for CNF. The alkali-soluble polysaccharide content was calculated three times for one sample, and the number average of the calculated alkali-soluble polysaccharide contents was used as the average alkali-soluble polysaccharide content of CNF.
[0557] <Fender Evaluation>
[0558] [Fender molding]
[0559] The obtained pellets were used to set the cylinder temperature of the injection molding machine with a maximum clamping pressure of 4000 tons to 260°C, and a Figure 6 and 7 The schematic diagram shows a specific mold of the shape of the fender (inner cavity volume: about 1400cm 3 , Average thickness: 2mm, Projection area: about 7000cm 2 , Number of gates: 5 gates, Hot runner: It should be noted that, Figure 6 In order to clarify the runner position of the molded body, the relative position of the runner (hot runner) is shown in the figure 1), and the mold temperature is set to 80°C to mold the fender.
[0560] [Polyamide phase ratio of CNF]
[0561] Reference Figure 7 The sample cut out from the position (9) of the fender is observed using a transmission electron microscope to confirm the area (CNFp) representing the amount of cellulose present in the polyamide phase and the area (CNFo) representing the amount of cellulose present in the other phases. At this time, the polyamide phase and the other phase are appropriately dyed using a known dye so that the cellulose can be clearly confirmed.
[0562] The polyamide phase ratio of CNF was calculated by the following calculation formula.
[0563] Polyamide phase ratio of CNF = CNFp / (CNFp+CNFo)
[0564] [Water absorption]
[0565] Reference Figure 7 , cut out a square of about 10 mm from the position (10) of the fender, and collect a small flat test piece with a length of 10 mm, a width of 10 mm, and a thickness of 2 mm. Measure the weight of the test piece before water absorption (Wb). After the test piece is immersed in warm water at 80°C for 17 hours, it is exposed to a constant temperature and humidity chamber at 80°C and 57RH% for 100 hours, and then further placed in a constant temperature and humidity chamber at 23°C and 50RH% for 24 hours, and the weight of the test piece after water absorption (Wa) is measured. The water absorption rate is calculated by the following calculation formula.
[0566] Water absorption = (Wa-Wb) / Wb×100
[0567] [Linear expansion coefficient]
[0568] Reference Figure 7 A long test piece with a length of 10 mm in the resin flow direction, a length of 5 mm in the direction perpendicular to the resin flow direction, and a thickness of 2 mm was collected from the position (1) of the fender. The expansion rate of the resin in the flow direction during molding was measured in the measurement temperature range of -10°C to 120°C according to ISO11359-2, and the expansion coefficient between 20°C and 100°C was calculated. At this time, annealing was performed by standing at 120°C for 5 hours before measurement.
[0569] [Linear expansion anisotropy]
[0570] The linear expansion coefficient was measured in the measurement temperature range of -10°C to 120°C according to ISO11359-2 for the expansion rate in the direction perpendicular to the flow direction of the resin during molding, and the expansion coefficient between 20°C and 100°C was calculated. At this time, annealing was performed by standing at 120°C for 5 hours before the measurement.
[0571] The linear expansion anisotropy is calculated by the following formula.
[0572] Linear expansion anisotropy = Linear expansion coefficient in the flow direction of the resin during molding / Linear expansion coefficient in the direction perpendicular to the flow direction of the resin during molding
[0573] [Tensile fracture strain]
[0574] Reference Figure 7A long test piece with a length of 70 mm in the resin flow direction, a length of 10 mm in the direction perpendicular to the resin flow direction, and a thickness of 2 mm was collected from the position (2) of the fender. A tensile test was performed using a tensile testing machine (Autograph AG-IS manufactured by Shimadzu Corporation) at a chuck distance of 40 mm, a tensile speed of 5 mm / min, and a temperature of 23°C and 50 RH%, and the strain at break was taken as the tensile break strain.
[0575] [Orientation degree of cellulose]
[0576] The resin composition was molded according to ISO294-1, and X-rays were incident perpendicularly to the plate surface on the center of the obtained plate-shaped multi-purpose test piece, and the orientation degree of cellulose was determined by small-angle X-ray scattering. Specifically, the two-dimensional scattering pattern obtained by small-angle X-ray scattering measurement was averaged by rings to obtain a one-dimensional scattering profile, and after background correction, a 0.05 <q<0.07nm -1 The azimuthal dependence of the scattering intensity in the range of . In this case, q = 4πsinθ / λ (λ: wavelength of X-rays, 2θ: scattering angle). Based on this result, the orientation degree is calculated as follows <p2>.
[0577] Assuming three orthogonal axes, and assuming that the angles formed by the fiber axis direction of cellulose and the three axes are α, β, and γ, respectively, the following equation holds.
[0578] [Number 2]
[0579] <cos 2 α>+ <cos 2 β>+ <cos 2 γ>=1
[0580] Assuming that the angle formed by the flow direction and the cellulose fiber axis during the molding of the multipurpose test piece is α, when the cellulose is symmetrical about the flow direction, the following equation holds true.
[0581] [Number 3]
[0582] <cos 2 α>=1-2 <cos 2 β>
[0583] The scattering of the cellulose surface occurs in the β direction which is orthogonal to α, so <cos 2 β> can be calculated by the following formula.
[0584] [Number 4]
[0585]
[0586] Therefore, the orientation degree of the cellulose fiber axis <p2>It is represented by the following formula.
[0587] [Number 5]
[0588]
[0589] At this time, when fully oriented in the flow direction <p2>The orientation is 1, and the orientation is 0.
[0590] (Small-angle X-ray scattering measurement conditions)
[0591] Device: Rigaku NANOPIX
[0592] X-ray wavelength: 0.154nm
[0593] Optical system: Point collimation (1st: 0.55mmΦ, 2nd: Open, guard: 0.35mmΦ)
[0594] Detector: HyPix-6000 (2D semiconductor detector)
[0595] Camera length: 1312mm
[0596] Exposure time: 15 minutes / sample
[0597] Environment around the sample cell: Atmosphere
[0598] Test piece arrangement: Arranged so that the resin composition flows in the left-right direction when molding the multi-purpose test piece
[0599] X-ray incident direction: perpendicular to the surface of the multi-purpose test piece
[0600] The manufacture of composites
[0601] [Extruder design]
[0602] A twin-screw extruder with 13 barrel sections and an L / D of 52 (TEM SX series extruder manufactured by TOSHIBA MACHINE CO., LTD.) was used. A side feed port was provided in barrel 5 so that raw materials could be supplied from this position. In addition, a vent for reduced pressure suction was provided in barrel 12 so that volatile components and coexisting air could be removed.
[0603] As for the screw configuration, barrels 1 and 2 were used as conveying screws, and barrels 3 and 4 were provided with two clockwise kneading disks (feed type kneading disks: hereinafter referred to as RKD), followed by one neutral kneading disk (non-conveying type kneading disk: hereinafter referred to as NKD), and followed by a counterclockwise screw as a premixing zone. Barrel 5, which was a side feed zone, was used as a conveying screw, and barrels 6 and 7 were provided with one RKD and two NKDs, followed by one counterclockwise screw as a melt kneading zone. Barrels 8 and 9 were used as conveying screws, and barrel 10 was provided with one RKD, followed by one NKD, and followed by a counterclockwise screw as a kneading zone. Barrels 11 to 13 were used as conveying screws as devolatilization zones.
[0604] [Example 1-1]
[0605] The barrel 1 was water-cooled, the barrel 3 was set to 300°C, and the other barrels were set to 250°C. A mixture of 34.3 parts by mass (pbw) of m-PPE and 14.3 parts by mass of hydrophobized CNF (including 4.3 parts by mass of PEG 20000) was loaded into the barrel 1 of the extruder, mixed, and extruded into a strand. The strand was cut with a strand pelletizer to obtain m-PPE / hydrophobized CNF masterbatch pellets.
[0606] The barrel 1 was water-cooled, and the other barrels were set to 250°C. A mixture of 51.4 parts by mass of PA6 and 48.6 parts by mass of m-PPE / hydrophobized CNF masterbatch was loaded into the barrel 1 of the extruder, mixed, and extruded into a strand. The strand was cut with a strand pelletizer to obtain a hydrophobized CNF composite pellet. The composition of the obtained composite is shown in Table 1.
[0607] [Example 1-2]
[0608] The barrel 1 was water-cooled, the barrel 3 was set to 300°C, and the other barrels were set to 250°C. 34.3 parts by mass of m-PPE was loaded from the barrel 1 of the extruder, and a mixture of 51.4 parts by mass of PA6 and 14.3 parts by mass of hydrophobized CNF was further loaded from the side feed port of the barrel 5, and kneaded to obtain hydrophobized CNF composite pellets.
[0609] [Examples 1-3]
[0610] The barrel 1 was water-cooled, and the other barrels were set to 250°C. A mixture of 51.4 parts by mass of PA6 and 14.3 parts by mass of hydrophobized CNF was loaded into the barrel 1 of the extruder, kneaded, and extruded into strands. The strands were cut with a strand pelletizer to obtain PA / hydrophobized CNF masterbatch pellets.
[0611] The barrel 1 was water-cooled, the barrel 3 was set to 300°C, and the other barrels were set to 250°C. The barrel 1 of the extruder was loaded with a mixture of 34.3 parts by mass of m-PPE and 65.7 parts by mass of PA / hydrophobized CNF masterbatch, mixed, and extruded into a strand. The strand was cut with a strand pelletizer to obtain a hydrophobized CNF composite pellet. The composition of the obtained composite is shown in Table 1.
[0612] [Examples 1-4]
[0613] The barrel 1 was water-cooled, the barrel 3 was set to 300°C, and the other barrels were set to 250°C. A mixture of 51.4 parts by mass of PA6, 34.3 parts by mass of m-PPE, and 14.3 parts by mass of hydrophobized CNF was loaded into the barrel 1 of the extruder, kneaded, and extruded into a strand. The strand was cut with a strand pelletizer to obtain hydrophobized CNF composite pellets.
[0614] [Comparative Example 1-1]
[0615] Pellets were obtained in the same manner as in Example 1-4 except that the materials were kneaded according to the composition shown in Table 1 without using the hydrophobized CNF.
[0616] [Comparative Example 1-2]
[0617] Pellets were obtained in the same manner as in Example 1-4 except that the cylinder 3 was set at 250° C. and that m-PPE was not used and kneading was performed so as to have the composition shown in Table 1.
[0618] [Reference Example 1-1]
[0619] Pellets were obtained in the same manner as in Example 1-4 except that the cylinder 3 was set at 250°C and kneading was performed so as to have the composition shown in Table 1. The composition of the obtained composite is shown in Table 2.
[0620] [Examples 1-5]
[0621] The barrel 1 was water-cooled, the barrel 3 was set to 300°C, and the other barrels were set to 250°C. A mixture of 40 parts by mass of m-PPE and 10 parts by mass of SEBS was loaded from the barrel 1 of the extruder, and 50 parts by mass of PA6 was further loaded from the side feed port of the barrel 5, and kneading was performed to obtain resin pellets.
[0622] The barrel 1 was water-cooled, and the other barrels were set to 250°C. A mixture of 87.5 parts by mass of resin pellets and 14.3 parts by mass of hydrophobized CNF was loaded into the barrel 1 of the extruder, kneaded, and extruded into a strand. The strand was cut with a strand pelletizer to obtain a hydrophobized CNF composite pellet. The composition of the obtained composite is shown in Table 2.
[0623] [Examples 1-6]
[0624] Hydrophobized CNF composite pellets were obtained in the same manner as in Example 1-5 except that a mixture of 30 parts by mass of PPE, 10 parts by mass of m-PPE, and 10 parts by mass of SEBS was charged into the cylinder 1 .
[0625] [Examples 1-7, 1-8]
[0626] Hydrophobized CNF composite pellets were obtained in the same manner as in Example 1-5 except that the materials were kneaded according to the composition shown in Table 2.
[0627] [Examples 1-9]
[0628] Hydrophobized CNF composite pellets were obtained in the same manner as in Example 1-5 except that a mixture of 40 parts by mass of m-PPE and 10 parts by mass of SEBS was charged from barrel 1 and a mixture of 45 parts by mass of PA6 and 5 parts by mass of m-EOR was charged from the side feed port of barrel 5 and kneaded.
[0629] [Examples 1-10]
[0630] The barrel 1 was water-cooled, the barrel 3 was set to 300°C, and the other barrels were set to 250°C. A mixture of 50 parts by mass of PA6, 40 parts by mass of m-PPE, 10 parts by mass of SBS1 and 0.2 parts by mass of antioxidant was charged into the barrel 1 of the extruder and kneaded to obtain resin pellets.
[0631] The barrel 1 was water-cooled, and the other barrels were set at 250°C. A mixture of 87.5 parts by mass of resin pellets and 14.3 parts by mass of hydrophobized CNF was loaded into the barrel 1 of the extruder, kneaded, and extruded into strands. The strands were cut with a strand pelletizer to obtain hydrophobized CNF composite pellets.
[0632] [Examples 1-11 to 1-20]
[0633] Hydrophobized CNF composite pellets were obtained in the same manner as in Example 1-10 except that the materials were kneaded according to the compositions shown in Tables 2 and 3.
[0634]
[0635]
[0636]
[0637] -Example II (Second Embodiment)-
[0638] Materials used
[0639] <Polyamide>
[0640] Polyamide 6 rich in terminal carboxyl groups (hereinafter referred to as PA6.)
[0641] UBE nylon 1013B (Ube Industries Co., Ltd.)
[0642] The ratio of amino terminal groups is: ([NH2] / ([NH2]+[COOH]))=0.4
[0643] The viscosity value (VN) of the polyamide measured in 96 mass % sulfuric acid = 95
[0644] <Elastomer>
[0645] [Elastomer having acidic functional group]
[0646] Tufprene T912 (Asahi Kasei Corporation) (hereinafter referred to as m-SBS.)
[0647] Maleic anhydride modified styrene-butadiene-styrene block copolymer
[0648] Bonded styrene content = 40 mass%
[0649] Maleic anhydride addition rate = 0.2 mass %
[0650] Glass transition point = -75°C
[0651] Fusabond MN-493D (Dow-Dupont) (hereinafter referred to as m-EOR.)
[0652] Maleic anhydride modified ethylene-octene copolymer
[0653] MFR (190°C, 2.16 kgf) = 1.2 g / 10 min
[0654] Octene content = 28 mass%
[0655] Melting point = 55°C (DSC method: heating rate 10°C / min)
[0656] Glass transition point = -55°C
[0657] Maleic anhydride addition rate = 1.0 mass %
[0658] [Elastomer without acidic functional group]
[0659] Asaprene T-411 (Asahi Kasei Corporation) (hereinafter referred to as SBS.)
[0660] Styrene-butadiene-styrene block copolymer
[0661] Bonded styrene content = 30 mass%
[0662] Glass transition point = -75°C
[0663] <Antioxidants>
[0664] Use IRGANOX1010 (BASF Japan Co., Ltd.).
[0665] <Colorant>
[0666] Organic colorant: NUBIANBLACK PA9801 (Orient Chemical Industries, Ltd.)
[0667] Inorganic colorant: Carbon black #52 (Mitsubishi Chemical Holdings Co., Ltd.)
[0668] <Cellulose>
[0669] The same hydrophobized CNF powder as prepared in Example 1 (first embodiment) was used. In addition, the properties of the hydrophobized CNF (wet cake) were evaluated, and the results showed that the diameter was 65 nm, the L / D was 30 or more (about 450), the weight average molecular weight (Mw) was 340,000, and the degree of acetylation was 0.9.
[0670] Evaluation Method
[0671] [Length, diameter, L / D of hydrophobized CNF]
[0672] The wet cake was made into a pure water suspension at a concentration of 1% by mass, and dispersed using a high shear homogenizer (manufactured by Nippon Seiki Co., Ltd., trade name "EXCEL Auto Homogenizer ED-7", processing conditions: rotation speed 15,000 rpm×5 minutes). The resulting aqueous dispersion was diluted with pure water to 0.1-0.5% by mass, poured on mica, and after air-drying, measured using an atomic force microscope (AFM). The ratio (L / D) of the length (L) and the diameter (D) of the particle image obtained at this time was determined and calculated as an average value of 100 to 150 particles.
[0673] [Confirmation of continuous phase]
[0674] The obtained pellets were immersed in chloroform to check whether there was any change in shape. Since no particular change occurred in the examples and comparative examples implemented this time, it was determined that the polyamide formed a continuous phase.
[0675] [Ratio of cellulose to polyamide phase]
[0676] The obtained composition was sliced with a thickness of 1 μm using an ultrathin slicer to obtain a film-like sample, which was then immersed in chloroform to dissolve the elastomer phase. The eluate was concentrated and subjected to ultracentrifugal separation. After cellulose was separated, the cellulose was washed with chloroform and ultracentrifugal separation was repeated three times. The remaining cellulose was dried and used as the amount of cellulose present in the elastomer phase. The obtained amount was subtracted from the feed amount, divided by the feed cellulose amount, and the obtained ratio was expressed as a percentage as the cellulose polyamide phase ratio.
[0677] [Number average particle size of dispersed elastomer particles and volume ratio of dispersed particles having a particle size of 1 μm or more]
[0678] The obtained composition was photographed using a transmission electron microscope. The number average value of the particle size (ie, dispersed particle size) of 500 dispersed particles of the elastomer dispersed phase and the volume ratio of dispersed particles having a particle size of 1 μm or more were calculated.
[0679] [Thermal expansion (thermal expansion coefficient)]
[0680] A sample with a length of 10 mm, a width of 4 mm, and a thickness of 2 mm was cut from the center of the test piece (ISO37 type 3) using a precision cutting saw. The expansion coefficient in the flow direction of the resin during molding (MD direction, length direction of the sample) was measured in the measurement temperature range of -10°C to 120°C according to ISO11359-2, and the thermal expansion coefficient (hereinafter referred to as CTE) between 20°C and 100°C was calculated. MD ). At this time, before the measurement, the sample was left to stand for 5 hours in an environment of 120°C for annealing.
[0681] [Toughness tensile fracture strain]
[0682] A tensile test was performed on the test piece (ISO37 type 3) at a temperature of 23°C and a relative humidity of 50% at a tensile speed of 5 mm / min using a tensile tester (Autograph AG-IS manufactured by Shimadzu Corporation). The five strain data at the time of tensile fracture were arithmetic averaged to determine the toughness index.
[0683] Extrusion Conditions
[0684] [Extruder design]
[0685] A twin-screw extruder (TEM SX series extruder manufactured by TOSHIBA MACHINE CO., LTD.) with 13 barrel sections and L / D of 52 was used, and barrel 1 was water-cooled, barrels 2 to 4 were set to 150° C., and barrel 5 to the die head were set to 250° C. A vent for reduced pressure suction was provided in barrel 12 to remove volatile components and coexisting air.
[0686] As for the screw structure, barrels 1 and 2 were set as conveying screws, and three clockwise kneading disks (feed type kneading disks: hereinafter sometimes referred to as RKD) were arranged on barrel 3. As a pre-mixing zone, barrel 4 was set as a conveying screw, and barrels 5 and 6 were set with one RKD and two neutral kneading disks (non-conveying type kneading disks: hereinafter sometimes referred to as NKD), and then one counterclockwise screw was set as a melt kneading zone. Barrels 7 to 9 as side feed zones were set as conveying screws, and barrel 10 was set with two RKDs, and then three NKDs and then a counterclockwise screw was set as a kneading zone. Barrels 11 to 13 were set as conveying screws as devolatilization zones. In addition, as for the die, a die having two holes with a diameter of 3 mm was installed.
[0687] 《Manufacturing of resin composition》
[0688] [Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-2]
[0689] The mixture was mixed at the ratio shown in Table 4 using an extruder in the extruder design, and melt-kneaded at a screw speed of 300 rpm to obtain pellets, which were then subjected to various evaluations. The results are shown in Table 4.
[0690] In addition, the column of mass parts in the table shows the charging formula, the mass % column in the middle section shows the composition, and the lower section shows the physical properties.
[0691] According to the results shown in the table, each example using an elastomer that is an aromatic vinyl compound-conjugated diene compound block copolymer or a derivative thereof shows high fracture strain (i.e., good toughness) and low thermal expansion coefficient, whereas Comparative Example 2-1 using an ethylene-octene copolymer as an elastomer has a poor thermal expansion coefficient, and Comparative Example 2-2 using no elastomer has a poor fracture strain. In addition, when comparing Examples 2-4, 2-5, and 2-6 using a colorant with Example 2-1 not using a colorant, Examples 2-4, 2-5, and 2-6 have higher fracture strains.
[0692]
[0693] -Example III (Third Embodiment)-
[0694] Materials used
[0695] <Polyamide>
[0696] PA6: UBE nylon 1013B (Ube Kosan Co., Ltd.)
[0697] Polyamide 6 rich in terminal carboxyl groups
[0698] The ratio of amino terminal groups is: ([NH2] / ([NH2]+[COOH]))=0.4
[0699] The viscosity value (VN) of the polyamide measured in 96 mass % sulfuric acid = 95
[0700] <Elastomer>
[0701] [Elastomer having acidic functional group]
[0702] m-EOR: Fusabond MN-493D(Dow-Dupont)
[0703] Maleic anhydride modified ethylene-octene copolymer
[0704] MFR (190°C, 2.16 kgf) = 1.2 g / 10 min
[0705] Octene content = 28 mass%
[0706] Melting point = 55°C (DSC method: heating rate 10°C / min)
[0707] Glass transition point = -55°C
[0708] Maleic anhydride addition rate = 1.0 mass %
[0709] m-SBS: Tufprene T912 (Asahi Kasei Co., Ltd.)
[0710] Maleic anhydride modified styrene-butadiene-styrene block copolymer
[0711] Bonded styrene content = 40 mass%
[0712] Maleic anhydride addition rate = 0.2 mass %
[0713] Glass transition point = -75°C
[0714] [Elastomer without acidic functional group]
[0715] SBS: Asaprene T-411 (Asahi Kasei Co., Ltd.)
[0716] Styrene-butadiene-styrene block copolymer
[0717] Bonded styrene content = 30 mass%
[0718] Glass transition point = -75°C
[0719] <Ethylene-vinyl ester copolymer saponification product>
[0720] EVOH-1: Soarnol V2504 (Mitsubishi Chemical Holdings Co., Ltd.)
[0721] Ethylene composition = 25 mol%, vinyl alcohol composition = 75 mol%, melting point = 195°C, glass transition point = 63°C
[0722] EVOH-2: Eval M100B (KURARAY Co., Ltd.)
[0723] Ethylene composition = 24 mol%, vinyl alcohol composition = 76 mol%, melting point = 195°C, glass transition point = 60°C
[0724] EVOH-3: Eval L104B (KURARAY Co., Ltd.)
[0725] Ethylene composition = 27 mol%, vinyl alcohol composition = 73 mol%, melting point = 190°C, glass transition point = 63°C
[0726] EVOH-4: Soarnol DT2904 (Mitsubishi Chemical Holdings Co., Ltd.)
[0727] Ethylene composition = 29 mol%, vinyl alcohol composition = 71 mol%, melting point = 188°C, glass transition point = 62°C
[0728] EVOH-5: Soarnol DC3212 (Mitsubishi Chemical Holdings Co., Ltd.)
[0729] Ethylene composition = 32 mol%, vinyl alcohol composition = 68 mol%, melting point = 183°C, glass transition point = 61°C
[0730] EVOH-6: Eval C109B (KURARAY Co., Ltd.)
[0731] Ethylene composition = 35 mol%, vinyl alcohol composition = 65 mol%, melting point = 177°C, glass transition point = 58°C
[0732] <Other ingredients>
[0733] Antioxidant: IRGANOX 1010 (BASF Japan Co., Ltd.)
[0734] Organic colorant: NUBIANBLACK PA9801 (Orient Chemical Industries, Ltd.)
[0735] Inorganic colorant: Carbon black #CB960 (Mitsubishi Chemical Holdings Co., Ltd.)
[0736] <Cellulose Nanofiber>
[0737] [Preparation Example 1] Cellulose nanofiber (hereinafter referred to as CNF)
[0738] After the cotton linter pulp is cut, it is heated in hot water at 120°C or higher for 3 hours using an autoclave to remove the hemicellulose part, and the obtained refined pulp is squeezed, and the solid content in pure water is 1.5% by mass to highly short-fiberize and fibrillate, and then the concentration is maintained by a high-pressure homogenizer (10 times of treatment at an operating pressure of 85 MPa) to obtain defibrated cellulose. Here, in the beating treatment, a disc refiner is used, and a beating blade with a high cutting function (hereinafter referred to as a cutting blade) is used for 4 hours, and then a beating blade with a high defibration function (hereinafter referred to as a defibration blade) is used for further 1.5 hours of beating.
[0739] The properties of the obtained CNF were evaluated, and as a result, the diameter was 90 nm and the L / D was 30 or more (about 300).
[0740] To the obtained CNF water dispersion was added 5 parts by mass of PEG20000 based on 100 parts by mass of CNF, and then vacuum dried at about 40°C using a revolution-rotation mixer (HIVIS MIX 2P-1 manufactured by Primix) to obtain CNF powder.
[0741] [Preparation Example 2] Acetylated cellulose nanofibers (hereinafter referred to as acetylated CNF)
[0742] The same hydrophobized CNF powder as prepared in Examples I and II (first and second embodiments) was used. In addition, the properties of the acetylated CNF (wet cake) were evaluated, and the results showed that the diameter was 65 nm, the L / D was 30 or more (about 450), the weight average molecular weight (Mw) was 340,000, and the degree of acetylation was 0.9.
[0743] [Preparation Example 3] Acetylated cellulose microfibers (hereinafter referred to as acetylated CMF)
[0744] The same procedure as in Preparation Example 1 was followed except that the high-pressure homogenizer treatment in Preparation Example 1 was repeated twice to obtain a defibrated pulp. The obtained defibrated pulp was treated in the same manner as in Preparation Example 2 in the defibration-acetylation step.
[0745] The properties of the obtained acetylated CMF were evaluated, and the diameter was 12 μm and the L / D was 30 or more (about 200).
[0746] After adding 5 parts by mass of PEG20000 to 100 parts by mass of acetylated CMF to the obtained aqueous dispersion of acetylated CMF (solid content: 10% by mass), the mixture was vacuum dried at about 40°C using a revolution-rotation mixer (HIVIS MIX 2P-1 manufactured by Primix) to obtain acetylated CMF powder.
[0747] Evaluation Method
[0748] [Weight average molecular weight (Mw) and degree of acetylation]
[0749] The measurement was performed by the same procedure as in Example I (first embodiment) except that powder was used instead of the porous sheet.
[0750] [Length, diameter, L / D of CNF, acetylated CNF, acetylated CMF]
[0751] The wet cake was made into a pure water suspension at a concentration of 1% by mass, and dispersed using a high shear homogenizer (manufactured by Nippon Seiki Co., Ltd., trade name "EXCEL Auto Homogenizer ED-7", processing conditions: rotation speed 15,000 rpm×5 minutes). The obtained aqueous dispersion was diluted with pure water to 0.1-0.5% by mass, poured on mica, and measured using an atomic force microscope (AFM) after air drying. The ratio (L / D) of the length (L) and the diameter (D) of the particle image obtained at this time was obtained and calculated as an average value of 100 to 150 particles.
[0752] [Confirmation of continuous phase]
[0753] The confirmation was performed by the same procedure as in Example II (Second Embodiment). Since no particular changes were made in the examples and comparative examples implemented this time, it was determined that the polyamide formed a continuous phase.
[0754] [Linear thermal expansion coefficient]
[0755] The measurement was performed by the same procedure as in Example II (second embodiment).
[0756] [Tensile fracture strain]
[0757] The tensile test was carried out in the same manner as in Example II (the second embodiment) to obtain five data of strain at tensile fracture. The number average of the five fracture strains was used as an indicator of toughness, and the difference between the maximum and minimum values among the five fracture strains, i.e., the fracture strain range, was used as an indicator of the fluctuation of toughness.
[0758] Extrusion Conditions
[0759] [Extruder design]
[0760] The same extruder design as in Example II (second embodiment) was used.
[0761] 《Manufacturing of resin composition》
[0762] [Examples 3-1 to 3-16, Comparative Examples 3-1 to 3-3]
[0763] Using an extruder in the extruder design, the mixture was mixed at the ratios shown in Tables 5 and 6, and melt-kneaded at a screw speed of 300 rpm to obtain pellets, which were then subjected to various evaluations. The results are shown in Tables 5 and 6.
[0764] In addition, the column of mass parts in the table shows the charging formula, the mass % column in the middle section shows the composition, and the lower section shows the physical properties.
[0765] According to the results shown in the table, in each embodiment including polyamide, ethylene-vinyl ester copolymer saponified product and cellulose nanofiber, high fracture strain (i.e. good toughness) and low linear thermal expansion coefficient are shown, while in each comparative example not including ethylene-vinyl ester copolymer saponified product or polyamide, the fracture strain is poor. In addition, Example 3-5 using acetylated CNF is compared with Example 3-12 using CNF, and the fluctuation of toughness in Example 3-5 using acetylated CNF is smaller. In addition, Example 3-13, 3-14, 3-15 using colorant is compared with Example 3-5 without colorant, and the fluctuation of toughness in Example 3-13, 3-14, 3-15 is smaller.
[0766]
[0767]
[0768] Industrial Applicability
[0769] The resin combination of the present embodiment can have the excellent characteristics particularly suitable for large-scale component purposes. That is, the resin combination of the first embodiment can have low specific gravity, high rigidity, low thermal expansion coefficient and low water absorption, and therefore can be suitably used for various large-scale component purposes. In addition, the resin combination of the second and third embodiments can highly take into account the opposite characteristics such as high toughness and low thermal expansion, and has sufficient physical property stability that can be resistant to practical use, and therefore can be suitably used for, for example, requiring to show the purposes of high physical property in a wide temperature region (as the field of the automotive exterior material purposes of large-scale components, etc.).
Claims
1. A resin composition comprising: Polyamide, Polyphenylene ether, and Cellulose nanofibers, in, The polyamide forms a continuous phase, the polyphenylene ether forms a dispersed phase, and more than 50 mass % of the cellulose nanofibers exist in the polyamide phase.
2. The resin composition according to claim 1, wherein The amount of the polyphenylene ether is 30 to 150 parts by mass based on 100 parts by mass of the polyamide.
3. The resin composition according to claim 1 or 2, wherein At least a portion of the polymer present in the dispersed phase has acidic functional groups.
4. The resin composition according to claim 1 or 2, wherein The polyphenylene ether is acid-modified with an α,β-unsaturated carboxylic acid or a derivative thereof.
5. The resin composition according to claim 4, wherein The acid modification degree of the polyphenylene ether is 0.2% to 2%.
6. The resin composition according to claim 1 or 2, wherein The polyphenylene ether exists in the continuous phase of the polyamide in the form of dispersed particles having a number average particle size of 3 μm or less.
7. The resin composition according to claim 1 or 2, wherein The polyphenylene ether exists in the continuous phase of the polyamide in the form of dispersed particles. The dispersed particles have a volume ratio such that the volume ratio of particles having a particle size of 1 μm or more is 30 volume % or less.
8. The resin composition according to claim 1 or 2, wherein The polyphenylene ether has an intrinsic viscosity [η] of 0.2 dl / g or more.
9. The resin composition according to claim 1 or 2, wherein The polyphenylene ether is contained in an amount of 20% by mass or more and 50% by mass or less relative to 100% by mass of the resin composition. 10 . The resin composition according to claim 1 , further comprising an elastomer.
11. The resin composition according to claim 10, wherein Inside the dispersed phase of the polyphenylene ether, the polyphenylene ether forms a continuous phase, and the elastomer forms a dispersed phase.
12. The resin composition according to claim 10, wherein The elastomer is one or more selected from the group consisting of ethylene-α-olefin copolymers, block copolymers of aromatic vinyl compounds and conjugated diene compounds, and hydrogenated products of block copolymers of aromatic vinyl compounds and conjugated diene compounds.
13. The resin composition according to claim 10, wherein The elastomer is an anhydride-modified elastomer.
14. The resin composition according to claim 10, wherein The elastomer is a mixture of an elastomer having an acidic functional group and an elastomer not having an acidic functional group.
15. The resin composition according to claim 10, wherein The polyphenylene ether has an acidic functional group, and the elastomer does not have an acidic functional group, or The polyphenylene ether does not have an acidic functional group, and the elastomer has an acidic functional group, or The polyphenylene ether has an acidic functional group, and the elastomer has an acidic functional group.
16. The resin composition according to claim 10, wherein The elastomer accounts for 5% by mass or more and 30% by mass or less relative to 100% by mass of the resin composition.
17. The resin composition according to claim 1 or 2, wherein In the center portion of a multipurpose test piece obtained by molding the resin composition in accordance with ISO 294-1, the degree of orientation of the cellulose nanofibers determined by a small-angle X-ray scattering method is 0.45 or less.
18. The resin composition according to claim 1 or 2, wherein The amount of the cellulose nanofibers is 0.1% by mass to 30% by mass based on 100% by mass of the resin composition.
19. The resin composition according to claim 1 or 2, wherein The cellulose nanofibers are hydrophobized cellulose nanofibers.
20. The resin composition according to claim 19, wherein The hydrophobization degree of the cellulose nanofibers is 0.2 or more and 1.5 or less, expressed as an average degree of substitution of hydroxyl groups.
21. The resin composition according to claim 19, wherein The hydrophobized cellulose nanofibers are acetylated cellulose nanofibers.
22. The resin composition according to claim 1 or 2, wherein The cellulose nanofibers have a weight average molecular weight (Mw) of 100,000 or more, and a ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of 6 or less.
23. The resin composition according to claim 1 or 2, wherein The cellulose nanofibers have an average alkali-soluble polysaccharide content of 12% by mass or less and a crystallinity of 60% or more.
24. The resin composition according to claim 1 or 2, wherein The cellulose nanofibers account for 3% to 15% by mass based on 100% by mass of the resin composition.
25. The resin composition according to claim 1 or 2, wherein The polyamide is one or more selected from the group consisting of polyamide 6, polyamide 10, polyamide 11, polyamide 12, polyamide 66, polyamide 610, polyamide 612, polyamide 6 / 6I, polyamide 66 / 6I, polyamide 6I, and mixtures thereof.
26. The resin composition according to claim 1 or 2, wherein When measured in 96 mass % sulfuric acid according to ISO 307, the viscosity value (V N ) is less than 200.
27. The resin composition according to claim 1 or 2, wherein The ratio of the carboxyl terminal groups of the polyamide to the total terminal groups is 0.20 to 0.
95.
28. The resin composition according to claim 1 or 2, wherein The polyamide accounts for 30% to 70% by mass based on 100% by mass of the resin composition.
29. The resin composition according to claim 1 or 2, further comprising a saponified ethylene-vinyl ester copolymer.
30. The resin composition according to claim 1 or 2, further comprising an antioxidant.
31. The resin composition according to claim 1 or 2, further comprising a colorant.
32. The resin composition according to claim 1 or 2, which has a thermal expansion coefficient of 50 ppm / K or less at 20°C to 100°C.
33. A molded product comprising the resin composition according to any one of claims 1 to 32.
34. An automobile exterior part, comprising the resin composition according to any one of claims 1 to 32.
Citation Information
Patent Citations
Manufacture of reactor blend polyolefin and catalyst therefor
JP1985035006A
Method and catalyst for controlling polyolefin density and molecular weight
JP1985035007A
Manufacture of polyethylene having broad molecular weight distribution and catalyst therefor
JP1985035008A
Stabilized polyphenylene ether-polyamide composition
JP1989163262A
Catalyst for use in closed geometric addition polymerization, its manufacture, precursor thereof, method of its use and novel polymer prepared thereby
JP1991163088A